Photosensitive composition, cured product, electronic component, and method for producing cured product

By using a photosensitive composition containing a specific resin structure and a functionalized acid, the problem of insufficient mechanical properties and migration resistance of hardened substances at low temperatures in the prior art is solved, and the effect of suppressing development residues and improving the reliability of electronic parts is achieved.

CN119895333APending Publication Date: 2025-04-25TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380066747.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-09-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide hardened products with excellent mechanical properties and migration resistance at low temperatures, especially while suppressing the development residue.

Method used

A photosensitive composition is employed, which comprises a binder resin, a photosensitive agent, a free radical polymerizable compound and/or a crosslinking agent. The resin of the composition contains specific resin structures, such as imide, oxazole and silicone structures, and contains specific sulfonic acids, phosphate esters and fluorine contents to improve the mechanical properties and migration resistance of the hardened substance.

Benefits of technology

Excellent mechanical properties and migration resistance of the hardened substance when heated at low temperatures are achieved, while suppressing the residue after development and improving the reliability of electronic parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119895333A_ABST
    Figure CN119895333A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a cured product having excellent mechanical properties even when heated at low temperatures by suppressing residues after development and increasing the degree of crosslinking of a resin or promoting a ring-closure reaction. The purpose of the present invention is also to provide a cured product included in an electronic component having excellent migration resistance. The present invention is a photosensitive composition containing (A) a binder resin and (C) a photosensitizer, and further containing (B) a radically polymerizable compound and / or (F) a cross-linking agent, in which the binder resin (A) contains the following resin (A1) and / or (A2) and satisfies the following condition (alpha). (A1) a resin: a resin containing, in a constituent unit of a main chain of the resin, one or more types of resin selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure; (A2) resin: a resin having a phenolic hydroxyl group in a constituent unit of the main chain of the resin; and (alpha) one or more elements selected from the group consisting of sulfonic acids, phosphoric acid esters, phosphonic acids, phosphonic acid esters, phosphite esters, phosphinic acids, phosphinic acid esters, and carboxylic acids containing elemental fluorine, the total content of these organic acids being within a specific range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photosensitive composition, a cured product, an electronic component, and a method for producing the cured product. Background Art

[0002] In recent years, electronic terminal devices have been continuously developed towards high functionality, miniaturization, thinness, and lightness. These electronic terminal devices include semiconductor devices, such as processors or memories. As representative materials for the surface protection layer or interlayer insulating layer of a semiconductor device, the insulating layer of an organic electroluminescent (hereinafter referred to as "organic EL (electroluminescence)") display, or the planarization layer of a thin-film transistor (hereinafter referred to as "TFT (thin film transistor)") substrate, resins such as polyimide or polybenzoxazole with excellent heat resistance or electrical insulation can be cited. Furthermore, in order to improve productivity, photosensitive polyimide / polybenzoxazole materials and photosensitive polyimide precursors / polybenzoxazole precursors that impart positive or negative photosensitivity are also studied.

[0003] As the use of semiconductors expands or their performance improves, efforts are being made to reduce costs and achieve high integration by improving the efficiency of the manufacturing process, and semiconductor devices that form multi-layer metal redistribution have attracted attention. The materials used in the interlayer insulating layers in such multi-layer metal redistribution are required to have high mechanical properties to withstand the stress associated with multi-layering. Furthermore, it is also necessary to take into account the suppression of development residues when forming positive or negative patterns by photolithography. In addition, due to the miniaturization of wiring associated with the high integration of semiconductor devices, reliability related to electrical insulation is also required, and therefore high migration resistance is also required.

[0004] In addition, the molded resins used in memory or semiconductor packaging in recent years have low heat resistance and cannot be used in high-temperature processes. Therefore, the materials used in the surface protection layer or interlayer insulation layer of the semiconductor device are also required to be able to harden even at a low temperature of 250°C or less, and ideally 220°C or less, and have high mechanical properties.

[0005] As materials with improved mechanical properties, for example, compositions in which a soft polyoxyalkylene structure is introduced into the main chain of polyimide can be cited (for example, see Patent Document 1). In addition, as materials that can be cured even by heating at low temperatures, for example, compositions containing resins such as polyimide or polybenzoxazole and a thermal crosslinking agent can be cited (for example, see Patent Document 2).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2012-208360

[0009] Patent Document 2: Japanese Patent Application Publication No. 2007-016214 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, the composition described in Patent Document 1 or Patent Document 2 has a problem in providing a cured product having excellent mechanical properties and migration resistance when heated at low temperature while suppressing the development residue. Therefore, it is desired to further improve the properties of the photosensitive composition. The object of the present invention is to provide a cured product including an electronic component having excellent mechanical properties and excellent migration resistance while suppressing the development residue. In addition, another object of the present invention is to provide an electronic component having excellent migration resistance.

[0012] Technical means of solving problems

[0013] To solve the above problems, the photosensitive composition and electronic component of the present invention have the following structures [1] to

[20] .

[0014] [1] A photosensitive composition comprising (A) a binder resin and (C) a photosensitizer, and further comprising (B) a radical polymerizable compound and / or (F) a crosslinking agent, wherein:

[0015] The (A) binder resin contains the following (A1) resin and / or (A2) resin,

[0016] The following condition (α) is satisfied.

[0017] (A1) Resin: A resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin

[0018] (A2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin

[0019] (α) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (1x)

[0020] (1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0021] [2] The photosensitive composition according to [1], wherein the sulfonic acid, and the phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, and phosphinate ester (hereinafter referred to as "organic acid containing phosphorus element") have the following specific substituent a,

[0022] The carboxylic acid containing fluorine element has the following specific substituent b,

[0023] The condition (α) is the following condition (α2), and satisfies the following condition (α2).

[0024] (α2) further contains one or more selected from the group consisting of a sulfonic acid having the following specific substituent a, an organic acid containing a phosphorus element having the following specific substituent a, and a carboxylic acid containing a fluorine element having the following specific substituent b, and satisfies the following condition (1y):

[0025] Specific substituent a: one or more selected from the group consisting of a monovalent aliphatic group to a divalent aliphatic group having 1 to 18 carbon atoms, a monovalent alicyclic group to a divalent alicyclic group having 4 to 18 carbon atoms, a monovalent aromatic group to a divalent aromatic group having 6 to 15 carbon atoms, a monovalent fluorinated aliphatic group to a divalent fluorinated aliphatic group having 1 to 18 carbon atoms, a monovalent fluorinated alicyclic group to a divalent fluorinated alicyclic group having 4 to 18 carbon atoms, and a monovalent fluorinated aromatic group to a divalent fluorinated aromatic group having 6 to 15 carbon atoms

[0026] Specific substituent b: one or more selected from the group consisting of monovalent fluorinated aliphatic groups to divalent fluorinated aliphatic groups having 1 to 18 carbon atoms, monovalent fluorinated alicyclic groups to divalent fluorinated alicyclic groups having 4 to 18 carbon atoms, and monovalent fluorinated aromatic groups to divalent fluorinated aromatic groups having 6 to 15 carbon atoms

[0027] (1y) The total content of the sulfonic acid having the specific substituent a, the organic acid containing phosphorus having the specific substituent a, and the carboxylic acid containing fluorine having the specific substituent b in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0028] [3] The photosensitive composition according to [2], wherein the condition (α2) is the following condition (α3), and the following condition (α3) is satisfied:

[0029] The sulfonic acid contains one or more selected from the group consisting of methanesulfonic acid, cyclohexanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, xylenesulfonic acid, trifluoromethanesulfonic acid, hexafluorocyclohexanesulfonic acid, hexafluorobenzenesulfonic acid, pentafluorotoluenesulfonic acid, tetrafluoroxylenesulfonic acid, trifluoromethylbenzenesulfonic acid, trifluoromethyltoluenesulfonic acid, and trifluoromethylxylenesulfonic acid.

[0030] The carboxylic acid containing fluorine element includes at least one selected from the group consisting of trifluoroacetic acid, trifluoropropionic acid, hexafluorocyclohexanecarboxylic acid, hexafluorobenzoic acid, and trifluoromethylbenzoic acid.

[0031] (α3) further contains sulfonic acid and / or carboxylic acid containing fluorine element and satisfies the following condition (1z):

[0032] (1z) The total content of the sulfonic acid and the carboxylic acid containing a fluorine element in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0033] [4] The photosensitive composition according to any one of [1] to [3], further satisfying the following condition (β).

[0034] (β) further contains one or more selected from the group consisting of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (2x):

[0035] (2x) The total content of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0036] [5] The photosensitive composition according to any one of [1] to [4], further satisfying the following condition (γ).

[0037] (γ) further contains one or more selected from the group consisting of benzene, toluene, xylene, and naphthalene, and satisfies the following condition (3)

[0038] (3) The total content of benzene, toluene, xylene, and naphthalene in the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0039] [6] The photosensitive composition according to any one of [1] to [5], wherein the (A) binder resin comprises the (A1) resin,

[0040] The (A1) resin contains one or more selected from the group consisting of the following (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, (A1-5) resin, (A1-6) resin, and copolymers containing two or more of these resins.

[0041] (A1-1) Resin: Polyimide

[0042] (A1-2) Resin: Polyimide precursor

[0043] (A1-3) Resin: polybenzoxazole

[0044] (A1-4) Resin: polybenzoxazole precursor

[0045] (A1-5) Resin: Polyamide-imide

[0046] (A1-6) Resin: polyamideimide precursor.

[0047] [7] The photosensitive composition according to any one of [1] to [6], further comprising one or more selected from the group consisting of a cyclic amide compound represented by the general formula (20), an amide compound represented by the general formula (21), a cyclic urea compound represented by the general formula (22), a urea compound represented by the general formula (23), an oxazolidinone compound represented by the general formula (24), and an isoxazolidinone compound represented by the general formula (25), and satisfies the condition (4) below.

[0048] (4) The total content of the cyclic amide compound represented by the general formula (20), the amide compound represented by the general formula (21), the cyclic urea compound represented by the general formula (22), the urea compound represented by the general formula (23), the oxazolidinone compound represented by the general formula (24), and the isoxazolidinone compound represented by the general formula (25) in the total solid content of the photosensitive composition is 0.010% by mass to 5.0% by mass

[0049] [Chemistry 1]

[0050]

[0051] In the general formulas (20) to (25), R 46 ~R 56 R each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms. 130 R represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyalkyl group having 1 to 6 carbon atoms, a hydroxyalkoxy group having 1 to 6 carbon atoms, a hydroxy group, an amino group, a monoalkylamino group having 1 to 6 carbon atoms, or a dialkylamino group having 2 to 12 carbon atoms. 131 ~R 142Each independently represents an alkyl group having 1 to 6 carbon atoms. α, β, and γ each independently represent an integer of 0 to 6. a, b, c, e, f, g, h, i, j, k, l, and m each independently represent an integer of 0 to 2. When α is 0, a is 0. When β is 0, b is 0. When γ is 0, c is 0.

[0052] [8] The photosensitive composition according to any one of [1] to [7], further comprising one or more selected from the group consisting of a component containing a sodium element, a component containing a potassium element, a component containing a magnesium element, a component containing a calcium element, a component containing an iron element, a component containing a copper element, and a component containing a chromium element, and satisfies the following condition (5).

[0053] (5) The total content of the sodium element, potassium element, magnesium element, calcium element, iron element, copper element, and chromium element in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0054] [9] The photosensitive composition according to any one of [1] to [8], wherein the (C) photosensitive agent contains a (C1) photopolymerization initiator, and the (C1) photopolymerization initiator contains a (C1-1) oxime ester compound and / or a (C1-2) phosphine oxide compound.

[0055]

[10] The photosensitive composition according to any one of [1] to [9], further comprising at least one selected from the group consisting of acetic acid, propionic acid, cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, and trimethylbenzoic acid, and satisfies the following condition (6):

[0056] and / or

[0057] It further contains an aldoxime compound and / or a ketoxime compound and satisfies the following condition (7).

[0058] (6) The total content of acetic acid, propionic acid, cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, and trimethylbenzoic acid in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0059] (7) The total content of the aldoxime compound and the ketoxime compound in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0060]

[11] The photosensitive composition according to any one of [1] to

[10] , further comprising one or more selected from the group consisting of a component containing a chlorine element, a component containing a bromine element, and a component containing a sulfur element, and satisfies the following conditions (8) and / or (9),

[0061] and / or

[0062] It also contains water and satisfies the following condition (10).

[0063] (8) The total content of chlorine and bromine in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0064] (9) The content of sulfur in the total solid content of the photosensitive composition is 0.010 ppm by mass to 500 ppm by mass

[0065] (10) The content of water in the photosensitive composition is 0.010 mass % to 3.0 mass %.

[0066]

[12] The photosensitive composition according to any one of [1] to

[11] , further satisfying the following condition (1α).

[0067] (1α) The content of fluorine element in the total solid content of the photosensitive composition is 1,000 ppm by mass or less.

[0068]

[13] The photosensitive composition according to any one of [1] to

[12] , further satisfying at least one of the following conditions (δ), (ε), and (ζ).

[0069] (δ) The (B) radical polymerizable compound contains the following (B1) first polymerizable compound and (B2) second polymerizable compound

[0070] (ε) The (B) radical polymerizable compound contains the following (B3) third polymerizable compound and (B4) fourth polymerizable compound

[0071] (ζ) The (B) radical polymerizable compound contains the following (B1) first polymerizable compound or (B2) second polymerizable compound, and further contains the following (B3) third polymerizable compound or (B4) fourth polymerizable compound

[0072] (B1) First polymerizable compound: a compound having the following structure (I-b1) and having at least two free radical polymerizable groups

[0073] (I-b1) Structure: Structure containing an alicyclic structure and / or structure containing a heteroalicyclic structure

[0074] (B2) Second polymerizable compound: a compound having the following structures (I-b2) and (II-b2) and having at least two free radical polymerizable groups

[0075] (I-b2) Structure: Structure containing an aromatic structure

[0076] (II-b2) Structure: Structure containing aliphatic structure

[0077] (B3) Third polymerizable compound: a compound having at least two (meth)acryloyl groups and further having the following structure (I-b3)

[0078] (I-b3) Structure: A structure containing an aliphatic structure in which at least two (meth)acryloyl groups are linked with a minimum number of 4 to 10 atoms.

[0079] (B4) Fourth polymerizable compound: a compound having at least two (meth)acryloyl groups and further having the following structure (I-b4):

[0080] (I-b4) Structure: a structure in which at least two (meth)acryloyl groups are linked with each other by a minimum number of atoms of 11 to 45 and which contains an aliphatic structure.

[0081]

[14] The photosensitive composition according to any one of [1] to

[13] , further comprising (G) inorganic particles.

[0082] The (G) inorganic particles include one or more selected from the group consisting of silicon dioxide particles, aluminum oxide particles, titanium oxide particles, vanadium oxide particles, chromium oxide particles, iron oxide particles, cobalt oxide particles, copper oxide particles, zinc oxide particles, zirconium oxide particles, niobium oxide particles, tin oxide particles, and cerium oxide particles.

[0083]

[15] A photosensitive composition comprising (A) a binder resin and (C) a photosensitizer, and further comprising (B) a radical polymerizable compound and / or (F) a crosslinking agent, wherein:

[0084] The (A) binder resin contains the following (A1) resin and / or (A2) resin,

[0085] Satisfies one or more selected from the group consisting of the following conditions (α), (β), and (γ).

[0086] (A1) Resin: A resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin

[0087] (A2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin

[0088] (α) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (1x)

[0089] (1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the total solid content of the photosensitive composition is 0.010 mass ppm to 1,000 mass ppm

[0090] (β) further contains one or more selected from the group consisting of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (2x):

[0091] (2x) the total content of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is 0.010 mass ppm to 1,000 mass ppm

[0092] (γ) further contains one or more selected from the group consisting of benzene, toluene, xylene, and naphthalene, and satisfies the following condition (3)

[0093] (3) The total content of benzene, toluene, xylene, and naphthalene in the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0094]

[16] A photosensitive composition film comprising a photosensitive composition coating film obtained by forming the photosensitive composition according to any one of [1] to

[15] above into a film, and a support.

[0095]

[17] A cured product obtained by curing the photosensitive composition according to any one of [1] to

[15] .

[0096]

[18] An electronic component comprising the hardened material according to

[17] .

[0097]

[19] A method for producing a cured product, comprising: (1) forming a coating film of the photosensitive composition according to any one of [1] to

[15] above on a substrate;

[0098] (2) a step of irradiating the coating film of the photosensitive composition with active chemical rays through a photomask;

[0099] (3) a step of developing the photosensitive composition using a developer to form a pattern; and

[0100] (4) A step of heating the pattern to obtain a cured pattern of the photosensitive composition.

[0101]

[20] An electronic component comprising a hardened material, wherein:

[0102] The cured product contains the following (XA1) resin and / or (XA2) resin,

[0103] The following condition (Xα) is satisfied.

[0104] (XA1) Resin: a resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin

[0105] (XA2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin

[0106] (Xα) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (X1x):

[0107] (X1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the cured product is 0.010 to 1,000 ppm by mass.

[0108] Effects of the Invention

[0109] The photosensitive composition of the present invention can suppress the residue after development, and can provide a cured product having excellent mechanical properties even when heated at low temperatures by increasing the crosslinking degree of the resin or promoting the ring closure reaction. In addition, a cured product included in an electronic component having excellent migration resistance can be provided. In addition, the electronic component of the present invention can provide an electronic component having excellent migration resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0110] [ Figure 1 ] is a schematic cross-sectional view showing an enlarged cross-section of a pad portion of a semiconductor device having a bump. DETAILED DESCRIPTION

[0111] Hereinafter, a photosensitive composition as the first mode of the present invention and a photosensitive composition as the second mode of the present invention are described. In addition, in the case of recording as the photosensitive composition of the present invention, the description of the photosensitive composition as the first mode and the second mode of the present invention is involved. On the other hand, in the case of describing a photosensitive composition of a specific mode, it is recorded as a photosensitive composition as the first mode of the present invention, etc. Among them, the present invention is not limited to the following embodiments, and various changes can be made within the scope that can achieve the purpose of the invention and does not deviate from the main purpose of the invention. In addition, the so-called main chain of the resin refers to the chain with the longest chain length in the chain constituting the resin containing the structural unit. The so-called side chain of the resin refers to a chain that branches from the main chain or is bonded to the main chain in the chain constituting the resin containing the structural unit and has a shorter chain length than the main chain. The so-called end of the resin refers to a structure that seals the main chain, such as a structure derived from a capping agent, etc. In addition, the hydrocarbon group or alkylene group containing a "*** bond" or a "*** group" refers to a hydrocarbon group or alkylene group bonded by a "*** bond" or a "*** group", or at least two hydrocarbon groups or at least two alkylene groups linked by a "*** bond" or a "*** group".

[0112] <Photosensitive composition>

[0113] The photosensitive composition of the first embodiment of the present invention has the structure of [1]. The photosensitive composition of the second embodiment of the present invention has the structure of

[15] . Hereinafter, sulfonic acid, phosphate, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, hypophosphite, and carboxylic acid containing fluorine element may be collectively referred to as "specific organic acid". Hereinafter, chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion may be collectively referred to as "specific anion". Hereinafter, benzene, toluene, xylene, and naphthalene may be collectively referred to as "specific aromatic compound".

[0114] By making the structure, the photosensitive composition of the present invention can suppress the residue after development, and by increasing the crosslinking degree of the resin or promoting the closed-loop reaction, a hardened material having excellent mechanical properties even when heated at low temperatures can be provided. In addition, a hardened material included in an electronic component having excellent migration resistance can be provided. It is inferred that when a pattern of the photosensitive composition is formed on wiring by containing a trace amount of the specific aromatic compound, specific anion, or specific organic acid in the photosensitive composition, the wiring surface equivalent to the opening is surface-modified by these specific aromatic compounds, specific anions, or specific organic acids. Therefore, it is believed that by preventing the residue from adhering to the wiring surface, the effect of suppressing the residue after development is exerted.

[0115] In addition, by the specific aromatic compound and polyimide, polybenzoxazole and these precursors etc., there is the π electron interaction of the resin of aromatic ring or the coordination bond formed by the π electron of the resin of the silicon atom of the 3d orbital as the empty atomic orbital with polysiloxane etc., it is inferred that these resins are in the state of local orientation.As a result, since the cross-linking reaction between resins or the ring-closure reaction of resin are carried out efficiently, it is believed that excellent mechanical properties are also exerted when heating at low temperature.On the other hand, the specific anion or specific organic acid is used as the catalyst for promoting the cross-linking reaction on the aromatic ring in the resin of aromatic ring such as polyimide, polybenzoxazole and these precursors etc. or the ring-closure reaction of resin, polysiloxane etc. with the cross-linking reaction in the resin of silanol group.As a result, since cross-linking reaction or ring-closure reaction are carried out efficiently, it is believed that excellent mechanical properties are also exerted when heating at low temperature.

[0116] In addition, it is believed that by intentionally containing a trace of these specific aromatic compounds, specific anions, or specific organic acids, the polarization structure or charge balance in the cured product of the photosensitive composition can be controlled. In addition, it is believed that the aromatic rings in the resins such as polyimide, polybenzoxazole, and these precursors, or the silanol groups in the resins such as polysiloxane also contribute to the control of polarization structure or charge balance. Thus, it is inferred that the ion migration or electromigration caused by the metal impurities or ionic impurities that have a negative impact on electrical insulation is suppressed, and the effect of excellent migration resistance is brought into play. In addition, it is inferred that by suppressing the migration of the metal in the wiring or suppressing the cohesion, the effect of high reliability in the electronic parts, semiconductor devices, display devices, and metal-clad laminates is brought into play.

[0117] <(A) Binder resin>

[0118] The photosensitive composition of the present invention contains (A) a binder resin. The (A) binder resin is a heat-resistant resin that at least a portion of which remains in a cured product formed by curing the composition. The (A) binder resin is preferably a resin that is cured by forming a cross-linked structure through a reaction. The reaction is not particularly limited to a reaction performed by heating, a reaction performed by irradiation with energy rays, etc., and a cross-linked structure may also be formed by a cross-linking agent (F) described later. The (A) binder resin is preferably a thermosetting resin.

[0119] (A) The binder resin is preferably an alkali-soluble resin or an organic solvent-soluble resin. The so-called alkali-soluble resin refers to a resin having an acidic group and having solubility in an alkali developer. The so-called organic solvent-soluble resin refers to a resin having an organic solvent-soluble structure and having solubility in a developer as an organic solvent. The alkali-soluble resin and the organic solvent-soluble resin in the photosensitive composition of the present invention are preferably resins having the following solubility, that is, by using the (C) photosensitive agent described later, the composition is given positive or negative photosensitivity, and a positive or negative pattern can be formed by developing using an alkali developer or an organic solvent. (A) The binder resin is more preferably a resin having an acidic group in the structural unit of the resin. The acidic group possessed by the (A) binder resin is preferably a phenolic hydroxyl group, a hydroxyimide group, a hydroxyamide group, a silanol group, a 1,1-bis(trifluoromethyl)hydroxymethyl group, a mercapto group, a carboxyl group, a carboxylic anhydride group, or a sulfonic acid group. In addition, when the (A) binder resin satisfies the conditions of (P1a) and / or (P2a) described below, or when the photosensitive composition of the present invention satisfies the condition of (1α) described below, the acidic group possessed by the (A) binder resin is preferably a phenolic hydroxyl group, a hydroxyimide group, a hydroxyamide group, a silanol group, a mercapto group, a carboxyl group, a carboxylic anhydride group, or a sulfonic acid group.

[0120] (A) The binder resin preferably has a radical polymerizable group, and more preferably has a radical polymerizable group in the structural unit of the resin. The radical polymerizable group preferably has an ethylenically unsaturated double bond group, and more preferably is a photoreactive group, an alkenyl group having 2 to 5 carbon atoms, or an alkynyl group having 2 to 5 carbon atoms. The photoreactive group is preferably a styryl group, a cinnamoyl group, a maleimide group, a nadicimide group, or a (meth)acryloyl group, and is more preferably a (meth)acryloyl group from the viewpoint of improving the sensitivity during exposure and promoting the radical polymerization during heating at a low temperature. On the other hand, the alkenyl group having 2 to 5 carbon atoms or the alkynyl group having 2 to 5 carbon atoms is preferably a vinyl group, an allyl group, a 2-methyl-2-propenyl group, a crotonyl group, a 2-methyl-2-butenyl group, a 3-methyl-2-butenyl group, a 2,3-dimethyl-2-butenyl group, an ethynyl group, or a 2-propargyl group, and is more preferably a vinyl group or an allyl group from the viewpoint of improving the sensitivity during exposure and promoting the radical polymerization during heating at a low temperature.

[0121] <(A1) resin, (A2) resin, and (A3) resin>

[0122] In the photosensitive composition of the present invention, the binder resin (A) contains the following resin (A1) and / or resin (A2). In the photosensitive composition of the present invention, the binder resin (A) preferably further contains the following resin (A3).

[0123] (A1) Resin: A resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin

[0124] (A2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin

[0125] (A3) Resin: a resin having a radical polymerizable group.

[0126] The resin (A1) is a resin including polyimide, polybenzoxazole, precursors thereof, and copolymers containing two or more of these, wherein the structural unit of the main chain of the resin contains one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure. The resin (A3) is a resin having a free radical polymerizable group such as a (meth)acryloyl group in at least one of the main chain of the resin, the side chain of the resin, and the terminal of the resin. Examples and preferred descriptions of the free radical polymerizable group are as described in the (A) binder resin.

[0127] In addition, with respect to (A1) resin, (A2) resin, and (A3) resin, in the case where each of these has a structure or group constituting other resins, it is set to be classified as any one according to the following rules. In the case where a certain resin can be equivalent to two or more of (A1) resin, (A2) resin, and (A3) resin, it is determined as follows which resin is equivalent to. That is, in the case where the structural unit of the main chain of the resin contains one or more resins selected from the group consisting of imide structure, amide structure, oxazole structure, and siloxane structure (hereinafter, "imide structure, etc.") and has a phenolic hydroxyl group in the structural unit of the main chain of the resin, the resin is equivalent to (A1) resin. In addition, in the case where the resin having a structural unit containing an imide structure, etc. has a free radical polymerizable group, the resin is equivalent to (A1) resin. In addition, in the case where the resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin has a free radical polymerizable group, the resin is equivalent to (A2) resin. When the resin having a structural unit including an imide structure or the like has a phenolic hydroxyl group and a radical polymerizable group in the structural unit of the main chain of the resin, the resin corresponds to the (A1) resin.

[0128] From the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the photosensitive composition of the present invention preferably contains (A1) resin, and from the viewpoint of suppressing residue after development and improving mechanical properties when heated at low temperatures, the photosensitive composition of the present invention more preferably contains (A1) resin and (A2) resin. In addition, from the viewpoint of improving sensitivity during exposure and improving mechanical properties when heated at low temperatures, the photosensitive composition of the present invention preferably contains (A1) resin and / or (A2) resin, and also contains (A3) resin. In addition, from these viewpoints, the photosensitive composition of the present invention further preferably contains (A1) resin, (A2) resin, and (A3) resin.

[0129] <(A1) Resin>

[0130] From the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the resin (A1) preferably contains one or more selected from the group consisting of the following resins (A1-1), (A1-2), (A1-3), (A1-4), (A1-5), (A1-6), (A1-7), (A1-8), maleimide resins, maleimide-styrene resins, maleimide-triazine resins, maleimide-oxazine resins, and copolymers containing two or more of these, and more preferably contains one or more selected from the group consisting of the following resins (A1-1), (A1-2), (A1-3), (A1-4), (A1-5), (A1-6), (A1-7), (A1-8), maleimide resins, maleimide-styrene resins, maleimide-triazine resins, maleimide-oxazine resins, and copolymers containing two or more of these. The present invention further preferably contains one or more selected from the group consisting of (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, (A1-5) resin, (A1-6) resin, (A1-7) resin, (A1-8) resin, and copolymers containing two or more of these resins, and more preferably contains one or more selected from the group consisting of (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, (A1-5) resin, (A1-6) resin, (A1-7) resin, and copolymers containing two or more of these resins (hereinafter referred to as "polyimide-based resins"). The (A1) resin may be a single resin or any of these copolymers.

[0131] (A1-1) Resin: Polyimide

[0132] (A1-2) Resin: Polyimide precursor

[0133] (A1-3) Resin: polybenzoxazole

[0134] (A1-4) Resin: polybenzoxazole precursor

[0135] (A1-5) Resin: Polyamide-imide

[0136] (A1-6) Resin: polyamide-imide precursor

[0137] (A1-7) Resin: Polyamide

[0138] (A1-8) Resin: polysiloxane.

[0139] The resin (A1) has an imide structure, an amide structure, an oxazole structure, or a siloxane structure in the structural unit of the main chain of the resin, thereby obtaining an effect of improving mechanical properties. In addition, since these structures capture metal impurities or ionic impurities that have an adverse effect on electrical insulation, it is estimated that ion migration or electromigration can be suppressed and migration resistance can be improved.

[0140] (A) The binder resin preferably comprises (A1) a resin,

[0141] From the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the (A1) resin preferably contains one or more selected from the group consisting of the (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, (A1-5) resin, (A1-6) resin, and copolymers containing two or more of these, and more preferably contains one or more selected from the group consisting of the (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, and copolymers containing two or more of these. In addition, from the viewpoint of improving mechanical properties when heated at low temperatures, the (A1) resin is further preferably a resin containing (A1-1) resin, (A1-3) resin, and copolymers containing two or more of these. On the other hand, from the viewpoint of improving sensitivity during exposure, the (A1) resin is further preferably a resin containing (A1-2) resin, (A1-4) resin, and copolymers containing two or more of these.

[0142] (A) The binder resin preferably comprises (A1) a resin,

[0143] The (A1) resin preferably has a radical polymerizable group from the viewpoint of improving sensitivity during exposure and improving mechanical properties during heating at low temperatures. Examples and preferred descriptions of the radical polymerizable group are the same as those described in the (A) binder resin.

[0144] From the viewpoint of improving sensitivity during exposure and improving mechanical properties during heating at low temperatures, the resin (A1-1), the resin (A1-2), the resin (A1-3), the resin (A1-4), the resin (A1-5), the resin (A1-6), and copolymers containing two or more of these preferably have a free radical polymerizable group. Examples and preferred descriptions of the free radical polymerizable group are as described in the (A) binder resin.

[0145] The radical polymerizable group is preferably one or more selected from the group consisting of General Formula (51), General Formula (52), General Formula (53), General Formula (54) and General Formula (55).

[0146] [Chemistry 2]

[0147]

[0148] In the general formulas (51) to (55), X 21 ~X 24 Each of X independently represents an alkylene group having 1 to 10 carbon atoms, a cycloalkylene group having 4 to 10 carbon atoms, or an arylene group having 6 to 15 carbon atoms. 25 It represents a divalent to hexavalent organic group. 26 Represents a direct bond or a divalent to hexavalent organic group. 181 ~R 202 Each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 15 carbon atoms. a, b, c, d, and e each independently represent 0 or 1. f and g each independently represent an integer of 1 to 5.

[0149] In the general formulas (51) to (55), X 25 It is preferably a divalent to hexavalent aliphatic group, and more preferably a divalent to hexavalent alkylene group having 1 to 10 carbon atoms. 26 It is preferably a direct bond or a divalent to hexavalent aliphatic group, and more preferably a divalent to hexavalent alkylene group having 1 to 10 carbon atoms. The alkyl group, aryl group, alkylene group, cycloalkylene group, and arylene group may have a heteroatom and may be unsubstituted or substituted.

[0150] The free radical polymerizable group is preferably a free radical polymerizable group obtained by reacting a part of the phenolic hydroxyl group and / or carboxyl group of the resin with a compound having a free radical polymerizable group. As the compound having a free radical polymerizable group, for example, isocyanate compounds, epoxy compounds, aldehyde compounds, ketone compounds, acetate compounds, carboxylic acid compounds, carboxylic acid derivatives, halogenated alkyl compounds, azidated alkyl compounds, sulfonate alkyl compounds, cyanated alkyl compounds, or alcohol compounds can be cited. These compounds also preferably have urea bonds or urethane bonds.

[0151] Examples of the alcohol compound having a radical polymerizable group include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 4-hydroxyhexyl (meth)acrylate, glycerol di(meth)acrylate, trimethylolpropane di(meth)acrylate, di-trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, and tripentaerythritol penta(meth)acrylate.

[0152] (A) The binder resin preferably comprises (A1) a resin,

[0153] From the viewpoints of improving sensitivity during exposure, suppressing residue after development, improving mechanical properties during heating at low temperatures, and improving migration resistance, the (A1) resin preferably contains a (A1) resin having no radical polymerizable group and a (A1) resin having a radical polymerizable group.

[0154] It is believed that by forming such a structure, the (A1) resin without a radical polymerizable group can exert the ability to suppress residue after development and capture metal impurities or ionic impurities, etc. due to the acidic group or organic solvent-soluble structure, while the (A1) resin with a radical polymerizable group can improve the sensitivity during exposure and promote radical polymerization during heating at low temperature, etc. It is estimated that the effects of improving multiple characteristics become significant through the functional separation in such (A1) resin.

[0155] From the viewpoint of improving the sensitivity during exposure, the acid equivalent of the resin (A1) is preferably 200 g / mol or more, more preferably 250 g / mol or more, and further preferably 300 g / mol or more. On the other hand, from the viewpoint of suppressing the residue after development, the acid equivalent of the resin (A1) is preferably 600 g / mol or less, more preferably 500 g / mol or less, and further preferably 450 g / mol or less. The exposure referred to herein is the irradiation with active chemical rays (radiation), for example, irradiation with visible light, ultraviolet rays, electron beams, or X-rays. Hereinafter, the exposure refers to the irradiation with active chemical rays (radiation).

[0156] From the viewpoint of suppressing the residue after development, the double bond equivalent of the resin (A1) is preferably 200 g / mol or more, more preferably 400 g / mol or more, further preferably 500 g / mol or more, further more preferably 700 g / mol or more, and particularly preferably 1,000 g / mol or more. On the other hand, from the viewpoint of improving the sensitivity during exposure, the double bond equivalent of the resin (A1) is preferably 3,000 g / mol or less, more preferably 2,000 g / mol or less, and further preferably 1,500 g / mol or less.

[0157] <(A1) Resin; Polyimide-based resin>

[0158] Examples of polyimide precursors include polyamic acid, polyamic acid ester, polyamic acid amide, or polyisoimide. Examples of polyimide include resins obtained by dehydrating and ring-closing polyimide precursors by heating or using a catalyst. Polyimide preferably has a structural unit represented by general formula (1). Polyimide precursor preferably has a structural unit represented by general formula (2).

[0159] [Chemistry 3]

[0160]

[0161] In the general formula (1) and the general formula (2), R 1 and R 5 R each independently represents a tetravalent to decavalent organic group. 2 and R 6 R each independently represents a divalent to decavalent organic group. 3 , R 4 , and R 9 R each independently represents a phenolic hydroxyl group, a sulfonic acid group, a mercapto group, or a substituent represented by the general formula (7) or (8). 7 represents a substituent represented by the general formula (7) or (8). 8 represents a phenolic hydroxyl group, a sulfonic acid group, or a mercapto group. p represents an integer of 0 to 6. q represents an integer of 0 to 8. t represents an integer of 2 to 8, u represents an integer of 0 to 6, and 2≤t+u≤8. v represents an integer of 0 to 8. 3 or R 4 In the case of a phenolic hydroxyl group, R 1 or R 2 Its structure contains an aromatic structure. 8 or R 9 In the case of a phenolic hydroxyl group, R 5 or R 6 It contains aromatic structures in its structure.

[0162] In the general formula (1) and the general formula (2), R 1 , R 5 , R 2 , and R 6 Preferably, each independently has an aliphatic structure having 2 to 20 carbon atoms, an alicyclic structure having 4 to 20 carbon atoms, or an aromatic structure having 6 to 30 carbon atoms. q is preferably an integer of 1 to 8. v is preferably an integer of 1 to 8. R 1 and R 5 Each independently represents a carboxylic acid residue. 2 and R 6 Each independently represents an amine residue. The aliphatic structure, alicyclic structure, and aromatic structure may have a heteroatom, and may be an unsubstituted or substituted structure.

[0163] [Chemistry 4]

[0164]

[0165] In the general formula (7) and the general formula (8), R 28 ~R30 Each independently represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, an acyl group having 2 to 6 carbon atoms, or an aryl group having 6 to 15 carbon atoms. 28 ~R 30 Preferably, each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an acyl group having 2 to 4 carbon atoms, or an aryl group having 6 to 10 carbon atoms. The alkyl group, acyl group, and aryl group may have a heteroatom, and may be unsubstituted or substituted.

[0166] As a polyimide precursor, R in the structural unit represented by the general formula (2) 7 In the case of a substituent represented by the general formula (7), R 28 The structural unit in which R is a hydrogen atom is called an amic acid structural unit. 7 In the case of a substituent represented by the general formula (7), R 28 A structural unit that is an alkyl group having 1 to 10 carbon atoms, an acyl group having 2 to 6 carbon atoms, or an aryl group having 6 to 15 carbon atoms is referred to as an amic acid ester structural unit. 7 The structural unit when it is a substituent represented by the general formula (8) is called an amic acid amide structural unit. From the viewpoint of improving the mechanical properties when heated at low temperatures, the polyimide precursor preferably has an amic acid ester structural unit and / or an amic acid amide structural unit. In addition, the polyimide precursor may also have an amic acid structural unit, an amic acid ester structural unit, or an imide ring-closing structural unit after a part of the amic acid amide structural unit is imide ring-closed.

[0167] As a polybenzoxazole precursor, for example, polyhydroxyamide can be cited. As a polybenzoxazole, for example, a resin obtained by dehydrating and ring-closing a polybenzoxazole precursor by heating or using a catalyst can be cited. The polybenzoxazole preferably has a structural unit represented by the general formula (3). The polybenzoxazole precursor preferably has a structural unit represented by the general formula (4).

[0168] [Chemistry 5]

[0169]

[0170] In the general formula (3) and the general formula (4), R 10 and R 14 R each independently represents a divalent to decavalent organic group. 11 and R 15 R each independently represents a tetravalent to decavalent organic group having an aromatic structure. 12 , R 13 , and R 16R each independently represents a phenolic hydroxyl group, a sulfonic acid group, a mercapto group, or a substituent represented by the general formula (7) or (8). 17 Represents a phenolic hydroxyl group. 18 represents a sulfonic acid group, a mercapto group, or a substituent represented by the general formula (7) or the general formula (8). r represents an integer of 0 to 8. s represents an integer of 0 to 6. w represents an integer of 0 to 8. x represents an integer of 2 to 8, and y represents an integer of 0 to 6, 2≤x+y≤8. 12 or R 13 In the case of a phenolic hydroxyl group, R 10 or R 11 Its structure contains an aromatic structure. 16 In the case of a phenolic hydroxyl group, R 14 Its structure contains an aromatic structure. 17 Bonded R 15 It contains aromatic structures in its structure.

[0171] In the general formula (3) and the general formula (4), R 10 , R 14 , R 11 , and R 15 Preferably, each independently has an aliphatic structure having 2 to 20 carbon atoms, an alicyclic structure having 4 to 20 carbon atoms, or an aromatic structure having 6 to 30 carbon atoms. s is preferably an integer of 1 to 6. 10 and R 14 Each independently represents a carboxylic acid residue. 11 and R 15 Each independently represents an amine residue. The aliphatic structure, alicyclic structure, and aromatic structure may have a heteroatom, and may be an unsubstituted or substituted structure.

[0172] As the polyamideimide precursor, for example, a resin obtained by reacting tricarboxylic anhydride or the like with a diamine or the like can be cited. As the polyamideimide, for example, a resin obtained by dehydrating and ring-closing a polyamideimide precursor by heating or a reaction using a catalyst can be cited. The polyamideimide preferably has a structural unit represented by the general formula (5). The polyamideimide precursor preferably has a structural unit represented by the general formula (6).

[0173] [Chemistry 6]

[0174]

[0175] In the general formula (5) and the general formula (6), R 19 and R 23 R each independently represents a trivalent to decavalent organic group. 20 and R24 R each independently represents a divalent to decavalent organic group. 21 , R 22 , and R 27 R each independently represents a phenolic hydroxyl group, a sulfonic acid group, a mercapto group, or a substituent represented by the general formula (7) or (8). 25 represents a substituent represented by the general formula (7) or (8). 26 represents a phenolic hydroxyl group, a sulfonic acid group, or a mercapto group. m represents an integer of 0 to 7. n represents an integer of 0 to 8. a represents an integer of 0 to 7. b represents an integer of 0 to 8. 21 or R 22 In the case of a phenolic hydroxyl group, R 19 or R 20 Its structure contains an aromatic structure. 26 or R 27 In the case of a phenolic hydroxyl group, R 23 or R 24 It contains aromatic structures in its structure.

[0176] In the general formula (5) and the general formula (6), R 19 , R 23 , R 20 , and R 24 Preferably, each independently has an aliphatic structure having 2 to 20 carbon atoms, an alicyclic structure having 4 to 20 carbon atoms, or an aromatic structure having 6 to 30 carbon atoms. n is preferably an integer of 1 to 8. b is preferably an integer of 1 to 8. R 19 and R 23 Each independently represents a carboxylic acid residue. 20 and R 24 Each independently represents an amine residue. The aliphatic structure, alicyclic structure, and aromatic structure may have a heteroatom, and may be an unsubstituted or substituted structure.

[0177] Examples of polyamides include resins obtained by reacting dicarboxylic acids or corresponding dicarboxylic acid active diesters with diamines or diisocyanate compounds. In addition, the polyimide, polyimide precursor, polybenzoxazole, polybenzoxazole precursor, polyamideimide, and polyamideimide precursor may be copolymers with polyamides.

[0178] From the viewpoint of improving the sensitivity during exposure, the polyimide resin preferably contains a carboxylic acid residue having a fluorine atom and / or an amine residue having a fluorine atom. The total content ratio of the carboxylic acid residue having a fluorine atom and the amine residue having a fluorine atom in all the carboxylic acid residues and all the amine residues of each resin is preferably 10 mol% to 100 mol%, more preferably 30 mol% to 100 mol%, and further preferably 50 mol% to 100 mol%. The total content ratio of the amine residue having a fluorine atom in all the amine residues of each resin is preferably 10 mol% to 100 mol%, more preferably 30 mol% to 100 mol%, and further preferably 50 mol% to 100 mol%. The total content ratio of the carboxylic acid residue having a fluorine atom in all the carboxylic acid residues of each resin is preferably 10 mol% to 100 mol%, more preferably 30 mol% to 100 mol%, and further preferably 50 mol% to 100 mol%.

[0179] From the viewpoint of improving storage stability, the polyimide resin preferably has a structure sealed by a monoamine, a dicarboxylic anhydride, or a monocarboxylic acid derivative at the end of the resin. From the viewpoint of improving sensitivity during exposure and improving mechanical properties during heating at low temperatures, the polyimide resin preferably has a crosslinking group or a free radical polymerizable group capable of reacting with a resin or the like at the end of the resin, more preferably a maleimide group or a nadic imide group. The maleimide group and the nadic imide group at the end of the resin are preferably amine residues and / or carboxylic acid residues. As such acid monomers, for example, maleic anhydride or nadic anhydride can be cited.

[0180] <(A) Content of fluorine element in the structure of binder resin>

[0181] From the viewpoint of suppressing the residue after development and improving the migration resistance, the binder resin (A) preferably satisfies the following condition (P1a). The binder resin (A) more preferably further satisfies the following condition (P2a). From the viewpoint of suppressing the residue after development and improving the migration resistance, the binder resin (A) is a polyimide-based resin, and similarly, preferably satisfies the following condition (P1a), and more preferably further satisfies the following condition (P2a).

[0182] (P1a) The content of fluorine element in the structure of the binder resin (A) is 10,000 ppm by mass or less

[0183] (P2a) The content of fluoride ions in the structure of the binder resin (A) is 10,000 ppm by mass or less.

[0184] From the viewpoint of the effect of the invention, the content of fluorine element in the structure of (A) binder resin is preferably 0 mass ppm or more, more preferably 0.010 mass ppm or more, further preferably 0.030 mass ppm or more, further preferably 0.050 mass ppm or more, particularly preferably 0.070 mass ppm or more, and most preferably 0.10 mass ppm or more. On the other hand, from the viewpoint of the effect of the invention, the content of fluorine element is preferably 10,000 mass ppm or less, more preferably 5,000 mass ppm or less, further preferably 1,000 mass ppm or less, further preferably 500 mass ppm or less, particularly preferably 300 mass ppm or less, and most preferably 100 mass ppm or less. Furthermore, the content of fluorine element is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5 mass ppm or less, particularly preferably 3 mass ppm or less, and most preferably 1 mass ppm or less.

[0185] The preferred range of the content of the fluoride ion in the structure of the binder resin (A) is also the same as the preferred range of the content of the fluorine element in the structure of the binder resin (A) described above.

[0186] The content of fluorine element in the structure of the binder resin (A) may be 0 mass ppm. The content of fluoride ion in the structure of the binder resin (A) may be 0 mass ppm.

[0187] By containing the (A) binder resin whose content of fluorine element is below a specific value in the photosensitive composition, the content of fluorine element or fluoride ion in these resins or anion containing fluorine element derived from these resins is below a specific value, so it is inferred that the protons in the photosensitive composition are locally activated by the interaction of hydrogen bonds of each component in the photosensitive composition. Therefore, it is believed that the effect of suppressing the residue after development becomes significant by promoting the dissolution relative to the developer. In addition, it is believed that by intentionally setting the content of the component in the resin to below a specific value, the content of the component in the hardened material of the photosensitive composition can also be reduced, and the polarization structure or charge balance in the hardened material can be controlled. As a result, it is inferred that the migration resistance is improved by suppressing the ion migration or electromigration caused by metal impurities or ionic impurities that have an adverse effect on electrical insulation.

[0188] <(A1) Resin; other resins>

[0189] Examples of polysiloxanes include resins obtained by hydrolyzing and dehydrating one or more selected from the group consisting of trifunctional organosilanes, tetrafunctional organosilanes, difunctional organosilanes, and monofunctional organosilanes. The polysiloxane preferably has a trifunctional organosilane unit represented by the general formula (9) and / or a tetrafunctional organosilane unit represented by the general formula (10).

[0190] [Chemistry 7]

[0191]

[0192] In the general formula (9) and the general formula (10), R 41 Represents a hydrogen atom or a monovalent organic group. * 1 ~* 3 R represents the bonding point in the resin independently. 41 Preferred are hydrogen atoms, alkyl groups having 1 to 10 carbon atoms, cycloalkyl groups having 4 to 10 carbon atoms, aryl groups having 6 to 15 carbon atoms, halogenated alkyl groups having 1 to 10 carbon atoms, halogenated cycloalkyl groups having 4 to 10 carbon atoms, or halogenated aryl groups having 6 to 15 carbon atoms. The alkyl groups, cycloalkyl groups, aryl groups, halogenated alkyl groups, halogenated cycloalkyl groups, and halogenated aryl groups may have heteroatoms and may be unsubstituted or substituted.

[0193] The maleimide resin is a resin having at least two maleimide groups in at least one of the main chain of the resin, the side chain of the resin, and the terminal of the resin. In addition, the maleimide resin is a resin different from a polyimide-based resin.

[0194] Examples of maleimide-styrene resins include resins obtained by free radical copolymerization of the maleimide resin and a styrene derivative, and resins obtained by free radical copolymerization of a maleimide compound and a styrene derivative with other copolymerization components such as a (meth)acrylic acid derivative.

[0195] As the maleimide-triazine resin, for example, a resin obtained by reacting the maleimide resin with a compound having a triazine structure and / or an aromatic cyanate compound can be cited. In addition, a resin obtained by reacting a maleimide compound with a compound having a triazine structure and / or an aromatic cyanate compound can also be cited.

[0196] Examples of the maleimide-oxazine resin include resins obtained by reacting the maleimide resin with a compound having a benzoxazine structure, and resins obtained by reacting a maleimide compound with a compound having a benzoxazine structure.

[0197] <(A2) Resin>

[0198] (A) The binder resin preferably contains (A2) a resin,

[0199] The resin (A2) preferably contains one or more selected from the group consisting of phenol resins, polyhydroxystyrene, phenol group-containing epoxy resins, and phenol group-containing acrylic resins. The resin (A2) may be a single resin or a copolymer thereof.

[0200] Examples of the phenol resin include resins obtained by reacting a phenol compound or the like with one or more selected from the group consisting of an aldehyde compound, a ketone compound, an alkoxymethyl compound, and a hydroxymethyl compound. The phenol resin is preferably a novolac resin, a resol resin, or a phenol aralkyl resin.

[0201] The phenol resin preferably contains one or more structural units selected from the group consisting of general formula (31), general formula (32), general formula (33), general formula (34), general formula (35), general formula (38), general formula (39) and general formula (40).

[0202] [Chemistry 8]

[0203]

[0204] In the general formulas (31) to (35), X 31 ~X 37 Each independently represents an aliphatic structure having 1 to 2 carbon atoms. 33 represents an alkylene group having 1 to 10 carbon atoms. 35 R represents a direct bond, an alkylene group having 1 to 6 carbon atoms, an alkylene group having 1 to 6 carbon atoms, a halogenated alkylene group having 1 to 6 carbon atoms, a halogenated alkylene group having 1 to 6 carbon atoms, an aromatic group, a condensed polycyclic structure, a condensed polycyclic heterocyclic structure, a structure in which an aromatic ring skeleton and an alicyclic skeleton are directly linked, or a structure in which at least two aromatic ring skeletons are directly linked. 71 ~R 82 Each independently represents a halogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkenyloxy group having 2 to 10 carbon atoms, an acyl group having 1 to 10 carbon atoms, a carboxyl group, an amino group, or a ring-forming group. The ring connected by the ring-forming group represents a monocyclic or condensed polycyclic hydrocarbon ring. 83 ~R 88Each independently represents an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, or a hydroxyl group. a represents an integer of 1 to 4. b represents an integer of 1 to 5. m represents an integer of 0 to 3. n represents an integer of 0 to 4. c represents an integer of 1 to 4. o and p each independently represent an integer of 0 to 3. q represents an integer of 0 to 4. d represents an integer of 1 to 4. r and s each independently represent an integer of 0 to 3. t represents an integer of 0 to 4. e represents an integer of 1 to 4. f, g, v, and w each independently represent an integer of 0 to 4. u represents an integer of 0 to 3. h represents an integer of 1 to 3. x represents an integer of 0 to 2. y and z each independently represent 0 or 1. α, β, γ, δ, ε, and ζ each independently represent an integer of 0 to 4. * 1 and* 2 Each independently represents a bonding point in the resin.

[0205] [Chemistry 9]

[0206]

[0207] In the general formulas (38) to (40), Z 31 ~Z 34 W each independently represents an aliphatic structure having 1 to 2 carbon atoms. 32 W represents an aromatic group, a condensed polycyclic structure, a condensed polycyclic heterocyclic structure, a structure in which an aromatic ring skeleton and an alicyclic skeleton are directly linked, or a structure in which at least two aromatic ring skeletons are directly linked. 34 R represents a direct bond, an alkylene group having 1 to 6 carbon atoms, an alkylene group having 1 to 6 carbon atoms, a halogenated alkylene group having 1 to 6 carbon atoms, a halogenated alkylene group having 1 to 6 carbon atoms, an aromatic group, a condensed polycyclic structure, a condensed polycyclic heterocyclic structure, a structure in which an aromatic ring skeleton and an alicyclic skeleton are directly linked, or a structure in which at least two aromatic ring skeletons are directly linked. 91 ~R 96 Each independently represents a halogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkenyloxy group having 2 to 10 carbon atoms, an acyl group having 1 to 10 carbon atoms, a carboxyl group, an amino group, or a ring-forming group. The ring connected by the ring-forming group represents a monocyclic or condensed polycyclic hydrocarbon ring. 97 ~R 99 Each independently represents an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, or a hydroxyl group. a represents an integer of 1 to 4. m represents an integer of 0 to 3. n represents an integer of 0 to 5. b represents an integer of 1 to 4. o represents an integer of 0 to 3. p represents an integer of 0 to 10. 32When the valence of is X, 0≤p≤(X-2). c and d each independently represent an integer of 1 to 4. q and r each independently represent an integer of 0 to 3. α, β, and γ each independently represent an integer of 0 to 4.

[0208] The phenol resin also preferably has a structural unit represented by the general formula (36).

[0209] [Chemistry 10]

[0210]

[0211] In the general formula (36), X 38 It represents an aliphatic structure having 1 to 6 carbon atoms. 89 R represents a halogen atom, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkenyloxy group having 2 to 10 carbon atoms, an acyl group having 1 to 10 carbon atoms, a carboxyl group, an amino group, or a ring-forming group. The ring connected by the ring-forming group represents a monocyclic or condensed polycyclic hydrocarbon ring. 90 represents an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, or an aryl group having 6 to 15 carbon atoms. a represents an integer of 1 to 4. b represents an integer of 0 to 3. α represents an integer of 0 to 4.

[0212] In the general formulae (31) to (36) and (38) to (40), the aliphatic structure, alkyl group, cycloalkyl group, aryl group, alkenyl group, alkoxy group, alkenyloxy group, acyl group, ring-forming group, alkylene group, alkylene group, aromatic group, condensed polycyclic structure, condensed polycyclic heterocyclic structure, aromatic ring skeleton, and alicyclic skeleton may have a heteroatom and may be unsubstituted or substituted. The condensed polycyclic hydrocarbon ring formed by the ring-forming group is preferably a naphthalene ring, anthracene ring, pyrene ring, dihydroindene ring, indene ring, tetralin ring, fluorene ring, xanthene ring, or isoindolinone ring.

[0213] Examples of the polyhydroxystyrene include resins obtained by radical copolymerization of a hydroxystyrene derivative or the like with a styrene derivative and / or other copolymerization components. Examples of other copolymerization components include (meth)acrylic acid derivatives and (meth)acrylate derivatives.

[0214] Examples of the phenol group-containing epoxy resin include resins obtained by reacting a polyfunctional epoxy compound with a phenol compound having an epoxy-reactive group. The phenol group-containing epoxy resin preferably has a fluorene structure, a xanthene structure, an isoindolinone structure, a naphthalene structure, a tricyclic [5.2.1.0 2,6 ]Decane structure, or biphenyl structure.

[0215] Examples of the phenol group-containing acrylic resin include resins obtained in the following (a) to (e).

[0216] (a) A resin obtained by reacting an acrylic resin described below with a phenol compound having an addition-reactive group

[0217] (b) a resin obtained by reacting the resin obtained in (a) with a polyfunctional carboxylic acid dianhydride or a polyfunctional carboxylic acid compound;

[0218] (c) A resin obtained by free radical copolymerization of a copolymer component having a phenolic hydroxyl group and another copolymer component such as a (meth)acrylic acid derivative.

[0219] (d) a resin obtained by reacting the resin obtained in (c) with a phenol compound having an addition-reactive group

[0220] (e) A resin obtained by further reacting the resin obtained in the above (d) with a polyfunctional carboxylic dianhydride or a polyfunctional carboxylic acid compound.

[0221] The phenol group-containing acrylic resin is a resin different from polyhydroxystyrene. The phenol group-containing acrylic resin preferably has a unit derived from a (meth)acrylate derivative containing a condensed polycyclic structure, a condensed polycyclic heterocyclic structure, or an aromatic structure, or a unit derived from a styrene derivative.

[0222] <(A3) Resin>

[0223] (A) The binder resin preferably further contains (A3) a resin,

[0224] The resin (A3) preferably contains one or more selected from the group consisting of a resin containing a polycyclic side chain, an acid-modified epoxy resin, and an acrylic resin. The resin (A3) may be a single resin or a copolymer thereof.

[0225] As the resin containing a polycyclic side chain, for example, a resin obtained by reacting a compound obtained by reacting a polyfunctional epoxy compound with a carboxylic acid compound having a free radical polymerizable group with a polyfunctional carboxylic dianhydride. In addition, a resin obtained by reacting a compound obtained by reacting a polyfunctional phenol compound with a polyfunctional carboxylic dianhydride with an epoxy compound having a free radical polymerizable group can also be mentioned. The resin containing a polycyclic side chain is preferably a cardo-based resin having a fluorene structure, a xanthene structure, or an isoindolinone structure.

[0226] Examples of the acid-modified epoxy resin include resins obtained by reacting a compound obtained by reacting a polyfunctional epoxy compound with a carboxylic acid compound having a free radical polymerizable group and a polyfunctional carboxylic acid dianhydride. The acid-modified epoxy resin preferably has a naphthalene structure, a tricyclic [5.2.1.0 2,6]Epoxy (meth)acrylate resin with a decane structure or a biphenyl structure.

[0227] Examples of the acrylic resin include resins obtained by radical copolymerization of one or more selected from the group consisting of (meth)acrylic acid derivatives, (meth)acrylate derivatives, styrene derivatives, and other copolymerization components.

[0228] From the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the total content ratio of the (A1) resin in the total 100% by mass of the (A) binder resin is preferably 10% by mass or more, more preferably 30% by mass or more, further preferably 50% by mass or more, and particularly preferably 70% by mass or more. On the other hand, from the viewpoint of improving mechanical properties when heated at low temperatures, the total content ratio of the (A1) resin is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less.

[0229] From the viewpoint of suppressing the residue after development and improving the mechanical properties when heated at low temperature, the total content ratio of the (A2) resin in the total 100% by mass of the (A) binder resin is preferably 5.0% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more. On the other hand, from the viewpoint of improving the mechanical properties when heated at low temperature, the total content ratio of the (A2) resin is preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less.

[0230] From the viewpoint of improving the sensitivity during exposure and improving the mechanical properties when heated at low temperatures, the total content ratio of the (A3) resin in the total 100% by mass of the (A) binder resin is preferably 5.0% by mass or more, more preferably 10% by mass or more, further preferably 20% by mass or more, and particularly preferably 30% by mass or more. On the other hand, from the viewpoint of improving the mechanical properties when heated at low temperatures, the total content ratio of the (A3) resin is preferably 70% by mass or less, more preferably 60% by mass or less, and further preferably 50% by mass or less.

[0231] From the viewpoint of improving the mechanical properties when heated at low temperatures and improving the migration resistance, the content ratio of the (A) binder resin in the total solid content of the photosensitive composition of the present invention is preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 25% by mass or more. On the other hand, from the viewpoint of improving the mechanical properties when heated at low temperatures, the content ratio of the (A) binder resin is preferably 75% by mass or less, more preferably 65% ​​by mass or less, and further preferably 55% by mass or less. In addition, the so-called total solid content of the composition refers to the total mass of all components other than the solvent in the composition. In addition, the solid content concentration can be calculated as the solid content concentration calculated by heating 1 g of the composition at 150°C for 30 minutes to evaporate it to dryness, measuring the mass remaining after heating, and calculating it based on the mass before and after heating.

[0232] <(B) Radically polymerizable compound>

[0233] The photosensitive composition of the present invention contains (B) a radical polymerizable compound (hereinafter referred to as "(B) compound") and / or (F) a crosslinking agent. The so-called (B) compound is a compound having a radical polymerizable group, preferably a compound having at least two radical polymerizable groups. Examples and preferred descriptions of the radical polymerizable group are the same as those described in the (A) binder resin.

[0234] The photosensitive composition of the present invention preferably contains the (C) photosensitive agent described later, and further contains the (B) compound and / or the (F) crosslinking agent. From the viewpoint of promoting the photoreaction, it is more preferably a (C1) photopolymerization initiator described later, and further contains the (B) compound. In the case where the composition has negative photosensitivity, the effect of improving the sensitivity during exposure becomes significant by containing the (B) compound. On the other hand, in the case where the composition has positive photosensitivity, the effect of controlling the pattern shape after thermal curing becomes significant by containing the (B) compound.

[0235] The radical polymerizable group possessed by the (B) compound preferably has an ethylenically unsaturated double bond group, and is more preferably a (meth)acryloyl group from the viewpoint of improving the sensitivity during exposure and promoting the radical polymerization during heating at low temperature. From the viewpoint of improving the sensitivity during exposure and improving the mechanical properties during heating at low temperature, the number of radical polymerizable groups possessed by the (B) compound is preferably two or more, more preferably three or more, and further preferably four or more. On the other hand, from the viewpoint of improving the mechanical properties during heating at low temperature and improving the migration resistance, the number of radical polymerizable groups is preferably twelve or less, more preferably ten or less, further preferably eight or less, and particularly preferably six or less.

[0236] In the case where the photosensitive composition of the present invention contains (A) a binder resin and (B) a compound, when the total amount of (A) a binder resin and (B) a compound is 100 parts by mass, from the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the content of (A) a binder resin is preferably 25 parts by mass or more, more preferably 35 parts by mass or more, and further preferably 45 parts by mass or more. On the other hand, from the viewpoint of improving sensitivity during exposure and improving mechanical properties when heated at low temperatures, the content of (A) a binder resin is preferably 85 parts by mass or less, more preferably 80 parts by mass or less, and further preferably 75 parts by mass or less.

[0237] <Compound (B1) to Compound (B5)>

[0238] From the viewpoint of improving sensitivity during exposure and improving mechanical properties during heating at low temperatures, the photosensitive composition of the present invention preferably further satisfies at least one of the following conditions (δ), (ε), and (ζ).

[0239] (δ) The (B) compound contains the following (B1) first polymerizable compound (hereinafter, "(B1) compound") and (B2) second polymerizable compound (hereinafter, "(B2) compound"):

[0240] (ε) The (B) compound contains the following (B3) third polymerizable compound (hereinafter, "(B3) compound") and (B4) fourth polymerizable compound (hereinafter, "(B4) compound")

[0241] (ζ) The (B) compound contains the following (B1) compound or (B2) compound, and further contains the following (B3) compound or (B4) compound

[0242] (B1) Compound: A compound having the following structure (I-b1) and having at least two free radical polymerizable groups

[0243] (I-b1) Structure: Structure containing an alicyclic structure and / or structure containing a heteroalicyclic structure

[0244] (B2) Compound: A compound having the following structures (I-b2) and (II-b2) and having at least two free radical polymerizable groups

[0245] (I-b2) Structure: Structure containing an aromatic structure

[0246] (II-b2) Structure: Structure containing aliphatic structure

[0247] (B3) Compound: A compound having at least two (meth)acryloyl groups and having the following structure (I-b3)

[0248] (I-b3) Structure: A structure containing an aliphatic structure in which at least two (meth)acryloyl groups are linked with a minimum number of 4 to 10 atoms.

[0249] (B4) Compound: A compound having at least two (meth)acryloyl groups and having the following structure (I-b4):

[0250] (I-b4) Structure: a structure in which at least two (meth)acryloyl groups are linked with each other by a minimum number of atoms of 11 to 45 and which contains an aliphatic structure.

[0251] From the viewpoint of improving mechanical properties when heated at low temperatures, the alicyclic structure in the structure (I-b1) in the compound (B1) is preferably a condensed polycyclic alicyclic structure, more preferably a tricyclic [5.2.1.0 2,6 ] decane structure. In addition, from the viewpoint of improving mechanical properties when heated at low temperature and improving migration resistance, the heteroalicyclic structure in the structure (I-b1) is preferably a nitrogen-containing cyclic structure, more preferably a cyclic structure having at least two nitrogen atoms, and further preferably an isocyanuric acid structure and / or a triazine structure. The number of nitrogen atoms possessed by the heteroalicyclic structure in the structure (I-b1) in the compound (B1) is preferably one or more, more preferably two or more, and further preferably three or more. On the other hand, the number of nitrogen atoms is preferably six or less, and more preferably four or less.

[0252] The compound (B1) preferably further has the following structure (II-b1).

[0253] (II-b1) Structure: Structure containing aliphatic structure

[0254] From the viewpoint of improving sensitivity during exposure and improving migration resistance, the aliphatic structure in the structure (II-b1) in the (B1) compound is preferably an alkylene group, an oxyalkylene group, an alkylene group containing a hydroxyl group, an oxyalkylene group containing a hydroxyl group, an alkylene carbonyl group, an oxyalkylene carbonyl group, or an aminoalkylene carbonyl group.

[0255] From the viewpoint of improving the mechanical properties when heated at low temperatures, the aromatic structure in the (I-b2) structure in the (B2) compound is preferably a benzene structure or a biphenyl structure. In addition, from the same viewpoint, the aromatic structure in the (I-b2) structure is preferably a condensed polycyclic structure, more preferably a fluorene structure, a dihydroindene structure, or a naphthalene structure. In addition, from the same viewpoint, the aromatic structure in the (I-b2) structure is preferably a condensed polycyclic heterocyclic structure, more preferably a xanthene structure, an indolinone structure, or an isoindolinone structure.

[0256] From the perspective of improving sensitivity during exposure and improving migration resistance, the aliphatic structure in the (II-b2) structure in the (B2) compound is preferably an alkylene group, an oxyalkylene group, an alkylene group containing a hydroxyl group, an oxyalkylene group containing a hydroxyl group, an alkylene carbonyl group, an oxyalkylene carbonyl group, or an aminoalkylene carbonyl group.

[0257] In the case where the (B3) compound or the (B4) compound has two (meth) acryloyl groups, the so-called minimum number of atoms in the (I-b3) structure or the (I-b4) structure refers to the minimum number of atoms of carbon atoms and heteroatoms between the carbonyl carbons of the two (meth) acryloyl groups. In addition, the carbon atoms between the carbonyl carbons and the atoms bonded by the heteroatoms are not included in the calculation of the minimum number of atoms. For example, in the case where there are oxygen atoms, acryloyl groups, and oxygen atoms between the carbonyl carbons, the minimum number of atoms is five. In addition, in the case where the (B3) compound or the (B4) compound has three or more (meth) acryloyl groups, the so-called minimum number of atoms refers to the minimum number of atoms of carbon atoms and heteroatoms including the carbonyl carbons connecting all the (meth) acryloyl groups. Similarly, the carbon atoms and heteroatoms bonded to the carbonyl carbons are not included in the calculation of the minimum number of atoms.

[0258] The (B3) compound can further reduce the low molecular weight of the (B) compound in the cured product by setting the minimum number of atoms in the (I-b3) structure to a specific range, and the effect of improving the migration resistance becomes significant. The minimum number of atoms in the (I-b3) structure is preferably five or more, and more preferably six or more. On the other hand, the minimum number of atoms in the (I-b3) structure is preferably nine or less, and more preferably eight or less. On the other hand, the (B4) compound is set to a specific range by setting the minimum number of atoms in the (I-b4) structure to improve the molecular mobility and the collision probability of (meth) acryloyl groups with each other, or (meth) acryloyl groups with other free radical polymerizable groups, and the effect of improving the sensitivity during exposure becomes significant. The minimum number of atoms in the (I-b4) structure is preferably thirteen or more, more preferably fifteen or more, and further preferably seventeen or more, and particularly preferably twenty or more. On the other hand, the minimum number of atoms in the (I-b4) structure is preferably forty or less, more preferably thirty-five or less, and further preferably thirty or less, and particularly preferably twenty-five or less.

[0259] In the (B3) compound and the (B4) compound, from the viewpoint of improving sensitivity during exposure and improving resistance to migration, the aliphatic structure in the (I-b3) structure and the (I-b4) structure is preferably an alkylene group, an oxyalkylene group, an alkylene group containing a hydroxyl group, an oxyalkylene group containing a hydroxyl group, an alkylene carbonyl group, an oxyalkylene carbonyl group, or an aminoalkylene carbonyl group. In addition, the aliphatic structure in the (I-b3) structure and the (I-b4) structure is preferably a structure derived from an aliphatic polyfunctional alcohol. In addition, the (B3) compound and the (B4) compound are different compounds from the (B1) compound and the (B2) compound, and do not have a structure containing an alicyclic structure, a structure containing a heteroalicyclic structure, and a structure containing an aromatic structure.

[0260] The compound (B) described above can improve the crosslinking degree of the cured product by generating free radicals during exposure or heating at low temperature, and can also improve the crosslinking degree by reacting with the free radical polymerizable groups at the side chains or terminals of the resin, so it is estimated that the mechanical properties when heated at low temperature are improved. In addition, the compound (B) having an aliphatic structure in the structure (II-b1), structure (II-b2), structure (I-b3), or structure (I-b4) described above can reduce the low molecular weight components derived from the compound (B) in the cured product, thereby suppressing ion migration or electromigration and improving migration resistance.

[0261] From the viewpoint of improving mechanical properties when heated at low temperatures, the compound (B) preferably further contains the following compound (B5). The compound (B5) is a compound different from the compound (B2) and does not have the structure (II-b2).

[0262] (B5) Compound: a compound having a structure including a condensed polycyclic structure and / or a structure including a condensed polycyclic heterocyclic structure, and further having at least two free radical polymerizable groups

[0263] The condensed polycyclic structure in the compound (B5) is preferably a fluorene structure, a dihydroindene structure, or a naphthalene structure. In addition, the condensed polycyclic heterocyclic structure in the compound (B5) is preferably a xanthene structure, an indolinone structure, or an isoindolinone structure.

[0264] The (B) compound also preferably contains one or more selected from the group consisting of the (B1) compound, the (B2) compound, the (B3) compound, the (B4) compound, and the (B5) compound. The (B) compound also preferably contains two or more selected from the group consisting of the (B1) compound, the (B2) compound, the (B3) compound, and the (B4) compound, and more preferably further contains the (B5) compound. The preferred contents of these (B) compounds are also the same as described above.

[0265] In addition, the total content of the compound (B1), the compound (B2), the compound (B3), the compound (B4), and the compound (B5) is preferably 15 parts by mass or more, more preferably 20 parts by mass or more, and further preferably 25 parts by mass or more. On the other hand, the total content of the compound (B1), the compound (B2), the compound (B3), the compound (B4), and the compound (B5) is preferably 75 parts by mass or less, more preferably 65 parts by mass or less, and further preferably 55 parts by mass or less.

[0266] <(C) Photosensitizer>

[0267] The photosensitive composition of the present invention contains (C) a photosensitizer. The (C) photosensitizer refers to a compound that generates other compounds by bond cleavage, reaction, or structural change upon exposure to light, thereby imparting positive or negative photosensitivity to the composition.

[0268] The (C) photosensitive agent preferably contains one or more selected from the group consisting of (C1) photopolymerization initiator, (C2) naphthoquinonediazide compound, (C3) photoacid generator, and (C4) photobase generator. When the composition is given negative photosensitivity, it is preferably a (C1) photopolymerization initiator, and more preferably it further contains one or more selected from the group consisting of (C2) naphthoquinonediazide compound, (C3) photoacid generator, and (C4) photobase generator. When the composition is given positive photosensitivity, it is preferably a (C2) naphthoquinonediazide compound, and more preferably it further contains one or more selected from the group consisting of (C1) photopolymerization initiator, (C3) photoacid generator, and (C4) photobase generator.

[0269] When the total amount of the binder resin (A) and the compound (B) is 100 parts by mass, the content of the photosensitive agent (C) is preferably 1.0 parts by mass or more, more preferably 3.0 parts by mass or more, and further preferably 5.0 parts by mass or more from the viewpoint of improving the sensitivity during exposure. On the other hand, from the viewpoint of suppressing the residue after development, the content of the photosensitive agent (C) is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and further preferably 20 parts by mass or less.

[0270] <(C1) Photopolymerization initiator>

[0271] The so-called (C1) photopolymerization initiator refers to a compound that generates free radicals by bond cleavage and / or reaction by exposure. The (C1) photopolymerization initiator is preferably contained for negative pattern formation, and the effect of improving the sensitivity during exposure becomes significant. The (C1) photopolymerization initiator is preferably an α-hydroxy ketone compound, an α-amino ketone compound, a biimidazole compound, a phosphine oxide compound, or an oxime ester compound. The preferred contents of these (C) photosensitive agents are also the same as described above.

[0272] From the viewpoint of improving the sensitivity during exposure and improving the mechanical properties during heating at low temperatures, the (C) photosensitive agent preferably contains a (C1) photopolymerization initiator, and the (C1) photopolymerization initiator contains a (C1-1) oxime ester compound (hereinafter referred to as "(C1-1) compound") and / or a (C1-2) phosphine oxide compound (hereinafter referred to as "(C1-2) compound"), and more preferably contains a (C1-1) compound. The so-called (C1-1) compound refers to a compound having an oxime ester structure in the molecule as a structure that generates free radicals by bond cleavage and / or reaction by exposure. The so-called (C1-2) compound refers to a compound having a phosphine oxide structure in the molecule and an acyl group as a structure that generates free radicals by bond cleavage and / or reaction by exposure. The preferred contents of these (C) photosensitive agents are also the same as described above.

[0273] From the viewpoint of improving sensitivity during exposure and improving mechanical properties during heating at low temperature, the compound (C1-1) preferably has one or more selected from the group consisting of the following (I) and (II).

[0274] (I) A structure in which at least one oxime ester structure is bonded to a condensed polycyclic structure, a condensed polycyclic heterocyclic structure, a diphenyl sulfide structure, or a benzene structure (α-oxime structure) or a structure in which at least one oxime ester carbonyl structure is bonded to the condensed polycyclic structure, the condensed polycyclic heterocyclic structure, the diphenyl sulfide structure, or the benzene structure (β-oxime structure)

[0275] (II) one or more selected from the group consisting of a nitro group, a group substituted with a halogen atom, a naphthylcarbonyl structure, a trimethylbenzoyl structure, a phenylthiocarbonyl structure, a furanylcarbonyl structure, at least two oxime ester structures, and a structure to which at least two oxime ester carbonyl structures are bonded (hereinafter referred to as a "specific substituent").

[0276] The condensed polycyclic structure is preferably a fluorene structure, a benzofluorene structure, a dibenzofluorene structure, an indene structure, a dihydroindene structure, a benzoindene structure, or a benzodihydroindene structure. The condensed polycyclic heterocyclic structure is preferably a carbazole structure, a dibenzofuran structure, a dibenzothiophene structure, a benzocarbazole structure, an indole structure, an indoline structure, a benzoindole structure, a benzoindoline structure, a phenothiazine structure, or a phenothiazine oxide structure. The (C1-1) compound is more preferably a structure having a specific substituent bonded to the condensed polycyclic structure, the condensed polycyclic heterocyclic structure, the diphenyl sulfide structure, or the benzene structure.

[0277] From the viewpoint of improving the sensitivity during exposure and improving the mechanical properties during heating at low temperatures, the (C1-1) compound preferably has a group substituted by a halogen atom, and more preferably has a group substituted by a fluorine atom. The group substituted by a halogen atom is preferably a trifluoromethyl group, a trifluoropropyl group, a trichloropropyl group, a tetrafluoropropyl group, a fluorocyclopentyl group, a fluorophenyl group, or a pentafluorophenyl group. It is inferred that the reason is that when the polyimide-based resin contains a carboxylic acid residue having a fluorine atom and / or an amine residue having a fluorine atom, the (C1-1) compound can improve the compatibility with the (A) binder resin and promote free radical polymerization from the film surface to the deep part of the film.

[0278] From the viewpoint of having photobleaching property, the compound (C1-1) preferably has a fluorene structure, a benzofluorene structure, a dibenzofluorene structure, an indole structure, a benzindole structure, a phenothiazine structure, a phenothiazine oxide structure, or a diphenyl sulfide structure, and preferably has a structure in which at least one oxime ester carbonyl structure is bonded to a condensed polycyclic structure, a condensed polycyclic heterocyclic structure, a diphenyl sulfide structure, or a benzene structure. When the compound (C1-1) has photobleaching property, the effects of improving the sensitivity during exposure and improving the pattern processability under thick film become significant. In addition, it is inferred that by reducing the low molecular weight components derived from the compound (C1-1) in the cured product, ion migration or electromigration can be suppressed, and the migration resistance can be improved. In addition, the so-called photobleaching property means that the absorbance at a wavelength in the ultraviolet region (for example, 400 nm or less) and / or the absorbance at a wavelength of visible light (380 nm to 780 nm) is reduced due to bond cleavage and / or reaction caused by exposure.

[0279] It is inferred that the compound (C1-1) described above can increase the crosslinking degree of the cured product or promote the ring closure reaction of the resin by generating free radicals when heated at low temperature or by interaction with the oxime ester structure, thereby improving the mechanical properties when heated at low temperature.

[0280] Examples of the compound (C1-2) include 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-(2,4,4-trimethylpentyl)phosphine oxide.

[0281] It is inferred that the compound (C1-2) can increase the crosslinking degree of the cured product or promote the ring closure reaction of the resin by generating free radicals when heated at low temperature or by interaction with the phosphine oxide structure, thereby improving the mechanical properties when heated at low temperature.

[0282] <(C2) Naphthoquinone diazide compounds>

[0283] The so-called (C2) naphthoquinonediazide compound refers to a compound that undergoes structural changes by exposure to produce indene carboxylic acid and / or sulfonated indene carboxylic acid. The (C2) naphthoquinonediazide compound is preferred for positive pattern formation. The (C2) naphthoquinonediazide compound is preferably a 1,2-naphthoquinonediazide-5-sulfonate or a 1,2-naphthoquinonediazide-4-sulfonate of a compound having a phenolic hydroxyl group. The preferred contents of these (C) photosensitive agents are also the same as described above.

[0284] <(C3) Photoacid generator>

[0285] The so-called (C3) photoacid generator refers to a compound that generates an acid by bond cleavage and / or reaction by exposure. From the viewpoint of promoting cationic polymerization, it is preferred to contain a (C3) photoacid generator for negative pattern formation. On the other hand, in the case where a resin or the like has an acidic group protected by an acid dissociative group, it is preferred for positive pattern formation from the viewpoint of freeing the acidic group by exposure. As the (C3) photoacid generator, for example, ionic compounds or non-ionic compounds can be listed. The ionic compound is preferably a triorganosulfonium salt compound. The non-ionic compound is preferably a halogen-containing compound, a diazomethane compound, a sulfone compound, a sulfonate compound, a carboxylate compound, a sulfonimide compound, a phosphate compound, or a sulfone benzotriazole compound. The preferred contents of these (C) photosensitive agents are also the same as described above.

[0286] <(C4) Photobase generator>

[0287] The so-called (C4) photobase generator refers to a compound that generates a base by bond cleavage and / or reaction by exposure. From the viewpoint of promoting anionic polymerization, it is preferred to contain a (C4) photobase generator for negative pattern formation. On the other hand, in the case where a resin or the like has an acidic group protected by alkali dissociation, it is preferred for positive pattern formation from the viewpoint of freeing the acidic group by exposure. As the (C4) photobase generator, for example, ionic compounds or nonionic compounds can be listed. The ionic compound is preferably a diazabicycloolefin salt compound, a triazabicycloolefin salt compound, an α-ketoquaternary ammonium salt compound, a benzylquaternary ammonium salt compound, a guanidine salt compound, or a biguanidine salt compound. The ionic compound preferably has a ketoprofen structure, an oxo-xanthene structure, a benzofuran structure, or a naphthalene structure. The nonionic compound is preferably a nitrobenzyl carbamate compound, anthracenyl carbamate compound, benzoin-based carbamate compound, anthraquinone-based carbamate compound, hydroxycinnamic acid amide compound, or coumarin amide compound. The preferred contents of these (C) photosensitizers are also the same as described above.

[0288] <(D) Coloring agent>

[0289] The photosensitive composition of the present invention also preferably contains (D) a colorant. The so-called (D) colorant refers to a compound that colors the visible light by absorbing light of a wavelength (380nm to 780nm). By containing the (D) colorant, the chromaticity of the transmitted light or reflected light of the film of the composition can be adjusted, or the film of the composition can be given a light-shielding property. The (D) colorant is preferably a pigment or a dye. From the viewpoint of improving the light-shielding property, the (D) colorant preferably contains a black agent.

[0290] The so-called black in the colorant (D) refers to a colorant containing "BLACK" in the Colour Index Generic Name (hereinafter referred to as "CI number"). When a colorant without a CI number is contained, it refers to a colorant that is black when formed into a cured film. The so-called black when formed into a cured film means that in the transmission spectrum of the cured film of the composition containing the (D) colorant, for the transmittance per 1.0 μm of the film thickness at a wavelength of 550 nm, when the film thickness is converted in the range of 0.10 μm to 1.5 μm based on the Lambert-Beer formula with a transmittance of 10% at a wavelength of 550 nm, the transmittance of the converted transmission spectrum at a wavelength of 450 nm to 650 nm is less than 25%. The transmission spectrum of the cured film can be obtained based on the method described in paragraph

[0285] of International Publication No. 2019 / 087985.

[0291] From the viewpoint of improving light-shielding properties and improving reliability, the content ratio of the (D) colorant in the total solid content of the photosensitive composition of the present invention is preferably 5.0% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, further more preferably 20% by mass or more, and particularly preferably 30% by mass or more. On the other hand, from the viewpoint of improving sensitivity during exposure and suppressing residue after development, the content ratio of the (D) colorant is preferably 70% by mass or less, more preferably 50% by mass or less.

[0292] (D) The colorant preferably contains a black pigment, more preferably an organic black pigment and / or an inorganic black pigment. The organic black pigment is preferably a benzofuranone black pigment, a perylene black pigment, an azomethine black pigment, an anthraquinone black pigment, an aniline black pigment, an azo black pigment, or carbon black. The inorganic black pigment is preferably a metal element microparticle, oxide, composite oxide, sulfide, sulfate, nitrate, carbonate, nitride, carbide, or nitrogen oxide. The metal element is preferably Ti, Zr, V, Cr, Mn, Co, Ni, Y, Nb, Hf, Ta, W, Re, Fe, Cu, Zn, or Ag. The inorganic black pigment preferably contains an element different from these metal elements, more preferably B, Al, Si, Mn, Co, Ni, Fe, Cu, Zn, or Ag. (D) The colorant also preferably contains a black dye. The black dye is preferably a black dye containing a chromium element and / or an azo black dye. Preferred content ratios of these (D) coloring agents are also the same as described above.

[0293] The benzofuranone-based black pigment is preferably a compound having at least two benzofuran-2(3H)-one structures that can share a benzene ring or at least two benzofuran-3(2H)-one structures that can share a benzene ring, their geometric isomers, their salts, or their salts. The perylene-based black pigment is preferably a compound having a 3,4,9,10-perylenetetracarboxylic acid bisbenzimidazole structure, their geometric isomers, their salts, or their salts. The azomethine-based black pigment is preferably a compound having an azomethine structure and a carbazole structure or a salt thereof.

[0294] (D) The colorant is preferably a mixture of colorants containing two or more colors, more preferably (I) containing blue, red, and yellow; (II) containing blue, red, and orange; (III) containing blue, purple, and orange; or (IV) containing purple and yellow. The colorant mixture is more preferably a mixture of coloring pigments and / or a mixture of coloring dyes. The coloring pigment is preferably an anthraquinone pigment, a diketopyrrolopyrrole pigment, a perylene pigment, an isoindoline pigment, an isoindolinone pigment, an imidazolinone pigment, a quinacridone pigment, an anthrone pigment, a phthalocyanine pigment, an indanthrone pigment, or a dioxazine pigment. The coloring dye is preferably a squarylium salt dye, a xanthene dye, a triarylmethane dye, or a phthalocyanine dye. The preferred content ratios of these (D) colorants are also the same as described above.

[0295] The photosensitive composition of the present invention also preferably has a coating layer on the pigment. The coating layer refers to a layer that coats the surface of the pigment, and examples thereof include a layer formed by surface treatment with a silane coupling agent, surface treatment with a silicate, surface treatment with a metal alkoxide, or coating treatment with a resin. The coating layer preferably has one or more selected from the group consisting of a silica coating layer, a metal oxide coating layer, and a metal hydroxide coating layer.

[0296] <(E) Dispersant>

[0297] The photosensitive composition of the present invention also preferably contains (E) a dispersant. The so-called (E) dispersant refers to a compound having a surface affinity structure that interacts with the surface of the pigment and a dispersion stabilization structure that prevents the pigments from approaching each other. From the viewpoint of improving the dispersion stability of the pigment, the photosensitive composition of the present invention more preferably contains the pigment and further contains (E) a dispersant.

[0298] (E) The dispersant is preferably a dispersant having a basic group, a dispersant having a basic group and an acidic group, or a dispersant having a salt structure of a basic group. In addition, a dispersant having an acidic group, a dispersant having a salt structure of an acidic group, or a dispersant having neither a basic group nor an acidic group may be contained.

[0299] (E) The basic group possessed by the dispersant is preferably a tertiary amino group or a nitrogen-containing ring structure. (E) The acidic group possessed by the dispersant is preferably a carboxyl group, a sulfonic acid group, or a phosphoric acid group. (E) The salt structure of the basic group possessed by the dispersant is preferably a quaternary ammonium salt structure or a salt structure containing a nitrogen ring structure. The counter anion in the salt structure of the basic group is preferably a carboxylate anion, a sulfonate anion, a sulfate anion, a nitrate anion, a phosphate anion, or a halogen anion. (E) The polymer chain possessed by the dispersant is preferably a fluororesin, a silicone, an acrylic resin, a polyoxyalkylene ether, a polyester, a polyurethane, a polyol, a polyalkyleneamine, a polyethyleneimine, or a polyallylamine.

[0300] When the photosensitive composition of the present invention contains a pigment, when the pigment is 100 parts by mass, from the viewpoint of improving the dispersion stability of the pigment, the content of the (E) dispersant is preferably 5.0 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 15 parts by mass or more. On the other hand, from the viewpoint of improving the sensitivity during exposure, the content of the (E) dispersant is preferably 50 parts by mass or less, and more preferably 40 parts by mass or less.

[0301] <(F) Cross-linking agent>

[0302] The photosensitive composition of the present invention contains (B) a compound and / or (F) a crosslinking agent. The crosslinking agent (F) refers to a compound having a crosslinking group, a cationically polymerizable group, or an anionically polymerizable group that can react with a resin or the like.

[0303] The photosensitive composition of the present invention preferably contains the (C) photosensitive agent, and further contains the (B) compound and / or the (F) crosslinking agent. From the viewpoint of promoting the photoreaction, it is more preferably contained the (C3) photoacid generator or the (C4) photobase generator, and further contains the (F) crosslinking agent. On the other hand, from the viewpoint of increasing the crosslinking degree of the resin, etc., it is also preferably contained the (C2) naphthoquinonediazide compound, and further contains the (F) crosslinking agent.

[0304] From the viewpoint of improving the sensitivity during exposure and improving the mechanical properties during heating at low temperatures, the crosslinking agent (F) is preferably a compound having one or more groups selected from the group consisting of an alkoxyalkyl group, a hydroxyalkyl group, an epoxy group, an oxetane group, and a blocked isocyanate group (hereinafter referred to as a "specific crosslinking group"). The alkoxyalkyl group is preferably an alkoxymethyl group or an alkoxyethyl group, and more preferably a methoxymethyl group or a methoxyethyl group. The hydroxyalkyl group is preferably a hydroxymethyl group or a hydroxyethyl group. From the viewpoint of improving the sensitivity during exposure and improving the mechanical properties during heating at low temperatures, the number of specific crosslinking groups possessed by the crosslinking agent (F) is preferably two or more, more preferably three or more, further preferably four or more, and particularly preferably six or more. On the other hand, from the viewpoint of improving the mechanical properties during heating at low temperatures, the number of specific crosslinking groups is preferably twelve or less, more preferably ten or less, and further preferably eight or less.

[0305] When the total amount of the binder resin (A) and the compound (B) is 100 parts by mass, the content of the crosslinking agent (F) is preferably 1.0 parts by mass or more, more preferably 3.0 parts by mass or more, and further preferably 5.0 parts by mass or more, from the viewpoint of improving the sensitivity during exposure and improving the mechanical properties during heating at low temperatures. On the other hand, from the viewpoint of suppressing the residue after development and improving the mechanical properties during heating at low temperatures, the content of the crosslinking agent (F) is preferably 30 parts by mass or less, and more preferably 20 parts by mass or less.

[0306] <(F1) Compound and (F2) Compound>

[0307] From the viewpoint of suppressing residue after development and improving mechanical properties when heated at low temperature, the crosslinking agent (F) preferably contains the following (F1) compound and / or (F2) compound. The preferred contents of these (F) crosslinking agents are also the same as described above.

[0308] (F1) Compound: a compound having at least two phenolic hydroxyl groups and at least two specific crosslinking groups

[0309] (F2) Compound: a compound having a structure including a heteroalicyclic structure and at least two specific crosslinking groups.

[0310] The compound (F1) preferably has a structure in which at least two phenolic hydroxyl groups and specific crosslinking groups are bonded to one aromatic structure. In addition, the compound (F1) more preferably has a structure in which at least two phenolic hydroxyl groups and at least two specific crosslinking groups are bonded to one aromatic structure.

[0311] The heteroalicyclic structure in the (F2) compound is preferably a nitrogen-containing cyclic structure, and more preferably a cyclic structure having at least two nitrogen atoms. In addition, the cyclic structure having at least two nitrogen atoms is preferably selected from one or more of the group consisting of an isocyanuric acid structure, a triazine structure, a glycoluril structure, an imidazolidinone structure, a pyrazole structure, an imidazole structure, a triazole structure, a tetrazole structure, and a purine structure, and more preferably an isocyanuric acid structure and / or a triazine structure. The number of nitrogen atoms possessed by the heteroalicyclic structure in the (F2) compound is preferably one or more, more preferably two or more, and further preferably three or more. On the other hand, the number of nitrogen atoms is preferably six or less, and more preferably four or less.

[0312] <(G) Inorganic particles>

[0313] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains (G) inorganic particles. The so-called (G) inorganic particles refer to particles containing elements selected from the group consisting of metal elements, semi-metal elements, and semiconductor elements in the main component. In addition, the so-called main component refers to the component that contains the most in terms of mass among the constituent components. From the viewpoint of improving migration resistance, the (G) inorganic particles preferably have hydroxyl groups and / or silanol groups on the particle surface.

[0314] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains (G) inorganic particles, and the (G) inorganic particles contain one or more selected from the group consisting of silica particles, aluminum oxide particles, titanium oxide particles, vanadium oxide particles, chromium oxide particles, iron oxide particles, cobalt oxide particles, copper oxide particles, zinc oxide particles, zirconium oxide particles, niobium oxide particles, tin oxide particles, and cerium oxide particles. From the viewpoint of improving migration resistance and suppressing external light reflection, it is more preferable to contain silica particles.

[0315] From the viewpoint of improving migration resistance, the silica particles preferably have functional groups on the surface. The functional groups that the silica particles have on the surface are preferably free radical polymerizable groups, thermally reactive groups, hydroxyl groups, silanol groups, alkoxysilyl groups, alkylsilyl groups, dialkylsilyl groups, trialkylsilyl groups, phenylsilyl groups, or diphenylsilyl groups. The free radical polymerizable groups or thermally reactive groups are also preferably reaction residues of surface modification groups containing free radical polymerizable groups or reaction residues of surface modification groups containing thermally reactive groups. The silica particles are more preferably free radical polymerizable groups and / or thermally reactive groups on the surface. The examples and preferred descriptions about free radical polymerizable groups are as described in the (A) binder resin.

[0316] From the viewpoint of improving migration resistance, the average primary particle diameter of the silica particles is preferably 5.0 nm or more, more preferably 7.0 nm or more, and further preferably 10 nm or more. On the other hand, from the viewpoint of suppressing residue after development and suppressing external light reflection, the average primary particle diameter of the silica particles is preferably 200 nm or less, more preferably 100 nm or less, further preferably 70 nm or less, further preferably 50 nm or less, particularly preferably 30 nm or less, and most preferably 20 nm or less.

[0317] In addition, from the viewpoint of high elastic modulus and low thermal expansion coefficient, the average primary particle diameter of the silica particles is preferably more than 0.20 μm, more preferably 0.30 μm or more, and further preferably 0.50 μm or more. On the other hand, from the viewpoint of suppressing the residue after development, the average primary particle diameter of the silica particles is preferably 100 μm or less, more preferably 50 μm or less, further preferably 30 μm or less, further more preferably 10 μm or less, particularly preferably 5.0 μm or less, and most preferably 3.0 μm or less.

[0318] The so-called primary particle diameter of silica particles refers to the major axis diameter in the primary particles of silica particles. The average primary particle diameter of the silica particles in the film can be calculated as the average value obtained by photographing and analyzing the cross section of the film using a transmission electron microscope (hereinafter referred to as "TEM") and measuring 30 primary particles of the silica particles. The average primary particle diameter of the silica particles in the silica particle dispersion is obtained by measuring the particle size distribution by dynamic light scattering or laser diffraction-scattering method. As a measuring instrument, for example, SZ-100 manufactured by Horiba, Ltd. can be listed in the case of dynamic light scattering method, and SLD3100 manufactured by Shimadzu Corporation or LA-920 manufactured by Horiba, Ltd. or its equivalent can be listed in the case of laser diffraction-scattering method.

[0319] It is believed that the silica particles described above can capture metal impurities or ionic impurities that have a negative effect on electrical insulation through the acidity or negative charge of the hydroxyl group and / or silanol group on the particle surface. In addition, it is inferred that the captured impurities can be continuously retained even after heat treatment or voltage application due to the solid structure of the particles, thereby improving migration resistance. In addition, it is believed that the silica particles that are biased toward the surface of the cured product can reduce reflection and scattering of incident external light.

[0320] From the viewpoint of improving migration resistance, the silica particles preferably contain silica particles containing sodium. Examples of the sodium element include ions (Na +) or a salt with a silanol group (Si-ONa). The content of sodium in the silica particles is preferably 1.0 mass ppm or more, more preferably 5.0 mass ppm or more, and further preferably 10 mass ppm or more, and further preferably 50 mass ppm or more, and particularly preferably 100 mass ppm or more. On the other hand, the content of sodium in the silica particles is preferably 10,000 mass ppm or less, more preferably 5,000 mass ppm or less, and further preferably 1,000 mass ppm or less. The sodium element possessed by the silica particles can be detected by photographing and analyzing the cross-section of the film using a transmission electron microscope-energy dispersive X-ray spectroscopy (hereinafter, "TEM-EDX") . It is believed that by intentionally containing a trace amount of sodium in the silica particles, the polarization structure or charge balance in the hardened material can be controlled. From this, it is inferred that the migration resistance is improved by efficiently capturing metal impurities or ionic impurities that have an adverse effect on electrical insulation.

[0321] From the viewpoint of improving migration resistance, the content ratio of the (G) inorganic particles in the total solid content of the photosensitive composition of the present invention is preferably 5.0% by mass or more, more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more. On the other hand, from the viewpoint of suppressing the residue after development, the content ratio of the (G) inorganic particles is preferably 90% by mass or less, more preferably 70% by mass or less, and further preferably 50% by mass or less.

[0322] <Other additives>

[0323] The photosensitive composition of the present invention also preferably contains one or more selected from the group consisting of a thermal color developer, an oxidative color developer, a dissolution promoter, an ink repellent, a sensitizer, a chain transfer agent, a polymerization inhibitor, a silane coupling agent, and a surfactant. These additives may also use existing additives.

[0324] <Solvent>

[0325] The photosensitive composition of the present invention preferably further contains a solvent. From the viewpoint of solubility of various resins and various additives, the solvent is preferably a compound having an alcoholic hydroxyl group, a carbonyl group, an ester bond, an amide bond, or at least three ether bonds.

[0326] When the photosensitive composition of the present invention contains a pigment and also contains a dispersant, the solvent is preferably a compound having a carbonyl group, an ester bond, or an amide bond, more preferably a compound having an alkylcarbonyl group, a dialkylcarbonyl group, a formyl group, a carboxyl group, a carboxylate bond, a carbonate bond, a formate bond, an amide group, an imide group, a urea bond, or a carbamate bond, and further preferably a compound having an acetate bond, a propionate bond, or a butyrate bond.

[0327] <Content of specific aromatic compounds, specific anions, and specific organic acids>

[0328] The photosensitive composition of the first aspect of the present invention satisfies the following condition (α). The photosensitive composition of the second aspect of the present invention satisfies one or more selected from the group consisting of the following condition (α), condition (β), and condition (γ).

[0329] (α) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (1x)

[0330] (1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the total solid content of the photosensitive composition is 0.010 mass ppm to 1,000 mass ppm

[0331] (β) further contains one or more selected from the group consisting of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (2x):

[0332] (2x) The total content of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is 0.010 mass ppm to 1,000 mass ppm

[0333] (γ) further contains one or more selected from the group consisting of benzene, toluene, xylene, and naphthalene, and satisfies the following condition (3)

[0334] (3) The total content of benzene, toluene, xylene, and naphthalene in the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0335] Sulfonic acid is an organic compound having at least one sulfonic acid group. Sulfonic acid is preferably a compound having a substituent containing a carbon element and having a sulfonic acid group. Phosphate, phosphonic acid, phosphonate, phosphite, phosphinic acid, and phosphite are preferably compounds having a substituent containing a carbon element and having an acidic group containing a phosphorus element. Carboxylic acid containing fluorine is preferably a compound having a substituent containing a fluorine element and a carbon element and having a carboxyl group.

[0336] When the condition (β) is satisfied, the photosensitive composition of the present invention preferably further contains a compound containing a specific anion. When the photosensitive composition of the present invention contains a compound containing a specific anion, it preferably further contains ammonium ions, primary ammonium ions, secondary ammonium ions, tertiary ammonium ions, or quaternary ammonium ions as cationic species.

[0337] The phosphate, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, and phosphite ester are preferably phosphate monoester, phosphate diester, phosphonic acid, phosphonic acid monoester, phosphite monoester, phosphite diester, phosphinic acid, or phosphite monoester.

[0338] The specific organic acid preferably has one or more selected from the group consisting of a monovalent aliphatic group to a divalent aliphatic group having 1 to 18 carbon atoms, a monovalent alicyclic group to a divalent alicyclic group having 4 to 18 carbon atoms, a monovalent aromatic group to a divalent aromatic group having 6 to 15 carbon atoms, a monovalent fluorinated aliphatic group to a divalent fluorinated aliphatic group having 1 to 18 carbon atoms, a monovalent fluorinated alicyclic group to a divalent fluorinated alicyclic group having 4 to 18 carbon atoms, and a monovalent fluorinated aromatic group to a divalent fluorinated aromatic group having 6 to 15 carbon atoms.

[0339] From the viewpoint of suppressing the residue after development, improving the mechanical properties when heated at low temperature, and improving the migration resistance, the photosensitive composition as the second embodiment of the present invention preferably satisfies two or more selected from the group consisting of the above conditions (α), the above conditions (β), and the above conditions (γ). From the viewpoint of the effect of the above invention, the photosensitive composition of the present invention more preferably satisfies the above condition (α), and further satisfies the above condition (β) and / or the above condition (γ).

[0340] From the viewpoint of suppressing the residue after development, improving the mechanical properties when heated at low temperature, and improving the migration resistance, the photosensitive composition of the present invention preferably satisfies the condition (α) and further satisfies the condition (β). From the viewpoint of the effect of the present invention, the photosensitive composition of the present invention preferably satisfies the condition (α) and further satisfies the condition (γ).

[0341] From the viewpoint of suppressing residue after development, improving mechanical properties when heated at low temperature, and improving migration resistance, the photosensitive composition of the present invention preferably satisfies the condition (γ) and satisfies the condition (α) and / or the condition (β).

[0342] On the other hand, in the case where the storage stability of the photosensitive composition is poor, for example, the generation of foreign matter after storage at room temperature sometimes becomes a problem. In the case where foreign matter is generated during the storage of the photosensitive composition, when the cured material of the photosensitive composition such as the cured material in the electronic component of the present invention is formed, foreign matter remains in the cured material or in the pattern opening. Due to such foreign matter, it becomes a factor that reduces the reliability of the light-emitting element in the display device or a factor that reduces the migration resistance in the electronic component. The photosensitive composition of the present invention is set to an appropriate range by setting the content of a specific aromatic compound, the content of a specific anion, or the content of a specific organic acid, and the effect of improving the storage stability becomes significant.

[0343] The total content of the specific aromatic compound in the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific aromatic compound is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 100 mass ppm or less. Furthermore, from the perspective of suppressing the residue after development, improving the mechanical properties when heated at low temperature, and improving the migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0344] The total content of the specific anion in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, and further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific anion is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 100 mass ppm or less. Furthermore, from the perspective of suppressing the residue after development, improving the mechanical properties when heated at low temperatures, and improving the migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, and further preferably 10 mass ppm or less, and further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0345] The total content of the specific organic acid in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, and further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific organic acid is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 100 mass ppm or less. Furthermore, from the perspective of suppressing the residue after development, improving the mechanical properties when heated at low temperatures, and improving the migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, and further preferably 10 mass ppm or less, and further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0346] In the case of satisfying the condition (α), the photosensitive composition of the present invention preferably contains sulfonic acid and / or carboxylic acid containing fluorine element, and more preferably contains sulfonic acid. The total content ratio of sulfonic acid and / or carboxylic acid containing fluorine element in the total of specific organic acid is preferably 50 mass % or more, and more preferably 60 mass % or more. On the other hand, the total content ratio of sulfonic acid and / or carboxylic acid containing fluorine element is preferably 100 mass % or less, more preferably 90 mass % or less, and further preferably 80 mass % or less. In addition, it is more preferred that the content ratio of sulfonic acid is respectively the above-mentioned content ratio.

[0347] When the condition (β) is satisfied, the photosensitive composition of the present invention preferably contains one or more selected from the group consisting of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and more preferably contains one or more selected from the group consisting of phosphate ion, phosphite ion, and hypophosphite ion. The total of the ratio of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total of specific anions is preferably 50% by mass or more, more preferably 60% by mass or more. On the other hand, the total of the ratio of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less. In addition, it is more preferred that the total of the ratio of phosphate ion, phosphite ion, and hypophosphite ion is the above-mentioned ratio.

[0348] When the condition (γ) is satisfied, the photosensitive composition of the present invention preferably contains one or more selected from the group consisting of benzene, toluene, and xylene, and more preferably contains benzene and / or toluene. The total content ratio of benzene, toluene, and xylene in the total of the specific aromatic compounds is preferably 50% by mass or more, and more preferably 60% by mass or more. On the other hand, the total content ratio of benzene, toluene, and xylene is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less. In addition, it is more preferred that the total content ratio of benzene and toluene is the above content ratio.

[0349] When the photosensitive composition of the present invention has negative photosensitivity, the photosensitive composition of the present invention preferably satisfies the condition (γ) from the viewpoint of suppressing the residue after development. In addition, when the photosensitive composition of the present invention has negative photosensitivity and contains the (C1) photopolymerization initiator and the (B) compound, the photosensitive composition of the present invention preferably satisfies the condition (γ) from the viewpoint of suppressing the residue after development.

[0350] It is believed that the specific aromatic compound can stabilize the active free radicals or active species in cationic polymerization or anionic polymerization by interacting with the active free radicals through the π electrons on the aromatic ring, thereby obtaining the effect of suppressing the residue after development. In particular, it is inferred that the specific aromatic compound captures the active free radicals derived from the (C1) photopolymerization initiator and the (B) compound, and the effect of suppressing the residue after development brought about by the free radical polymerization control during exposure becomes significant.

[0351] From the viewpoint of suppressing residue after development, improving mechanical properties when heated at low temperature, and improving migration resistance, the photosensitive composition of the present invention preferably has the condition (β) as the following condition (β2) and satisfies the condition (α) and / or the following condition (β2).

[0352] (β2) further contains one or more selected from the group consisting of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (2y):

[0353] (2y) The total content of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0354] The preferred range of the total content of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is also the same as the content of the specific anion.

[0355] From the viewpoint of suppressing residue after development, improving mechanical properties when heated at low temperature, and improving migration resistance, the photosensitive composition of the present invention preferably has the following specific substituent a in which the sulfonic acid, the phosphoric acid, the phosphonic acid, the phosphonic acid ester, the phosphite, the phosphinic acid, and the phosphite (hereinafter referred to as "organic acid containing phosphorus element") have:

[0356] The carboxylic acid containing fluorine element has the following specific substituent b,

[0357] The condition (α) is the following condition (α2), and the following condition (α2) and / or the condition (β) are satisfied, and more preferably the following condition (α2) is satisfied.

[0358] (α2) further contains one or more selected from the group consisting of a sulfonic acid having the following specific substituent a, an organic acid containing a phosphorus element having the following specific substituent a, and a carboxylic acid containing a fluorine element having the following specific substituent b, and satisfies the following condition (1y):

[0359] Specific substituent a: one or more selected from the group consisting of a monovalent aliphatic group to a divalent aliphatic group having 1 to 18 carbon atoms, a monovalent alicyclic group to a divalent alicyclic group having 4 to 18 carbon atoms, a monovalent aromatic group to a divalent aromatic group having 6 to 15 carbon atoms, a monovalent fluorinated aliphatic group to a divalent fluorinated aliphatic group having 1 to 18 carbon atoms, a monovalent fluorinated alicyclic group to a divalent fluorinated alicyclic group having 4 to 18 carbon atoms, and a monovalent fluorinated aromatic group to a divalent fluorinated aromatic group having 6 to 15 carbon atoms

[0360] Specific substituent b: one or more selected from the group consisting of monovalent fluorinated aliphatic groups to divalent fluorinated aliphatic groups having 1 to 18 carbon atoms, monovalent fluorinated alicyclic groups to divalent fluorinated alicyclic groups having 4 to 18 carbon atoms, and monovalent fluorinated aromatic groups to divalent fluorinated aromatic groups having 6 to 15 carbon atoms

[0361] (1y) The total content of the sulfonic acid having the specific substituent a, the organic acid containing phosphorus having the specific substituent a, and the carboxylic acid containing fluorine having the specific substituent b in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0362] The preferred range of the total content of the sulfonic acid having the specific substituent a, the organic acid containing the phosphorus element having the specific substituent a, and the carboxylic acid containing the fluorine element having the specific substituent b in the total solid content of the photosensitive composition is also the same as the content of the specific organic acid.

[0363] From the viewpoint of suppressing residue after development, improving mechanical properties when heated at low temperature, and improving migration resistance, the photosensitive composition of the present invention preferably has the condition (α2) as the following condition (α3) and satisfies the following condition (α3):

[0364] The sulfonic acid preferably contains at least one selected from the group consisting of methanesulfonic acid, propanesulfonic acid, cyclohexanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, xylenesulfonic acid, trifluoromethanesulfonic acid, hexafluorocyclohexanesulfonic acid, hexafluorobenzenesulfonic acid, pentafluorotoluenesulfonic acid, tetrafluoroxylenesulfonic acid, trifluoromethylbenzenesulfonic acid, trifluoromethyltoluenesulfonic acid, and trifluoromethylxylenesulfonic acid.

[0365] From the viewpoint of suppressing residue after development, improving mechanical properties when heated at low temperature, and improving migration resistance, the carboxylic acid containing fluorine element preferably contains one or more selected from the group consisting of trifluoroacetic acid, trifluoropropionic acid, hexafluorocyclohexanecarboxylic acid, hexafluorobenzoic acid, and trifluoromethylbenzoic acid.

[0366] (α3) further contains sulfonic acid and / or carboxylic acid containing fluorine element and satisfies the following condition (1z):

[0367] (1z) The total content of the sulfonic acid and the carboxylic acid containing the fluorine element in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

[0368] The preferred range of the total content of the sulfonic acid and the carboxylic acid containing a fluorine element in the total solid content of the photosensitive composition is also the same as the content of the specific organic acid.

[0369] <Content of specific nitrogen-containing compounds>

[0370] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of a cyclic amide compound represented by the general formula (20), an amide compound represented by the general formula (21), a cyclic urea compound represented by the general formula (22), a urea compound represented by the general formula (23), an oxazolidinone compound represented by the general formula (24), and an isoxazolidinone compound represented by the general formula (25), and satisfies the following condition (4).

[0371] (4) The total content of the cyclic amide compound represented by the general formula (20), the amide compound represented by the general formula (21), the cyclic urea compound represented by the general formula (22), the urea compound represented by the general formula (23), the oxazolidinone compound represented by the general formula (24), and the isoxazolidinone compound represented by the general formula (25) (hereinafter referred to as "specific nitrogen-containing compounds") in the total solid content of the photosensitive composition is 0.010% by mass to 5.0% by mass.

[0372] When the (A) binder resin includes the (A1) resin, and the (A1) resin includes one or more selected from the group consisting of the (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, (A1-5) resin, (A1-6) resin, and copolymers containing two or more of these,

[0373] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention more preferably further contains one or more selected from the group consisting of specific nitrogen-containing compounds and satisfies the condition (4).

[0374] [Chemistry 11]

[0375]

[0376] In the general formulas (20) to (25), R 46 ~R 56 R each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms. 130 R represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyalkyl group having 1 to 6 carbon atoms, a hydroxyalkoxy group having 1 to 6 carbon atoms, a hydroxy group, an amino group, a monoalkylamino group having 1 to 6 carbon atoms, or a dialkylamino group having 2 to 12 carbon atoms. 131 ~R 142 Each independently represents an alkyl group having 1 to 6 carbon atoms. α, β, and γ each independently represent an integer of 0 to 6. a, b, c, e, f, g, h, i, j, k, l, and m each independently represent an integer of 0 to 2. When α is 0, a is 0. When β is 0, b is 0. When γ is 0, c is 0. The substituents and structures may have heteroatoms and may be unsubstituted or substituted.

[0377] Examples of the specific nitrogen-containing compound include N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, N-butyl-2-pyrrolidone, N-cyclohexyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, N,N-dimethylformamide, N,N-diethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, N,N-dimethylisobutylamide, N,N-dimethyl-3-methoxypropionamide, N,N-dimethyl-3-butoxypropionamide, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, 1,1,3,3-tetramethylurea, and 1,1,3,3-tetraethylurea.

[0378] The total content of the specific nitrogen-containing compound in the total solid content of the photosensitive composition is preferably 0.030 mass % or more, more preferably 0.050 mass % or more, further preferably 0.070 mass % or more, and particularly preferably 0.10 mass % or more. On the other hand, the total content of the specific nitrogen-containing compound is preferably 4.0 mass % or less, more preferably 3.5 mass % or less, and further preferably 3.0 mass % or less. Further, from the viewpoint of improving migration resistance, it is preferably 2.5 mass % or less, more preferably 2.0 mass % or less, further preferably 1.5 mass % or less, further more preferably 1.0 mass % or less, particularly preferably 0.70 mass % or less, and most preferably 0.50 mass % or less.

[0379] It is inferred that the specific nitrogen-containing compound can suppress ion migration or electromigration and improve migration resistance because the nitrogen-containing structure having non-covalent electron pairs captures metal impurities or ion impurities that adversely affect electrical insulation.

[0380] <Content of specific metal elements>

[0381] From the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of a component containing a sodium element, a component containing a potassium element, a component containing a magnesium element, a component containing a calcium element, a component containing an iron element, a component containing a copper element, and a component containing a chromium element (hereinafter referred to as "a component containing a specific metal element"), and satisfies the following condition (5).

[0382] (5) The total content of sodium, potassium, magnesium, calcium, iron, copper and chromium (hereinafter referred to as "specific metal elements") in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0383] When the photosensitive composition of the present invention contains one or more selected from the group consisting of specific nitrogen-containing compounds and satisfies the condition (4),

[0384] From the viewpoint of improving mechanical properties when heated at low temperatures and improving migration resistance, the photosensitive composition of the present invention more preferably further contains one or more selected from the group consisting of components containing specific metal elements and satisfies the condition (5).

[0385] The component containing the specific metal element is preferably a halide, oxide, nitride, hydroxide, sulfide, carbide, oxynitride, carboxylate, phosphate, carbonate, sulfate, nitrate, or metasilicate of the specific metal element.

[0386] The total content of the specific metal element in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, and further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific metal element is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Furthermore, from the perspective of improving mechanical properties when heated at low temperatures and improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, and further preferably 10 mass ppm or less, and further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0387] It is inferred that the specific metal element captures metal impurities or ionic impurities that have a negative impact on electrical insulation through the positive charge of the metal element, thereby suppressing ion migration or electromigration and improving migration resistance. It is inferred that in the photosensitive composition of the present invention, a metal complex is formed by intentionally containing a trace amount of a specific metal element in the presence of a specific nitrogen-containing compound. It is believed that the formed metal complex functions as a catalyst for promoting cross-linking reactions on aromatic rings in resins with aromatic rings such as polyimide, polybenzoxazole, and these precursors, or cross-linking reactions in resins with silanol groups such as polysiloxane. As a result, since the cross-linking reaction or the ring-closure reaction is efficiently carried out, it is believed that excellent mechanical properties are also exerted when heated at low temperatures. In addition, it is inferred that the formed metal complex efficiently captures metal impurities or ionic impurities that have a negative impact on electrical insulation through the positive charge of the metal element or the nitrogen-containing structure, thereby improving migration resistance.

[0388] <Content of specific carboxylic acid>

[0389] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of acetic acid, propionic acid, cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, and trimethylbenzoic acid, and satisfies the following condition (6), and / or

[0390] It further contains an aldoxime compound and / or a ketoxime compound described below, and satisfies the following condition (7) described below.

[0391] (6) The total content of acetic acid, propionic acid, cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, and trimethylbenzoic acid (hereinafter referred to as "specific carboxylic acids") in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0392] As described above, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of specific carboxylic acids and satisfies the condition (6). In addition, when the (C) photosensitive agent contains the (C1-1) oxime ester compound and / or the (C1-2) phosphine oxide compound,

[0393] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention more preferably further contains one or more selected from the group consisting of specific carboxylic acids and satisfies the condition (6).

[0394] The total content of the specific carboxylic acid in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific carboxylic acid is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0395] It is believed that the specific carboxylic acid captures metal impurities or ionic impurities that have an adverse effect on electrical insulation through the acidity or negative charge of the carboxyl group. In addition, it is inferred that since the specific carboxylic acid captures moisture in the cured product, ion migration or electromigration can be suppressed, thereby improving migration resistance. In addition, it is believed that in the photosensitive composition of the present invention, in the presence of the (C1-1) oxime ester compound and / or the (C1-2) phosphine oxide compound, the content of the specific carboxylic acid is controlled to a specific range, thereby controlling the polarization structure or charge balance in the cured product. Therefore, it is inferred that since metal impurities or ionic impurities that have an adverse effect on electrical insulation are efficiently captured, migration resistance is improved. When the photosensitive composition of the present invention contains the (C1-1) oxime ester compound, this effect is more significant.

[0396] <Content of specific oxime compound>

[0397] As described above, from the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains an aldoxime compound and / or a ketoxime compound and satisfies the following condition (7).

[0398] (7) The total content of the aldoxime compound and the ketoxime compound (hereinafter referred to as "specific oxime compound") in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0399] When the (C) photosensitizer contains the (C1-1) oxime ester compound and / or the (C1-2) phosphine oxide compound,

[0400] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention more preferably further contains an aldoxime compound and / or a ketoxime compound and satisfies the condition (7).

[0401] The total content of the specific oxime compound in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific oxime compound is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Further from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0402] It is believed that the specific oxime compound captures metal impurities or ionic impurities that have an adverse effect on electrical insulation through the acidity or negative charge of the oxime group. In addition, it is inferred that since the specific oxime compound captures moisture in the cured product, ion migration or electromigration can be suppressed, and migration resistance can be improved. In addition, it is believed that in the photosensitive composition of the present invention, in the presence of the (C1-1) oxime ester compound and / or the (C1-2) phosphine oxide compound, the content of the specific oxime compound is controlled to a specific range, thereby controlling the polarization structure or charge balance in the cured product. Therefore, it is inferred that since metal impurities or ionic impurities that have an adverse effect on electrical insulation are efficiently captured, migration resistance is improved. In the case where the photosensitive composition of the present invention contains the (C1-1) oxime ester compound, this effect is more significant.

[0403] <Contents of chlorine, bromine, and sulfur>

[0404] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of a component containing a chlorine element, a component containing a bromine element, and a component containing a sulfur element, and satisfies the following conditions (8) and / or (9), and / or

[0405] It also contains water described later and satisfies the following condition (10) described later.

[0406] (8) The total content of chlorine and bromine in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0407] (9) The content of sulfur element in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

[0408] As described above, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of a component containing a chlorine element, a component containing a bromine element, and a component containing a sulfur element, and satisfies the conditions of (8) and / or (9). In addition, when the photosensitive composition of the present invention contains one or more selected from the group consisting of specific carboxylic acids and satisfies the condition of (6), or

[0409] When the photosensitive composition of the present invention contains one or more selected from the group consisting of specific oxime compounds and satisfies the condition (7),

[0410] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention more preferably further contains one or more selected from the group consisting of a component containing a chlorine element, a component containing a bromine element, and a component containing a sulfur element, and satisfies the conditions of (8) and / or (9).

[0411] The component containing chlorine and the component containing bromine are preferably chlorinated alkyl compounds, chlorinated cycloalkyl compounds, chlorinated aryl compounds, brominated alkyl compounds, brominated cycloalkyl compounds, or brominated aryl compounds. The component containing sulfur is preferably a thiol compound, a sulfide compound, a disulfide compound, a sulfoxide compound, a sulfone compound, a sultone compound, or a thiophene compound.

[0412] The total content of chlorine and bromine in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of chlorine and bromine is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0413] The content of sulfur in the total solid content of the photosensitive composition is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the content of sulfur is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0414] It is inferred that the chlorine element, bromine element, and sulfur element capture metal impurities or ionic impurities that have a negative effect on electrical insulation through non-covalent electron pairs or empty atomic orbitals, i.e., 3d orbitals, thereby suppressing ion migration or electromigration and improving migration resistance. In addition, it is believed that in the photosensitive composition of the present invention, in the presence of a trace amount of a specific carboxylic acid and / or a trace amount of a specific oxime compound, a trace amount of these elements is intentionally contained, thereby controlling the polarization structure or charge balance in the hardened material. In addition, by containing a trace amount of these elements, the storage stability of the (C1-1) oxime ester compound and / or (C1-2) phosphine oxide compound is improved, so the content of the specific carboxylic acid and the content of the specific oxime compound are controlled, which is preferred in terms of the above aspect. It is inferred that through these effects, metal impurities or ionic impurities that have a negative effect on electrical insulation are efficiently captured, thereby improving migration resistance.

[0415] As an example, when the total content of the specific organic acid in the total solid content of the photosensitive composition is 100 mass ppm and the content of elemental sulfur in the total solid content of the photosensitive composition is 100 mass ppm, the conditions (1x) and (9) are satisfied.

[0416] As another example, when the total content of the specific organic acid in the total solid content of the photosensitive composition is 600 mass ppm and the content of elemental sulfur in the total solid content of the photosensitive composition is 600 mass ppm, the condition (1x) is satisfied.

[0417] As another example, when the total content of the specific organic acid in the total solid content of the photosensitive composition is 100 mass ppm and the content of elemental sulfur in the total solid content of the photosensitive composition is 50 mass ppm, the conditions (1x) and (9) are satisfied.

[0418] <Water content>

[0419] As described above, from the viewpoint of improving migration resistance, the photosensitive composition of the present invention preferably further contains water and satisfies the following condition (10).

[0420] (10) The content of water in the photosensitive composition is 0.010% by mass to 3.0% by mass.

[0421] When the photosensitive composition of the present invention contains one or more selected from the group consisting of specific carboxylic acids and satisfies the condition (6), or

[0422] When the photosensitive composition of the present invention contains one or more selected from the group consisting of specific oxime compounds and satisfies the condition (7),

[0423] From the viewpoint of improving migration resistance, the photosensitive composition of the present invention more preferably further contains water and satisfies the condition (10).

[0424] (10) The content of water in the photosensitive composition is 0.010% by mass to 3.0% by mass.

[0425] The content of water in the photosensitive composition is preferably 0.030 mass % or more, more preferably 0.050 mass % or more, further preferably 0.070 mass % or more, particularly preferably 0.10 mass % or more. On the other hand, the content of water is preferably 2.5 mass % or less, more preferably 2.2 mass % or less, and further preferably 2.0 mass % or less. Further, from the viewpoint of improving migration resistance, it is preferably 1.7 mass % or less, more preferably 1.5 mass % or less, further preferably 1.2 mass % or less, further more preferably 1.0 mass % or less, particularly preferably 0.70 mass % or less, and most preferably 0.50 mass % or less.

[0426] It is inferred that the water captures metal impurities or ionic impurities that have a negative effect on electrical insulation through the interaction of the dipole moment or hydrogen bond of the water molecule, so that ion migration or electromigration can be suppressed and migration resistance can be improved. In addition, it is believed that in the photosensitive composition of the present invention, in the presence of a trace of specific carboxylic acid and / or a trace of specific oxime compound, the content of water is set to a specific range, thereby controlling the polarization structure or charge balance in the hardened material. In addition, by setting the content of water to a specific range, the storage stability of the (C1-1) oxime ester compound and / or (C1-2) phosphine oxide compound is improved, so the content of the specific carboxylic acid and the content of the specific oxime compound are controlled, which is preferred in terms of the above aspect. It is inferred that through these effects, metal impurities or ionic impurities that have a negative effect on electrical insulation are efficiently captured, so migration resistance is improved.

[0427] <Content of fluorine>

[0428] From the viewpoint of suppressing the residue after development and improving the migration resistance, the photosensitive composition of the present invention preferably further satisfies the following condition (1α).

[0429] (1α) The content of fluorine element in the total solid content of the photosensitive composition is 1,000 mass ppm or less.

[0430] From the perspective of the effect of the invention, the content of fluorine in the total solid content of the photosensitive composition is preferably 0 mass ppm or more, more preferably 0.010 mass ppm or more, further preferably 0.030 mass ppm or more, further more preferably 0.050 mass ppm or more, particularly preferably 0.070 mass ppm or more, and most preferably 0.10 mass ppm or more. On the other hand, from the perspective of the effect of the invention, the content of fluorine is preferably 1,000 mass ppm or less, more preferably 500 mass ppm or less, further preferably 300 mass ppm or less, and particularly preferably 100 mass ppm or less. Furthermore, the content of fluorine is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5 mass ppm or less, particularly preferably 3 mass ppm or less, and most preferably 1 mass ppm or less.

[0431] In addition, when the photosensitive composition of the present invention satisfies the condition (α) and the specific organic acid contains a fluorine atom in the structure, it is preferred that the condition (1α) is further satisfied from the viewpoint of the effect of the present invention. In addition, when the photosensitive composition of the present invention satisfies the condition (β) and the compound containing the specific anion contains a fluoride ion, it is preferred that the condition (1α) is further satisfied from the viewpoint of the effect of the present invention.

[0432] The content of fluorine in the total solid content of the photosensitive composition may also be 0 mass ppm. When the content of fluorine in the total solid content of the photosensitive composition exceeds 0 mass ppm, the photosensitive composition of the present invention preferably has a fluorine atom in the structure of (A) the binder resin, (C) the photosensitizer, (B) the compound, or (F) the crosslinking agent, or further contains a component containing fluorine.

[0433] The component containing fluorine is preferably a phenol compound, a fluorinated alkyl compound, a fluorinated cycloalkyl compound, or a fluorinated aryl compound having a substituent containing a fluorinated alkyl group. In addition, the component containing fluorine is a compound different from the specific organic acid and the compound containing the specific anion.

[0434] It is inferred that by setting the content of the compound containing fluorine atoms or the component containing fluorine element in the structure of the photosensitive composition to below a specific value, the content of the fluorine element in these components or the anion containing fluorine element derived from these components is below a specific value, so the protons in the photosensitive composition are locally activated by the interaction of the hydrogen bonds of the components in the photosensitive composition. Therefore, it is believed that the effect of suppressing the residue after development becomes significant by the dissolution promotion effect relative to the developer. In addition, it is believed that by intentionally setting the content of the component to below a specific value, the polarization structure or charge balance in the hardened material can be controlled. As a result, it is inferred that the migration resistance is improved by suppressing the ion migration or electromigration caused by the metal impurities or ionic impurities that have an adverse effect on the electrical insulation.

[0435] <Photosensitive composition coating film and photosensitive composition film of the present invention>

[0436] The photosensitive composition film of the present invention is a film in a semi-cured state (B stage) formed by forming the photosensitive composition of the present invention. The so-called semi-cured state means that a cross-linked structure is not formed, or a cross-linked structure is formed by a partial reaction but the film has fluidity, or the above state. For example, the state in which the coating film is dried under reduced pressure and the solvent is distilled off after being applied to a substrate, or the state in which the coating film is heated at 40°C to 150°C to dry it, refers to a state soluble in an alkaline solution or an organic solvent. The photosensitive composition film of the present invention preferably has a photosensitive composition film and a support formed by forming the photosensitive composition of the present invention. From the viewpoint of operability, it is preferred to adopt such a structure. The photosensitive composition film has positive or negative photosensitivity. The photosensitive composition film is also preferably capable of forming a self-supporting film using a single film. The photosensitive composition film is preferably adhesive, and it is also preferred to join multiple components. The term "capable of forming a self-supporting film from a single film" means that a film having a width of 1.5 cm or more, a length of 5.0 cm or more, and a thickness of 5.0 μm or more can be formed without a support. That is, the photosensitive composition film is preferably a photosensitive composition film that can form a self-supporting film from a single film.

[0437] The photosensitive composition film of the present invention has positive or negative photosensitivity, so after patterned exposure, it can form a positive or negative pattern by developing with an alkaline developer or an organic solvent. The photosensitive composition film of the present invention is preferably used for forming a pattern on a substrate having a concave-convex structure, forming a hollow structure, or a dry film resist.

[0438] From the viewpoint of improving adhesion to the photosensitive film of the present invention, flexibility, and operability, the support is preferably a flexible substrate. The flexible substrate is preferably a polyimide substrate, a polyphenylene sulfide substrate, a silicone substrate, an acrylic resin substrate, an epoxy resin substrate, a polyethylene terephthalate substrate, a polybutylene terephthalate substrate, a polyethylene naphthalate substrate, or a polycarbonate substrate. The support may also be a rigid substrate. Examples of rigid substrates include glass substrates, quartz substrates, crystal substrates, or sapphire substrates. From the viewpoint of improving adhesion to the film and improving peelability, the surface of the photosensitive film side of the present invention in the support may also be surface treated with a silane coupling agent or the like. From the viewpoint of operability, the thickness of the support is preferably 10 μm to 200 μm.

[0439] <Cured product of the photosensitive composition of the present invention>

[0440] The hardened material of the present invention is a hardened material formed by hardening the photosensitive composition of the present invention. Hardening refers to the state in which the fluidity of the film disappears by forming a cross-linked structure through reaction, or the above-mentioned state. The reaction is not particularly limited to a reaction performed by heating, a reaction performed by irradiation with energy rays, etc., but preferably a reaction performed by heating. The state in which the fluidity of the film disappears by forming a cross-linked structure through heating is called thermal hardening.

[0441] As heating conditions, for example, heating at 150°C to 500°C for 5.0 minutes to 300 minutes. As heating methods, for example, heating methods using an oven, a hot plate, infrared rays, a flash annealing device, or a laser annealing device can be cited. As processing environments, for example, there can be listed: in air, oxygen, nitrogen, helium, neon, argon, krypton, or xenon environments; in a gas environment containing less than 1.0 mass ppm to 10,000 mass ppm (0.00010 mass% to 1.0 mass%) of oxygen; in a gas environment containing more than 10,000 mass ppm (1.0 mass%) of oxygen; or in a vacuum.

[0442] The hardened material of the present invention may also be a hardened material obtained by hardening the photosensitive film of the present invention. Hardening means that the fluidity of the film disappears or the above-mentioned state after a cross-linked structure is formed by reaction. The reaction here is as described. In addition, the examples and preferred descriptions of the heating conditions are as described.

[0443] From the viewpoint of improving light-shielding properties and improving reliability, the optical density of the cured product of the present invention at the wavelength of visible light (380nm to 780nm) per 1μm of film thickness is preferably 0.20 or more, more preferably 0.30 or more, and further preferably 0.50 or more, and particularly preferably 1.0 or more. On the other hand, from the viewpoint of improving sensitivity during exposure and improving reliability, the optical density is preferably 3.0 or less, more preferably 2.0 or less, more preferably 1.7 or less, and further preferably 1.5 or less. In addition, the optical density is preferably the optical density in the cured product formed by heat-curing the composition. By having the optical density in the range, the incident external light can be shielded, so the effect of suppressing external light reflection becomes significant. In addition, since the light degradation of the cured product itself or the layer located inside it can be suppressed, the effect of improving reliability becomes significant.

[0444] From the viewpoint of improving reliability, the dielectric loss tangent of the hardened material of the present invention at a frequency of 1 GHz is preferably more than 0.00010, more preferably more than 0.00030, and further preferably more than 0.00050. On the other hand, from the viewpoint of low transmission loss, the dielectric loss tangent is preferably less than 0.0100, more preferably less than 0.0050, and further preferably less than 0.0030, and particularly preferably less than 0.0010. The preferred range of the dielectric loss tangent of the hardened material of the present invention at a frequency of 10 GHz, 30 GHz, and 70 GHz is also respectively the same as described. In addition, the dielectric loss tangent is a value obtained by measuring the resonator method using a split column dielectric resonator (Split Post Dielectric Resonator, SPDR).

[0445] It is preferred that the dielectric constant of the cured product of the present invention at a frequency of 1 GHz is 3.5 or less, and / or the water absorption of the cured product of the present invention is 1.5 mass % or less.

[0446] The dielectric constant is preferably 2.0 or more, more preferably 2.3 or more, and even more preferably 2.5 or more. On the other hand, the dielectric constant is preferably 3.5 or less, more preferably 3.0 or less, even more preferably 2.9 or less, and particularly preferably 2.7 or less. The preferred ranges of the dielectric constants of the cured product of the present invention at frequencies of 10 GHz, 30 GHz, and 70 GHz are also the same as described above.

[0447] The water absorption is preferably 0.10% by mass or more, more preferably 0.30% by mass or more. On the other hand, the water absorption is preferably 2.0% by mass or less, more preferably 1.5% by mass or less, further preferably 1.0% by mass or less, further more preferably 0.70% by mass or less, and particularly preferably 0.50% by mass or less.

[0448] <Components and articles including hardened materials>

[0449] The element of the present invention includes the hardened material of the present invention. In addition, the article of the present invention includes the hardened material of the present invention. As an article, for example, electronic parts, electronic devices, mobile bodies, buildings, or windows can be listed. As electronic parts, for example, semiconductor devices, antennas, display devices, metal-clad laminates, wiring substrates, semiconductor packages, active parts including semiconductor devices, or passive parts including semiconductor devices can be listed. As semiconductor devices, for example, transistors, diodes, integrated circuits, processors, or memories can be listed. As passive parts, for example, resistors, capacitors, or inductors can be listed. As electronic devices, for example, industrial devices, medical devices, or building devices can be listed. As mobile bodies, for example, vehicles, railways, airplanes, or heavy equipment can be listed. As buildings, for example, houses, shops, offices, buildings, or factories can be listed. As windows, for example, electronic device windows, mobile body windows, or building windows can be listed.

[0450] The photosensitive composition of the present invention is preferably used to form an electronic component. In addition, the photosensitive composition of the present invention is also preferably used to form one or more selected from the group consisting of a semiconductor device, an antenna, a display device, and a metal-clad laminate.

[0451] As a semiconductor device, for example, a semiconductor device having a fan-out chip-level packaging structure, a fan-out panel-level packaging structure, or an antenna-in-package structure can be listed. As an antenna, for example, a microstrip line antenna, a strip line antenna, a coplanar line antenna, a coplanar line with grounding (conductor back coplanar (Conductor Back Coplanar; CBC)) antenna, a substrate integrated waveguide (Substrate Integrated Waveguide; SIW) antenna, a post wall waveguide (Post Wall Waveguide; PWW) antenna, a parallel dual-wire line (coplanar strip (Coplanar Strip; CPS)) antenna, or a slot line antenna can be listed. As a display device, for example, an organic EL display, a quantum dot display, a micro light emitting diode (light emitting diode) (hereinafter referred to as "LED") display, a micro LED display, or a liquid crystal display. As a metal-clad laminate, for example, a printed circuit board can be listed.

[0452] The electronic component of the present invention includes the cured product of the present invention. The cured product of the present invention can also have excellent mechanical properties and high migration resistance when heated at low temperatures. Therefore, the photosensitive composition of the present invention is preferably used to form an insulating layer of metal wiring in an electronic component, a protective layer of metal wiring, or an interlayer insulating layer of metal wiring.

[0453] The semiconductor device, antenna, display device, and metal-clad laminate of the present invention include the cured product of the present invention. For the same reasons as above, the photosensitive composition of the present invention is also preferably used to form an interlayer insulating layer for redistribution in a semiconductor device, and is also preferably used to form an insulating layer for metal wiring in an antenna, a protective layer for metal wiring, or an interlayer insulating layer between metal wiring and ground wiring, and is also preferably used to form a pixel segmentation layer, a flattening layer of TFT, a protective layer of TFT, an interlayer insulating layer of TFT, or a gate insulating layer in an organic EL display, a quantum dot display, or a micro-LED display, and is also preferably used to form an insulating layer for metal wiring, a protective layer for metal wiring, or a solder resist layer for metal wiring in a metal-clad laminate.

[0454] An application example of the cured product of the present invention to a semiconductor device having bumps using the cured product of the present invention will be described with reference to the drawings. Figure 1 It is a schematic cross-sectional view showing an enlarged cross section of a pad portion of a semiconductor device having a bump. On a Si wafer 1, a passivation layer 3 is formed on an Al pad 2 for input and output, and a through hole is formed in the passivation layer 3. On the passivation layer 3, a hardened material of the present invention, i.e., an insulating layer 4, is formed by patterning, and a metal layer 5 of Cr or Ti or the like is formed to be connected to the Al pad 2, and a metal wiring 6 of Al or Cu or the like is formed by electrolytic plating or the like. With respect to the metal layer 5, the periphery of the solder bump 10 is etched to insulate the pads. A barrier metal layer 8 and a solder bump 10 are formed on the insulated pad. The insulating layer 7 is a hardened material of a patterned photosensitive composition, preferably a hardened material of the present invention. The photosensitive composition forming the insulating layer 7 can be patterned as a thick film in the formation of the scribe line 9. When the insulating layer 4 and / or the insulating layer 7 is a cured product of the present invention, the mechanical properties are excellent when heated at low temperatures, so the warping of the wafer can be suppressed, and the accuracy of the exposure or wafer handling process can be significantly improved. In addition, the stress of the sealing resin during semiconductor mounting can be relieved, so the damage of the Low-k layer can be suppressed, and the reliability of the semiconductor device can be significantly improved.

[0455] <Hollow structure>

[0456] The hollow structure of the present invention includes the cured product of the present invention. The electronic component of the present invention preferably has the hollow structure of the present invention. The hollow structure of the present invention has a hollow structure support material and a hollow structure roof material. The hollow structure support material and the hollow structure roof material are preferably the cured product of the present invention. From the viewpoint of improving heat resistance and improving reliability, the hollow structure support material and the hollow structure roof material are preferably a resin containing the polyimide system. The film thickness of the hollow structure support material is preferably 5μm to 20μm. The film thickness of the hollow structure roof material is preferably 10μm to 50μm.

[0457] The photosensitive composition of the present invention is preferably used to form a hollow structure, and more preferably used to form a hollow structure support material and / or a hollow structure roof material. The photosensitive film of the present invention is more preferably used to form a hollow structure, and further preferably to form a hollow structure support material and / or a hollow structure roof material, and particularly preferably to form a hollow structure roof material. As electronic parts having a hollow structure, for example, microelectromechanical systems (MEMS) and the like can be listed. As MEMS, for example, sensors, noise filters, surface acoustic wave (SAW) filters, or bulk acoustic wave (BAW) filters can be listed.

[0458] <Electronic components>

[0459] The electronic component of the present invention is described below. However, the present invention is not limited to the following embodiments, and various modifications can be made within the scope of achieving the object of the invention and not departing from the gist of the invention.

[0460] The electronic component of the present invention has the structure of

[20] . By making the structure, the present invention can provide an electronic component with excellent migration resistance. It is believed that this is achieved by intentionally containing a trace amount of the specific aromatic compound, specific anion, or specific organic acid in the cured photosensitive composition to control the polarization structure or charge balance in the cured photosensitive composition. In addition, it is believed that aromatic rings in resins such as polyimide, polybenzoxazole, and their precursors, or silanol groups in resins such as polysiloxane also contribute to the control of polarization structure or charge balance. From this, it is inferred that by suppressing ion migration or electromigration caused by metal impurities or ionic impurities that have an adverse effect on electrical insulation, an excellent migration resistance effect is exerted. In addition, it is inferred that by suppressing the migration of metal in the wiring or suppressing cohesion, the effect of high reliability in electronic components, semiconductor devices, display devices, and metal-clad laminates is exerted.

[0461] <Resins and compounds in cured products>

[0462] The electronic component of the present invention includes a cured product. The cured product in the electronic component of the present invention is preferably a cured product of a photosensitive composition, more preferably a cured product of a photosensitive composition containing a binder resin and a photosensitizer, and further preferably a cured product of a photosensitive composition containing a binder resin and a photosensitizer, and further containing a free radical polymerizable compound and / or a crosslinking agent. The binder resin is preferably the (A) binder resin. The photosensitive agent is preferably the (C) photosensitive agent, more preferably the (C1) photopolymerization initiator. The free radical polymerizable compound is preferably the (B) compound. The crosslinking agent is preferably the (F) crosslinking agent. Examples and preferred descriptions of the (A) binder resin, (C) photosensitive agent, (B) compound, and (F) crosslinking agent are as described.

[0463] The cured product in the electronic component of the present invention is also preferably a cured product of a photosensitive composition further containing one or more selected from the group consisting of a colorant, a dispersant, and inorganic particles. The colorant is preferably the colorant (D). The dispersant is preferably the dispersant (E). The inorganic particles are preferably the inorganic particles (G). Examples and preferred descriptions of the colorant (D), the dispersant (E), and the inorganic particles (G) are as described above.

[0464] The cured product of the electronic component of the present invention contains the following (XA1) resin and / or (XA2) resin. In addition, the cured product of the electronic component of the present invention preferably further contains the following (XA3) resin.

[0465] (XA1) Resin: a resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin

[0466] (XA2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin

[0467] (XA3) Resin: a resin having a free radical polymerizable group.

[0468] The (XA1) resin in the cured product is preferably a resin having a structure derived from the (A1) resin. The (XA2) resin in the cured product is preferably a resin having a structure derived from the (A2) resin. The (XA3) resin in the cured product is preferably a resin having a structure derived from the (A3) resin. Examples and preferred descriptions of the (XA1) resin, (XA2) resin, and (XA3) resin in the cured product are the same as the examples and preferred descriptions of the (A1) resin, (A2) resin, and (A3) resin.

[0469] From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention preferably contains the resin (A1), more preferably contains the resin (A1) and the resin (A2), and preferably further contains the resin (A3). From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention further preferably contains the resin (A1), the resin (A2), and the resin (A3).

[0470] The resin (A1) is presumed to suppress ion migration or electromigration and improve migration resistance because the imide structure, amide structure, oxazole structure or siloxane structure in the structural unit of the main chain of the resin captures metal impurities or ionic impurities that adversely affect electrical insulation.

[0471] The resin (XA1) preferably has one or more structural units selected from the group consisting of the general formula (1), the general formula (2), the general formula (3), the general formula (4), the general formula (5), the general formula (6), the general formula (9) and the general formula (10). The resin (XA2) preferably has one or more structural units selected from the group consisting of the general formula (31), the general formula (32), the general formula (33), the general formula (34), the general formula (35), the general formula (36), the general formula (38), the general formula (39) and the general formula (40). It is also preferred that a part of the phenolic hydroxyl groups contained in these resins react with other resins or compounds to form a crosslinked structure.

[0472] <Content of specific aromatic compounds, specific anions, and specific organic acids>

[0473] The cured product in the electronic component of the present invention satisfies one or more selected from the group consisting of the following conditions (Xα), (Xβ), and (Xγ). The cured product in the electronic component of the present invention preferably satisfies the following condition (Xα).

[0474] (Xα) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (X1x):

[0475] (X1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the cured product is 0.010 mass ppm to 1,000 mass ppm

[0476] (Xβ) further contains one or more selected from the group consisting of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (X2x):

[0477] (X2x) The total content of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the hardened material is 0.010 mass ppm to 1,000 mass ppm

[0478] (Xγ) further contains one or more selected from the group consisting of benzene, toluene, xylene, and naphthalene, and satisfies the following condition (X3):

[0479] (X3) The total content of benzene, toluene, xylene, and naphthalene in the cured product is 0.010 to 1,000 ppm by mass.

[0480] When the condition (Xβ) is satisfied, the cured product in the electronic component of the present invention preferably further contains a compound containing a specific anion. When the cured product in the electronic component of the present invention contains a compound containing a specific anion, it preferably further contains ammonium ions, primary ammonium ions, secondary ammonium ions, tertiary ammonium ions, or quaternary ammonium ions as cation species.

[0481] The phosphate, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, and phosphite ester are preferably phosphate monoester, phosphate diester, phosphonic acid, phosphonic acid monoester, phosphite monoester, phosphite diester, phosphinic acid, or phosphite monoester.

[0482] The specific organic acid preferably has one or more selected from the group consisting of a monovalent aliphatic group to a divalent aliphatic group having 1 to 18 carbon atoms, a monovalent alicyclic group to a divalent alicyclic group having 4 to 18 carbon atoms, a monovalent aromatic group to a divalent aromatic group having 6 to 15 carbon atoms, a monovalent fluorinated aliphatic group to a divalent fluorinated aliphatic group having 1 to 18 carbon atoms, a monovalent fluorinated alicyclic group to a divalent fluorinated alicyclic group having 4 to 18 carbon atoms, and a monovalent fluorinated aromatic group to a divalent fluorinated aromatic group having 6 to 15 carbon atoms.

[0483] From the viewpoint of improving the migration resistance, the cured product in the electronic component of the present invention preferably satisfies two or more selected from the group consisting of the condition (Xα), the condition (Xβ), and the condition (Xγ). From the viewpoint of improving the migration resistance, the cured product in the electronic component of the present invention more preferably satisfies the condition (Xα) and further satisfies the condition (β) and / or the condition (γ). Furthermore, from the viewpoint of improving the migration resistance, the cured product in the electronic component of the present invention preferably satisfies the condition (Xγ) and satisfies the condition (Xα) and / or the condition (Xβ).

[0484] The total content of the specific aromatic compounds in the cured product is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific aromatic compounds is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0485] The total content of specific anions in the cured product is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of specific anions is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0486] The total content of the specific organic acid in the cured product is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific organic acid is preferably 500 mass ppm or less, more preferably 300 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0487] When the condition (Xα) is satisfied, the cured product in the electronic component of the present invention is preferably a carboxylic acid containing sulfonic acid and / or fluorine, and more preferably a sulfonic acid. The total content ratio of sulfonic acid and / or carboxylic acid containing fluorine in the total of the specific organic acid is preferably 50% by mass or more, and more preferably 60% by mass or more. On the other hand, the total content ratio of sulfonic acid and / or carboxylic acid containing fluorine is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less. In addition, it is more preferred that the content ratio of sulfonic acid is the above content ratio.

[0488] In the case where the condition (Xβ) is satisfied, the hardened material in the electronic component of the present invention preferably contains one or more selected from the group consisting of phosphate ions, phosphite ions, hypophosphite ions, formate ions, and fluoride ions, and more preferably contains one or more selected from the group consisting of phosphate ions, phosphite ions, and hypophosphite ions. The total content ratio of phosphate ions, phosphite ions, hypophosphite ions, formate ions, and fluoride ions in the total of specific anions is preferably 50% by mass or more, and more preferably 60% by mass or more. On the other hand, the total content ratio of phosphate ions, phosphite ions, hypophosphite ions, formate ions, and fluoride ions is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less. In addition, it is more preferred that the total content ratio of phosphate ions, phosphite ions, and hypophosphite ions is the above content ratio.

[0489] When the condition (Xγ) is satisfied, the cured material in the electronic component of the present invention preferably contains one or more selected from the group consisting of benzene, toluene, and xylene, and more preferably contains benzene and / or toluene. The total content ratio of benzene, toluene, and xylene in the total of the specific aromatic compounds is preferably 50% by mass or more, and more preferably 60% by mass or more. On the other hand, the total content ratio of benzene, toluene, and xylene is preferably 100% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less. In addition, it is more preferred that the total content ratio of benzene and toluene is the above content ratio.

[0490] From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention preferably satisfies the condition (Xβ) as the following condition (Xβ2) and satisfies the condition (Xα) and / or the following condition (Xβ2).

[0491] (Xβ2) further contains one or more selected from the group consisting of phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (X2y):

[0492] (X2y) The total content of phosphate ions, phosphite ions, hypophosphite ions, formate ions, and fluoride ions in the cured product is 0.010 to 1,000 ppm by mass.

[0493] The preferred range of the total content of phosphate ions, phosphite ions, hypophosphite ions, formate ions, and fluoride ions in the cured product is also the same as the content of the specific anions.

[0494] From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention preferably has the following specific substituent a:

[0495] The carboxylic acid containing fluorine element has the following specific substituent b,

[0496] The condition (Xα) is the following condition (Xα2), and satisfies the following condition (Xα2) and / or the condition (Xβ), and more preferably satisfies the following condition (Xα2).

[0497] (Xα2) further contains one or more selected from the group consisting of a sulfonic acid having the following specific substituent a, an organic acid containing a phosphorus element having the following specific substituent a, and a carboxylic acid containing a fluorine element having the following specific substituent b, and satisfies the following condition (X1y):

[0498] Specific substituent a: one or more selected from the group consisting of a monovalent aliphatic group to a divalent aliphatic group having 1 to 18 carbon atoms, a monovalent alicyclic group to a divalent alicyclic group having 4 to 18 carbon atoms, a monovalent aromatic group to a divalent aromatic group having 6 to 15 carbon atoms, a monovalent fluorinated aliphatic group to a divalent fluorinated aliphatic group having 1 to 18 carbon atoms, a monovalent fluorinated alicyclic group to a divalent fluorinated alicyclic group having 4 to 18 carbon atoms, and a monovalent fluorinated aromatic group to a divalent fluorinated aromatic group having 6 to 15 carbon atoms

[0499] Specific substituent b: one or more selected from the group consisting of monovalent fluorinated aliphatic groups to divalent fluorinated aliphatic groups having 1 to 18 carbon atoms, monovalent fluorinated alicyclic groups to divalent fluorinated alicyclic groups having 4 to 18 carbon atoms, and monovalent fluorinated aromatic groups to divalent fluorinated aromatic groups having 6 to 15 carbon atoms

[0500] (X1y) The total content of the sulfonic acid having the specific substituent a, the organic acid containing the phosphorus element having the specific substituent a, and the carboxylic acid containing the fluorine element having the specific substituent b in the cured product is 0.010 to 1,000 ppm by mass.

[0501] The preferred range of the total content of the sulfonic acid having the specific substituent a, the organic acid containing phosphorus having the specific substituent a, and the carboxylic acid containing fluorine having the specific substituent b in the cured product is also the same as the content of the specific organic acid.

[0502] From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention preferably satisfies the following condition (Xα3) in addition to the condition (Xα2):

[0503] The sulfonic acid preferably contains at least one selected from the group consisting of methanesulfonic acid, cyclohexanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, xylenesulfonic acid, trifluoromethanesulfonic acid, hexafluorocyclohexanesulfonic acid, hexafluorobenzenesulfonic acid, pentafluorotoluenesulfonic acid, tetrafluoroxylenesulfonic acid, trifluoromethylbenzenesulfonic acid, trifluoromethyltoluenesulfonic acid, and trifluoromethylxylenesulfonic acid.

[0504] From the viewpoint of improving migration resistance, the carboxylic acid containing a fluorine element preferably contains at least one selected from the group consisting of trifluoroacetic acid, trifluoropropionic acid, hexafluorocyclohexanecarboxylic acid, hexafluorobenzoic acid, and trifluoromethylbenzoic acid.

[0505] (Xα3) further contains sulfonic acid and / or carboxylic acid containing fluorine, and satisfies the following condition (X1z):

[0506] The total content of the sulfonic acid and the carboxylic acid containing the fluorine element in the (X1z) compound is 0.010 to 1,000 ppm by mass.

[0507] The preferred range of the total content of the sulfonic acid and the carboxylic acid containing the fluorine element in the cured product is also the same as the content of the specific organic acid.

[0508] <Content of specific nitrogen-containing compounds>

[0509] When the cured product of the electronic component of the present invention contains the resin (XA1),

[0510] From the viewpoint of improving migration resistance, the cured product of the electronic component of the present invention preferably further contains one or more selected from the group consisting of a cyclic amide compound represented by the general formula (20), an amide compound represented by the general formula (21), a cyclic urea compound represented by the general formula (22), a urea compound represented by the general formula (23), an oxazolidinone compound represented by the general formula (24), and an isoxazolidinone compound represented by the general formula (25), and satisfies the following condition (X4). Examples and preferred descriptions of the specific nitrogen-containing compound are as described above.

[0511] (X4) The total content of the cyclic amide compound represented by the general formula (20), the amide compound represented by the general formula (21), the cyclic urea compound represented by the general formula (22), the urea compound represented by the general formula (23), the oxazolidinone compound represented by the general formula (24), and the isoxazolidinone compound represented by the general formula (25) (hereinafter referred to as "specific nitrogen-containing compounds") in the cured product is 0.010 mass % to 5.0 mass %.

[0512] The total content of the specific nitrogen-containing compounds in the hardened material is preferably 0.030 mass % or more, more preferably 0.050 mass % or more, further preferably 0.070 mass % or more, and particularly preferably 0.10 mass % or more. On the other hand, the total content of the specific nitrogen-containing compounds is preferably 4.0 mass % or less, more preferably 3.5 mass % or less, and further preferably 3.0 mass % or less. Further, from the viewpoint of improving migration resistance, it is preferably 2.5 mass % or less, more preferably 2.0 mass % or less, further preferably 1.5 mass % or less, further more preferably 1.0 mass % or less, particularly preferably 0.70 mass % or less, and most preferably 0.50 mass % or less.

[0513] It is inferred that the specific nitrogen-containing compound can suppress ion migration or electromigration and improve migration resistance because the nitrogen-containing structure having non-covalent electron pairs captures metal impurities or ion impurities that adversely affect electrical insulation.

[0514] <Content of specific metal elements>

[0515] When the cured product in the electronic component of the present invention contains one or more selected from the group consisting of specific nitrogen-containing compounds and satisfies the condition (X4),

[0516] From the viewpoint of improving the mechanical properties when heated at low temperatures and improving the migration resistance, the photosensitive composition of the present invention preferably further contains one or more selected from the group consisting of a component containing a sodium element, a component containing a potassium element, a component containing a magnesium element, a component containing a calcium element, a component containing an iron element, a component containing a copper element, and a component containing a chromium element, and satisfies the following condition (X5).

[0517] (X5) The total content of sodium element, potassium element, magnesium element, calcium element, iron element, copper element, and chromium element (hereinafter referred to as "specific metal elements") in the cured product is 0.010 mass ppm to 500 mass ppm.

[0518] The component containing the specific metal element is preferably a halide, oxide, nitride, hydroxide, sulfide, carbide, oxynitride, carboxylate, phosphate, carbonate, sulfate, nitrate, or metasilicate of the specific metal element.

[0519] The total content of the specific metal elements in the hardened material is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the specific metal elements is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0520] It is inferred that the specific metal element captures metal impurities or ionic impurities that adversely affect electrical insulation by the positive charge of the metal element, thereby suppressing ion migration or electromigration and improving migration resistance. It is inferred that in the hardened material of the electronic component of the present invention, a metal complex is formed by intentionally containing a trace amount of the specific metal element in the presence of a specific nitrogen-containing compound. It is inferred that the formed metal complex efficiently captures metal impurities or ionic impurities that adversely affect electrical insulation by the positive charge of the metal element or the nitrogen-containing structure, thereby improving migration resistance.

[0521] <Contents of chlorine, bromine, and sulfur>

[0522] From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention preferably further contains one or more selected from the group consisting of a component containing a chlorine element, a component containing a bromine element, and a component containing a sulfur element, and satisfies the following conditions (X8) and / or (X9).

[0523] (X8) The total content of chlorine and bromine in the cured product is 0.010 ppm by mass to 500 ppm by mass

[0524] (X9) The content of sulfur element in the cured product is 0.010 ppm by mass to 500 ppm by mass.

[0525] The component containing chlorine and the component containing bromine are preferably chlorinated alkyl compounds, chlorinated cycloalkyl compounds, chlorinated aryl compounds, brominated alkyl compounds, brominated cycloalkyl compounds, or brominated aryl compounds. The component containing sulfur is preferably a thiol compound, a sulfide compound, a disulfide compound, a sulfoxide compound, a sulfone compound, a sultone compound, or a thiophene compound.

[0526] The total content of the chlorine element and the bromine element in the cured product is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the total content of the chlorine element and the bromine element is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Furthermore, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0527] The sulfur content in the cured product is preferably 0.030 mass ppm or more, more preferably 0.050 mass ppm or more, further preferably 0.070 mass ppm or more, and particularly preferably 0.10 mass ppm or more. On the other hand, the sulfur content is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, and further preferably 100 mass ppm or less. Further, from the viewpoint of improving migration resistance, it is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5.0 mass ppm or less, particularly preferably 3.0 mass ppm or less, and most preferably 1.0 mass ppm or less.

[0528] It is inferred that the chlorine, bromine, and sulfur elements capture metal impurities or ionic impurities that adversely affect electrical insulation through non-covalent electron pairs or empty atomic orbitals, namely 3d orbitals, thereby suppressing ion migration or electromigration and improving migration resistance.

[0529] <Content of fluorine>

[0530] From the viewpoint of improving migration resistance, the cured product in the electronic component of the present invention preferably satisfies the following condition (X1α).

[0531] (X1α) The content of fluorine element in the cured product is 1,000 mass ppm or less.

[0532] From the viewpoint of the effect of the invention, the content of fluorine in the cured material is preferably 0 mass ppm or more, more preferably 0.010 mass ppm or more, further preferably 0.030 mass ppm or more, further more preferably 0.050 mass ppm or more, particularly preferably 0.070 mass ppm or more, and most preferably 0.10 mass ppm or more. On the other hand, from the viewpoint of the effect of the invention, the content of fluorine is preferably 1,000 mass ppm or less, more preferably 500 mass ppm or less, further preferably 300 mass ppm or less, and particularly preferably 100 mass ppm or less. Furthermore, the content of fluorine is preferably 50 mass ppm or less, more preferably 30 mass ppm or less, further preferably 10 mass ppm or less, further more preferably 5 mass ppm or less, particularly preferably 3 mass ppm or less, and most preferably 1 mass ppm or less.

[0533] Furthermore, when the cured product in the electronic component of the present invention satisfies the condition (Xα) and the specific organic acid contains fluorine atoms in its structure, it is preferred that the cured product further satisfies the condition (X1α) from the viewpoint of the effect of the present invention. Furthermore, when the cured product in the electronic component of the present invention satisfies the condition (Xβ) and the compound containing the specific anion contains fluoride ions, it is preferred that the cured product further satisfies the condition (X1α) from the viewpoint of the effect of the present invention.

[0534] The content of fluorine in the cured product may be 0 mass ppm. When the content of fluorine in the cured product exceeds 0 mass ppm, the cured product in the electronic component of the present invention preferably has a binder resin having fluorine atoms in its structure or further contains a component containing fluorine.

[0535] The component containing fluorine is preferably a phenol compound, a fluorinated alkyl compound, a fluorinated cycloalkyl compound, or a fluorinated aryl compound having a substituent containing a fluorinated alkyl group. In addition, the component containing fluorine is a compound different from the specific organic acid and the compound containing the specific anion.

[0536] It is believed that by intentionally setting the fluorine content in the cured product to a specific value or less, the polarization structure and charge balance in the cured product can be controlled. As a result, it is inferred that the migration resistance is improved by suppressing ion migration or electromigration caused by metal impurities or ion impurities that have a negative effect on electrical insulation.

[0537] <Method for producing hardened product>

[0538] The method for producing a cured product of the present invention comprises the following steps (1) to (4).

[0539] (1) Step of forming a coating film of the photosensitive composition of the present invention on a substrate

[0540] (2) A step of irradiating the coating film of the photosensitive composition with active chemical rays through a photomask

[0541] (3) A step of developing the photosensitive composition using a developer to form a pattern

[0542] (4) A step of heating the pattern to obtain a cured pattern of the photosensitive composition

[0543] In addition, in these processes, the methods described in paragraphs

[0453] to

[0481] of International Publication No. 2019 / 087985 may also be applied. The process of forming a coating film is preferably to form a film by pre-baking after coating. The process of obtaining a cured pattern is preferably to heat the pattern to thermally cure it.

[0544] Example

[0545] The present invention is described in more detail below with reference to Examples, Reference Examples, and Comparative Examples, but the present invention is not limited to these scopes. In addition, for compounds using abbreviations in the following descriptions or the compounds used in the tables, the names corresponding to the abbreviations are shown in Table 1-1.

[0546] [Table 1-1]

[0547]

[0548] <Synthesis Examples of Each Resin>

[0549] As the binder resin (A), the compositions of the resins obtained in Synthesis Examples 1 to 25 are shown in Tables 1-2 to 1-4. Each resin was synthesized by a conventional method by appropriately changing the monomer compound or copolymerization ratio of the monomer based on the method described in the existing literature. The copolymerization ratio of the monomer is as shown in Tables 1-2 to 1-4.

[0550] The hydroxyl-containing diamine (HA) of the following structure used in Synthesis Example 8 was synthesized by a conventional method based on the synthesis method described in Synthesis Example 1 in paragraphs

[0374] to

[0376] of International Publication No. 2016 / 056451. In addition, the resin obtained in Synthesis Example 5 using the hydroxyl-containing diamine (HA) of the following structure is a polyimide precursor having an amic acid ester structural unit, an amic acid structural unit, and an imide closed ring structure.

[0551] [Chemistry 12]

[0552]

[0553] In Synthesis Example 19, based on the synthesis methods described in Synthesis Example 3 and Synthesis Example 5 in paragraphs

[0109] to

[0122] of International Publication No. 2012 / 141165, a phenol compound of the following structure is synthesized as a condensation reaction product of XLN and SAD instead of a condensation reaction product of XLN and 4-hydroxybenzaldehyde, and the obtained phenol compound is used for a condensation reaction with an aldehyde compound.

[0554] [Chemistry 13]

[0555]

[0556] In Synthesis Examples 8 and 11, DFA as an esterifying agent was reacted with the amic acid structural unit in the resin to convert the structure thereof into an amic acid ester structural unit having a methyl group.

[0557] In Synthesis Examples 9 and 10, HEMA or GDMA was reacted with ODPA as tetracarboxylic dianhydride to allow all the anhydride groups of ODPA to undergo ring-opening addition, and then BAHF as a bisaminophenol compound and EtOH as a capping agent were reacted with the carboxyl groups derived from ODPA.

[0558] In Synthesis Example 18, GMA having an epoxy group was reacted with the carboxyl group derived from MAA in the resin to cause all the epoxy groups of GMA to undergo ring-opening addition.

[0559] In Synthesis Example 24, DHBA having a carboxyl group was reacted with the epoxy group derived from GMA in the resin to cause all the epoxy groups of GMA to undergo ring-opening addition.

[0560] In Synthesis Example 25, GMA having an epoxy group was reacted with the phenolic hydroxyl group derived from HPMA in the resin to cause ring-opening addition of all the epoxy groups of GMA.

[0561]

[0562]

[0563]

[0564] Regarding the resins obtained in each synthesis example and the resins used in each example, reference example, and comparative example, the structural units and structures of each resin are shown in Table 2-1.

[0565] [Table 2-1]

[0566]

[0567] Table 2-2 shows a list of (D) colorants and (E) dispersants used in each of Examples, Reference Examples, and Comparative Examples, along with their descriptions.

[0568] In addition, (AR52-BB7) is a dye obtained by mixing and stirring at AR52 / BB7 = 1 / 1 (mol ratio), filtering the precipitated salt, washing it three times with water, and drying it.

[0569] [Table 2-2]

[0570]

[0571] <Each colorant>

[0572] · Bk-CBF1 is a benzofuranone-based black pigment having a coating layer described in paragraphs

[0503] to

[0505] and Coating Example 1 of International Publication No. 2019 / 087985.

[0573] Bk-CPR1 is a perylene-based black pigment having a coating layer obtained by the synthesis method described in paragraphs

[0186] to

[0188] and

[0191] of International Publication No. 2018 / 038083 and Example 18.

[0574] <Preparation Example of Each Pigment Dispersion Liquid>

[0575] As the pigment dispersion, the composition of each dispersion obtained in Preparation Example Bk-1 to Preparation Example Bk-6 is shown in Table 2-3. In Preparation Example Bk-1 to Preparation Example Bk-6, each pigment dispersion was prepared by the following method.

[0576] Preparation Example Bk-1 to Preparation Example Bk-6 Preparation of Pigment Dispersion Liquid (Bk-1) to Pigment Dispersion Liquid (Bk-6)

[0577] 35.0 g of a polyalkyleneamine-polyoxyalkylene ether dispersant, i.e., ADP (paragraphs

[0138] to

[0141] of Japanese Patent Laid-Open No. 2020-070352, pigment dispersant 1 described in Synthesis Example 2) and 765.0 g of PGMEA as a solvent were weighed and mixed, stirred for 10 minutes and diffused, and then 100.0 g of the black pigment described in Table 2-3 as a colorant was weighed and mixed, and stirred for 30 minutes to obtain a pre-mixed liquid. The pre-mixed liquid is sent to a vertical bead mill in which a container (vessel) is filled with 0.40 mmφ ceramic beads as a grinding medium, which are a composite oxide of zirconium and hafnium elements (ZrO2-HfO2) with a purity of more than 90 mass %, and the grinding medium contains composite oxides (zirconium oxide (ZrO2) / hafnium oxide (HfO2) / yttrium oxide (Y2O3) / aluminum oxide (Al2O3) = 93.3 / 1.5 / 4.9 / 0.3 (mass ratio)), and the first wet media dispersion treatment is carried out at a peripheral speed of 8 m / s for 3 hours in a circulation manner. Furthermore, the liquid was sent to a vertical bead mill filled with a 0.05 mm φ pulverizing medium containing a composite oxide (zirconium oxide (ZrO2) / hafnium oxide (HfO2) / yttrium oxide (Y2O3) / aluminum oxide (Al2O3) = 93.3 / 1.5 / 4.9 / 0.3 (mass ratio)) as a pulverizing medium in a container, and a second wet medium dispersion treatment was performed in a circulation manner at a peripheral speed of 9 m / s in such a manner that the average primary particle diameter of the pigment became the value described in Table 2-3. Afterwards, filtration was performed using a 0.80 μm φ filter to obtain a pigment dispersion (Bk-1) to a pigment dispersion (Bk-6) having a solid content concentration of 15% by mass and a colorant / dispersant = 100 / 35 (mass ratio). The average primary particle diameter of the pigment in the obtained pigment dispersion is shown in Table 2-3.

[0578] [Table 2-3]

[0579] [Table 2-3]

[0580]

[0581] <Synthesis Example of Silica Particle Dispersion Liquid>

[0582] Table 2-4 shows a list of silica particles, which are inorganic particles, used in each of Examples, Reference Examples, and Comparative Examples, together with their descriptions.

[0583] Synthesis Example 26 Synthesis of Silica Particle (SP-1) Dispersion

[0584] Into a three-necked flask, weigh and add 104.5g of MEK as a solvent, 142.5g of MEK-ST-40 as a dispersion of silica particles containing sodium elements, and 0.01g of MOP as a polymerization inhibitor and mix, stir for 10 minutes, and then raise the liquid temperature to 50°C. Then, it takes 10 minutes to drip a solution in which 3.0g of KBM-503 as a surface modifier is dissolved in 50.0g of MEK. After the dropwise addition is completed, stir at 50°C for 2 hours to dehydrate and condense the surface modifier. After the reaction, the reaction solution is cooled to room temperature to obtain a dispersion of silica particles (SP-1). The obtained silica particles (SP-1) have a surface modification group containing a methacryloyl group as a free radical polymerizable group.

[0585] In addition, regarding (MSiP-1) as a dispersion liquid of silica particles (SP-2), MEK-ST-40 was used as a dispersion liquid of silica particles containing sodium element, KBM-13 was used as a surface modifier, MOP as a polymerization inhibitor was not used, and silica particles having a surface modifier containing a methylsilyl group were synthesized by the same method as Synthesis Example 20. In addition, regarding (MSiP-2) as a dispersion liquid of silica particles (SP-3), MEK-ST-L was used as a dispersion liquid of silica particles containing sodium element, KBM-13 was used as a surface modifier, MOP as a polymerization inhibitor was not used, and silica particles having a surface modifier containing a methylsilyl group were synthesized by the same method as Synthesis Example 20.

[0586] [Table 2-4]

[0587] [Table 2-4]

[0588]

[0589] <Evaluation Methods in Examples, Reference Examples, and Comparative Examples>

[0590] The evaluation methods in each embodiment, reference example, and comparative example are shown below. In addition, a glass substrate (manufactured by Geomatec; hereinafter referred to as "ITO / Ag substrate") in which APC (silver / palladium / copper = 98.07 / 0.87 / 1.06 (mass ratio)) is formed into a 100 nm film on glass by sputtering, and a 10 nm film of ITO is formed on the upper layer of the APC layer by sputtering is used after UV-O3 cleaning treatment for 100 seconds using a desktop optical surface treatment device (PL16-110; manufactured by SEN Special Light Source Co., Ltd.). Tempax glass substrate (manufactured by AGC Techno Glass Co., Ltd.), polyethylene terephthalate (hereinafter referred to as "PET") film, polypropylene (hereinafter referred to as "PP") film, and alumina substrate were used without pretreatment. The other substrates were heated at 130°C for 2 minutes using a hot plate (HP-1SA; manufactured by ASONE) and subjected to dehydration baking treatment. In addition, the film thickness was measured using a surface roughness / contour shape measuring machine (SURFCOM 1400D; manufactured by Tokyo Seimitsu Co., Ltd.) at a measurement magnification of 10,000 times, a measurement length of 1.0 mm, and a measurement speed of 0.30 mm / s.

[0591] (1) Weight average molecular weight of the resin

[0592] Regarding the polyimide (PI-1) to polyimide (PI-7), polyimide precursor (PIP-1) to polyimide precursor (PIP-4), polybenzoxazole (PB-1), polybenzoxazole precursor (PBP-1), and polyamide-imide (PAI-1), each resin was dissolved in N-methyl-2-pyrrolidone to prepare a 0.10 mass % N-methyl-2-pyrrolidone solution. Using a GPC analyzer (Waters 2690; manufactured by Waters), the weight average molecular weight converted to polystyrene was measured under the following measurement conditions to obtain the result.

[0593] <GPC measurement conditions>

[0594] Detector: Waters 996

[0595] System controller: Waters 2690

[0596] Column oven: Waters HTR-B

[0597] Thermal controller: Waters TCM

[0598] Column: TOSOH Guard Column

[0599] Column: TOSOH TSK-GELα-4000

[0600] Column: TOSOH TSK-GELα-2500

[0601] Mobile layer: N-methyl-2-pyrrolidone with 0.050 mol / L lithium chloride and phosphoric acid dissolved in each

[0602] Development speed: 0.40mL / min.

[0603] For other resins, a GPC analyzer (HLC-8220; manufactured by TOSOH Corporation) was used, and tetrahydrofuran or N-methyl-2-pyrrolidone was used as a fluidized layer. The weight average molecular weight in terms of polystyrene was measured by a method near room temperature based on "Japanese Industrial Standards (JIS) K7252-3 (2008)".

[0604] (2) Average primary particle size of the pigment in the pigment dispersion

[0605] Using a dynamic light scattering particle size distribution measuring device (SZ-100; manufactured by Horiba, Ltd.), the laser wavelength was set to 532nm, PGMEA was used as a dilution solvent, the dilution ratio was set to 250 times (weight ratio), the solvent viscosity was set to 1.25, the solvent refractive index was set to 1.40, the measurement temperature was set to 25°C, the measurement mode was set to scattered light, and the calculation condition was set to polydispersity·wide, and the D50 (median particle size) in the pigment dispersion was measured. In addition, the number of measurements was set to two, and the average value was set to the average primary particle size of the pigment in the pigment dispersion.

[0606] (3) Average primary particle size of the pigment in the cured film

[0607] A cured film of the composition was prepared by the method described in Example 1 below. The cross section of the cured film was photographed and analyzed using a transmission electron microscope to measure the primary particle size of the pigment. The average value of 30 primary particles of the pigment was measured as the average primary particle size of the pigment in the cured film.

[0608] (4) Content of the specific aromatic compound, specific organic acid, specific nitrogen-containing compound, specific carboxylic acid, and specific oxime compound in the composition or in the cured film

[0609] The content of a specific aromatic compound, a specific organic acid, a specific nitrogen-containing compound, a specific carboxylic acid, or a specific oxime compound in the composition or the cured film is measured by gas chromatography mass spectrometry and liquid chromatography mass spectrometry using a calibration curve based on a standard substance. In addition, the content in the total solid content of the composition is calculated from the obtained measured value and the following formula.

[0610] (Content in the total solid content of the composition) = (Content in the composition) x 100 / (Concentration of solid content in the composition [mass %]).

[0611] (5) Content of specific anions in the composition or cured film

[0612] The content of specific anions in the composition or in the cured film is determined by ion chromatography under the following measurement conditions. The composition or cured film is added to a 10 mmol / L potassium hydroxide aqueous solution, shaken for 2 hours, and the ion components are extracted. After filtering the extract under the following conditions, the cationic components and anionic components are analyzed by ion chromatography. The record without ion content means that the ion was not detected. In addition, the content in the total solid content of the composition is calculated from the obtained measured value and the following formula.

[0613] (Content in the total solid content of the composition) = (Content in the composition) × 100 / (Concentration of solid content in the composition [mass %])

[0614] <Filtration treatment conditions>

[0615] Membrane filter: 0.22 μmφ, PVDF (manufactured by Merck Millipore)

[0616] Solid phase extraction cartridge: InertSep Slim-J PLS-3 (manufactured by GL Sciences)

[0617] Cationic replacement cartridge: OnGuard II H (manufactured by Thermo Fisher Scientific)

[0618] <Ion chromatography analysis conditions>

[0619] Device: ICS-5000 + (Manufactured by Thermo Fisher Scientific)

[0620] Separation column: 2mmφ×250mm, IonPac AS11-HC-4μm

[0621] Eluent: Potassium hydroxide / gradient

[0622] Detector: Conductivity detector

[0623] Sample injection volume: 100 μL.

[0624] (6) Content of specific metal element in the composition or cured film

[0625] The content of a specific metal element in the composition or the cured film is measured by inductively coupled plasma mass spectrometry and inductively coupled plasma emission spectrometry using a calibration curve based on a standard substance. The content of the metal element in the total solid content of the composition is calculated from the obtained measured value and the following formula.

[0626] (Content in the total solid content of the composition) = (Content in the composition) x 100 / (Concentration of solid content in the composition [mass %]).

[0627] (7) Contents of fluorine, chlorine, bromine, and sulfur in the composition or cured film

[0628] The contents of fluorine, chlorine, bromine, and sulfur in the composition or cured film are measured by combustion ion chromatography under the following measurement conditions. The composition or cured film is burned and decomposed in the combustion tube of the analysis device, and the generated gas is absorbed in the absorption liquid, and then a part of the absorption liquid is analyzed by ion chromatography. The absence of an element content indicates that the element was not detected. In addition, the content in the total solid content of the composition is calculated from the obtained measurement value and the following formula.

[0629] (Content in the total solid content of the composition) = (Content in the composition) × 100 / (Concentration of solid content in the composition [mass %])

[0630] <Combustion-absorption conditions>

[0631] System: AQF-2100H, GA-210 (Made by Mitsubishi Chemical Corporation)

[0632] Electric furnace temperature: Inlet 900℃, Outlet 1000℃

[0633] Gas: Ar / O2 200mL / min, O2 400mL / min

[0634] Absorption liquid: H2O2 0.1 mass%

[0635] Absorption volume: 5mL

[0636] <Ion chromatography-anion analysis conditions>

[0637] System: ICS1600 (manufactured by DIONEX)

[0638] Mobile phase: 2.7mmol / L Na2CO3, 0.3mmol / L NaHCO3

[0639] Flow rate: 1.50mL / min

[0640] Detector: Conductivity detector

[0641] Injection volume: 100 μL.

[0642] (8) Water content in the composition

[0643] The water content in the composition was measured by volumetric titration using a Karl Fischer moisture meter (MKS-520; manufactured by Kyoto Electronics Co., Ltd.) and Karl Fischer reagent as a titrating agent in accordance with "JIS K0113 (2005)".

[0644] (9) Sensitivity

[0645] The developed film of the composition was prepared by the method described in Example 1 below. The analysis pattern of the developed film prepared was observed using an FPD / LSI inspection microscope (OPTIPHOT-300; manufactured by Nikon). As an index of sensitivity, the exposure amount (i-ray illuminometer value) that can form a space pattern equivalent to an opening with a width of 18 μm in a 20 μm line and space pattern is set as sensitivity. The sensitivity is determined as follows: 90 mJ / cm 2 The following A+, A, B+, B, C+, and C are considered qualified, and the sensitivity is 60mJ / cm 2 The following A+, A, B+, and B are considered good, and the sensitivity is 40mJ / cm 2 The following A+ and A are considered excellent.

[0646] A+: Sensitivity is 30mJ / cm 2 the following

[0647] A: Sensitivity exceeds 30mJ / cm 2 And 40mJ / cm 2 the following

[0648] B+: Sensitivity exceeds 40mJ / cm 2 And 50mJ / cm 2 the following

[0649] B: Sensitivity exceeds 50mJ / cm 2 And 60mJ / cm 2 the following

[0650] C+: Sensitivity exceeds 60mJ / cm 2 and 75mJ / cm 2 the following

[0651] C: Sensitivity exceeds 75mJ / cm 2 And 90mJ / cm 2 the following

[0652] D: Sensitivity exceeds 90mJ / cm 2 And 150mJ / cm 2 the following

[0653] E: Sensitivity exceeds 150mJ / cm 2 .

[0654] (10) Development residue

[0655] The developed film of the composition was prepared by the method described in Example 1 below. The analysis pattern of the prepared developed film was observed using an FPD / LSI inspection microscope (OPTIPHOT-300; manufactured by Nikon Corporation). As an indicator of development residue, the presence or absence of residue in the pattern corresponding to the opening portion was observed in the 20 μm line and space pattern. The following judgment was made: A+, A, B+, B, C+, and C with a residue area of ​​less than 20% were qualified, A+, A, B+, and B with a residue area of ​​less than 10% were good, and A+ and A with a residue area of ​​less than 3% were excellent.

[0656] A+: No residue

[0657] A: The area of ​​residue is less than 3%.

[0658] B+: The area of ​​residue is more than 3% and less than 6%.

[0659] B: The area of ​​the residue is more than 6% and less than 10%

[0660] C+: The area of ​​residue is more than 10% and less than 15%.

[0661] C: The area of ​​residue is more than 15% and less than 20%

[0662] D: The area of ​​the residue is more than 20% and less than 50%.

[0663] E: The area where the residue exists is more than 50% and not more than 100%.

[0664] (11) Light-shielding property (optical density value (hereinafter referred to as “OD value”))

[0665] A cured film of the composition was prepared on a Tempax glass substrate (manufactured by AGC Techno Glass) by the method described in Example 1 below. The incident light intensity (I0) and the transmitted light intensity (I) at three locations within the surface of the prepared cured film were measured using a transmission density meter (X-Rite 361T(V); manufactured by X-Rite). As an index of light-shielding properties, the OD value per film thickness of 1 μm was calculated using the following formula, and the average OD value at three locations within the surface was calculated.

[0666] OD value = log 10 (I0 / I).

[0667] (12) Mechanical properties (elongation at break)

[0668] Using the method described in Example 1 below, a cured film of the composition with a film thickness of about 5 μm is made on a 6-inch diameter SiO2 / Si wafer. Using dilute hydrofluoric acid, the cured film is peeled off from the SiO2 / Si wafer. The peeled cured film is cut into strips of 1.5 cm in width × 9.0 cm in length. Using tensilon (RTM-100; manufactured by Orientec), a tensile test is performed at a room temperature of 23.0°C and a humidity of 45.0% RH at a tensile speed of 50 mm / min to determine the elongation at breaking point. In addition, 10 strips of one sample were measured. As an indicator of mechanical properties, the average value of the top 5 is calculated based on the results obtained. The results were judged as follows: A+, A, B+, B, C+, and C with an elongation at break of 5.0% or more were considered acceptable, A+, A, B+, and B with an elongation at break of 10% or more were considered good, and A+ and A with an elongation at break of 20% or more were considered excellent.

[0669] A+: Elongation at breaking point is more than 30%

[0670] A: Elongation at break is 20% or more and less than 30%

[0671] B+: Elongation at break is 15% or more and less than 20%

[0672] B: Elongation at break is 10% or more and less than 15%

[0673] C+: Elongation at break is 7.5% or more and less than 10%

[0674] C: Elongation at break is 5.0% or more and less than 7.5%

[0675] D: Elongation at break is 1.0% or more and less than 5.0%

[0676] E: The elongation at break was less than 1.0% or could not be measured.

[0677] (13) Migration resistance (insulation reliability)

[0678] Using the method described in Example 1 below, a cured film of the composition with a film thickness of about 1.5 μm was prepared on a migration evaluation substrate (WALTS-TEG ME0102JY; manufactured by Walts). Subsequently, in the line and space pattern of the copper wiring of the comb teeth, a wire was welded at the position of the measurement terminal of 15 μm on the line and 10 μm in the space to prepare an evaluation element. The insulation reliability of the prepared evaluation element under high temperature and high humidity was evaluated using an insulation degradation characteristic evaluation system (ETAC SIR13; manufactured by Kusumoto Chemicals Co., Ltd.). The evaluation element was placed in a high temperature and high humidity tank with the test conditions set to a temperature of 85°C and a humidity of 85% RH, a voltage of 5.0 V was applied, and the change in resistance over time was measured at intervals of 5 minutes. When the resistance value reached 1.0×10 6 If the value is less than Ω, it is judged as poor insulation, and the test time at this time is measured as an index of migration resistance. It is judged as follows: A+, A, B+, B, C+, and C with a test time of more than 200 hours are qualified, A+, A, B+, and B with a test time of more than 400 hours are good, and A+ and A with a test time of more than 800 hours are excellent.

[0679] A+: Test time is more than 1,000 hours

[0680] A: The test time is more than 800 hours and less than 1,000 hours.

[0681] B+: The test time is more than 600 hours and less than 800 hours

[0682] B: The test time is more than 400 hours and less than 600 hours

[0683] C+: The test time is more than 300 hours and less than 400 hours

[0684] C: The test time is more than 200 hours and less than 300 hours

[0685] D: The test time is more than 50 hours and less than 200 hours

[0686] E: The test time is less than 50 hours or the measurement is impossible.

[0687] <Compounds used in Examples, Reference Examples, and Comparative Examples>

[0688] The structures of the compounds used in the examples, reference examples, and comparative examples are shown below: (b-1) to (b-9), (c-1) to (c-9), (f-1) to (f-3), (i-1), (j-1), (k-1), and (NQD-1).

[0689] In addition, (b-1) and (b-2) are equivalent to the compound (B-1), and (b-3) and (b-4) are equivalent to the compound (B-2). (b-5) is equivalent to the compound (B-3), and the minimum number of atoms in the structure (I-b3) is 4. (b-6), (b-7), (b-8), and (b-9) are equivalent to the compound (B-4), and the minimum number of atoms in the structure (I-b4) is 13 for (b-6), 23 for (b-7), 31 for (b-8), and 17 for (b-9).

[0690] (i-1) is a dissolution promoter having a hydrophobic structure (an ethylene group having a phenyl ...

[0691] (j-1) is a fluorenone compound which is a sensitizer.

[0692] (k-1) is an organic silane compound which is a silane coupling agent serving as an adhesion improving agent and has an epoxy group.

[0693] [Chemistry 14]

[0694]

[0695] [Chemistry 15]

[0696]

[0697] [Chemistry 16]

[0698]

[0699] [Chemistry 17]

[0700]

[0701] In addition, the specific aromatic compounds used in each embodiment, reference example, and comparative example; compounds containing specific anions; specific organic acids; specific nitrogen-containing compounds; compounds containing specific metal elements; specific carboxylic acids; specific oxime compounds; compounds containing fluorine, chlorine, bromine, or sulfur (hereinafter referred to as "compounds containing specific elements") and their corresponding compounds are shown in Tables 2-5.

[0702] [Table 2-5]

[0703]

[0704] <Preparation of photosensitive composition 1>

[0705] Composition 1 to composition 157 were prepared according to the compositions described in Table 3-1 to Table 3-12. The values ​​in brackets in Table 3-1 to Table 3-12 represent the mass parts of the solid content of each component. When the composition contains a pigment, a mixed solution that does not contain a pigment dispersion is first prepared, and then the pigment dispersion and the mixed solution are mixed to prepare the composition. As a solvent, PGMEA / EL / GBL=50 / 40 / 10 (mass ratio) was used, and the composition was prepared in a manner such that the solid content concentration was 20% by mass. The solution of the obtained composition was filtered using a 0.45μmφ filter for use.

[0706] The addition amounts of the specific aromatic compound and water were prepared so that the contents in the composition would have the compositions described in Tables 3-1 to 3-12, respectively.

[0707] The added amounts of the compound containing a specific anion, the compound containing a specific metal element, and the compound containing a specific element are prepared in such a way that the content of the specific anion, the content of the specific organic acid, the content of the specific metal element, and the content of the fluorine element, the chlorine element, the bromine element, and the sulfur element in the total solid content of the composition become the compositions described in Tables 3-1 to 3-12, respectively.

[0708] The addition amounts of the specific organic acid, the specific nitrogen-containing compound, the specific carboxylic acid, and the specific oxime compound were prepared so that the contents in the total solid content of the composition would have the compositions described in Tables 3-1 to 3-12, respectively.

[0709] [Table 3-1]

[0710] [Table 3-1]

[0711]

[0712] [Table 3-2]

[0713] [Table 3-2]

[0714]

[0715] [Table 3-3]

[0716] [Table 3-3]

[0717]

[0718] [Table 3-4]

[0719] [Table 3-4]

[0720]

[0721] [Table 3-5]

[0722] [Table 3-5]

[0723]

[0724]

[0725]

[0726]

[0727]

[0728]

[0729]

[0730]

[0731] <Example 1>

[0732] Composition 1 was applied to an ITO / Ag substrate using a spin coater (MS-A100; manufactured by Mikasa Corporation), and then pre-baked at 120° C. for 120 seconds using a buzzer hot plate (HPD-3000BZN; manufactured by ASONE Corporation) to prepare a pre-baked film having a film thickness of about 1.8 μm. The prepared pre-baked film was spray-developed using a 2.38 mass % TMAH aqueous solution or cyclopentanone using a small developer for lithography (AD-1200; manufactured by Takizawa Sangyo Co., Ltd.), and the time (Breaking Point; hereinafter referred to as “BP”) at which the pre-baked film (unexposed portion) was completely dissolved was measured.

[0733] The same method was used to prepare a pre-baked film. For the prepared pre-baked film, a double-sided alignment single-sided exposure device (mask alignment exposure machine PEM-6M; manufactured by United Optical Co., Ltd.) and a grayscale mask for dielectric sensitivity measurement (MDRMMODEL 4000-5-FS; manufactured by Opto-Line International) were used to perform patterned exposure with i-rays (wavelength 365nm), h-rays (wavelength 405nm), and g-rays (wavelength 436nm) of an ultra-high pressure mercury lamp. After exposure, a small developing device for photolithography (AD-1200; manufactured by Takizawa Sangyo Co., Ltd.) was used to develop with a 2.38 mass% TMAH aqueous solution, and a developed film was prepared by rinsing with water for 30 seconds. The development time was set to 1.3 times the measured BP. In addition, when a pattern cannot be formed after development with a 2.38 mass % TMAH aqueous solution, an exposed film is prepared in the same manner as the method described above, and after exposure, a small developing device for lithography (AD-1200; manufactured by Takizawa Sangyo Co., Ltd.) is used to develop with cyclopentanone and rinse with water for 30 seconds to prepare a developed film. The development time is set to 1.3 times the measured BP. The pattern after development is observed to determine the optimal exposure amount (i-ray illuminometer value) for forming a space pattern equivalent to an opening portion with a size width of 18 μm in a 20 μm line and space pattern. After exposure at the optimal exposure amount, the developed pattern is thermally cured at 220°C for 60 minutes using a high-temperature inert gas oven (INH-9CD-S; manufactured by Koyo Thermosystem) to prepare a cured film with a film thickness of about 1.2 μm. Regarding the thermal curing conditions, the temperature was raised to 220°C at a heating rate of 3.5°C / min in a nitrogen environment with an oxygen concentration of 20 mass ppm or less, and heat treatment was performed at 220°C for 60 minutes, followed by cooling to 50°C.

[0734] The cured film was analyzed by nuclear magnetic resonance spectroscopy, infrared spectroscopy, and time-of-flight secondary ion mass spectrometry, and the structural unit of the resin contained in the cured film was analyzed. It was confirmed that the cured film of composition 1 prepared by the above method contained the following resin. That is, the cured film of composition 1 contained a resin having a structure derived from the resin contained in composition 1.

[0735] (XA1) Resin: a resin having a structural unit represented by the general formula (1); a resin having a structural unit represented by the general formula (2)

[0736] <Example 2 to Example 152 and Comparative Examples 1 to 5>

[0737] The same operation and evaluation as in Example 1 were performed using the compositions shown in Tables 3-1 to 3-12. The evaluation results are shown in Tables 4-1 to 4-12. In addition, for easy comparison, the composition and evaluation results of Example 1 are described in Tables 3-2 to 3-8 and Tables 4-2 to 4-8, respectively. In addition, the composition and evaluation results of Example 1, Example 115, and Example 119 are described in Tables 3-9 and 4-9, respectively. In addition, the composition and evaluation results of Example 123 are described in Tables 3-10 and 4-10, respectively. In addition, the content of fluorine element in the total solid content of the composition and the content of fluorine element in the cured product in Examples 1 to 144 and Comparative Examples 1 to 5 exceeded 1,000 mass ppm. The content of fluorine element in the total solid content of the composition and the content of fluorine element in the cured product in Examples 145 to 148 was 0 mass ppm. The content of fluorine element in the total solid content of the composition in Examples 149 to 152 is as described in Table 3-11, and the content of fluorine element in the cured product is as described in Table 4-11.

[0738] In addition, regarding the thermal curing conditions of Example 142, the temperature was raised to 200°C at a heating rate of 3.5°C / min in a nitrogen environment with an oxygen concentration of less than 20 mass ppm, and after a heat treatment at 200°C for 60 minutes, it was cooled to 50°C. In addition, in each of the above embodiments, when a composition having positive photosensitivity is used, a photomask in which the light-transmitting portion and the light-shielding portion are reversed is used. The development time is set to 60 seconds, 90 seconds, or 120 seconds, and a grayscale mask for sensitivity measurement (MDRMMODEL 4000-5-FS; manufactured by Opto-Line International) is used to determine the optimal exposure (i-ray illuminometer value) for forming a space pattern equivalent to the opening portion with a size width of 20μm in a 20μm line and space pattern. Based on these results, the optimal development time (60 seconds, 90 seconds, or 120 seconds) and the optimal exposure under the development time are determined. After exposure at the most preferred exposure amount, the pattern developed at the most preferred development time was thermally cured at 200° C. for 60 minutes. Regarding the thermal curing conditions, the temperature was raised to 200° C. at a heating rate of 3.5° C. / min in a nitrogen environment with an oxygen concentration of 20 mass ppm or less, and after heat treatment at 200° C. for 60 minutes, it was cooled to 50° C.

[0739] [Table 4-1]

[0740] [Table 4-1]

[0741]

[0742] [Table 4-2]

[0743] [Table 4-2]

[0744]

[0745]

[0746] [Table 4-4]

[0747] [Table 4-4]

[0748]

[0749] [Table 4-5]

[0750] [Table 4-5]

[0751]

[0752]

[0753]

[0754]

[0755] [Table 4-9]

[0756] [Table 4-9]

[0757]

[0758]

[0759]

[0760]

[0761] Comparative Examples 1 and 2 did not contain the specific aromatic compound, the compound containing the specific anion, and the specific organic acid, and therefore were inferior in development residue, mechanical properties, and migration resistance.

[0762] The content of the specific aromatic compound in Comparative Example 3 exceeds 1,000 mass ppm. The content of the specific organic acid in Comparative Example 4 exceeds 1,000 mass ppm. The content of the specific anion in Comparative Example 5 exceeds 1,000 mass ppm. Comparative Examples 3, 4, and 5 do not satisfy Condition (1x), Condition (2x), and Condition (3). Therefore, any of the characteristics of development residue, mechanical properties, and migration resistance are poor.

[0763] <Comparative Example 6>

[0764] In Comparative Example 3, a composition 155 was prepared in which the content of the specific aromatic compound in the composition was 1,500 ppm by mass. The obtained composition 155 was stored at 25° C. for one week. After the storage, when the composition was formed into a film on a substrate in the same manner as in Example 1, a large amount of foreign matter was generated, and the storage stability of the composition was poor.

[0765] <Comparative Example 7>

[0766] In Comparative Example 4, a composition 156 was prepared in which the content of the specific organic acid in the total solid content of the composition was 1,500 ppm by mass. The obtained composition 156 was stored at 25° C. for one week. After the storage, when the composition was formed into a film on a substrate in the same manner as in Example 1, a large amount of foreign matter was generated, and the storage stability of the composition was poor.

[0767] <Comparative Example 8>

[0768] In Comparative Example 5, a composition 157 was prepared in which the content of the specific anion in the total solid content of the composition was 1,500 ppm by mass. The obtained composition 157 was stored at 25° C. for one week. After the storage, when the composition was formed into a film on a substrate in the same manner as in Example 1, a large amount of foreign matter was generated, and the storage stability of the composition was poor.

[0769] <Example 153>

[0770] In Example 1, a composition 1 was prepared in which the content of the specific aromatic compound in the composition was 3 mass ppm, and the content of the specific organic acid in the total solid content of the composition was 3 mass ppm. The obtained composition 1 was stored at 25° C. for one week. After storage, when the composition was formed into a film on a substrate in the same manner as in Example 1, no foreign matter was generated, and the storage stability of the composition was good.

[0771] <Example 154>

[0772] In Example 14, a composition 14 was prepared in which the content of the specific aromatic compound in the composition was 3 mass ppm, and the content of the specific anion in the total solid content of the composition was 3 mass ppm. The obtained composition 14 was stored at 25° C. for one week. After storage, when the composition was formed into a film on a substrate in the same manner as in Example 1, no foreign matter was generated, and the storage stability of the composition was good.

[0773] <Preparation of photosensitive composition 2>

[0774] Composition 158 was prepared with the same solid content composition as Composition 1 described in Table 3-1, using GBL as a solvent, so that the solid content concentration of the composition was 60% by mass. Similarly, Composition 159 was prepared with the same solid content composition as Composition 22, using GBL as a solvent, so that the solid content concentration of the composition was 60% by mass. The obtained solution of the composition was filtered using a 1.0 μmφ filter before use.

[0775] <Example 155>

[0776] Composition 158 was coated on a 50 μm thick PET film using a notch roll coater and then dried at 120° C. for 8 minutes. Subsequently, a 30 μm thick PP film was laminated as a protective film to obtain a photosensitive composition film having a composition 158, a PET film as a support, and a PP film as a protective film. The PP film as a protective film was peeled off from the obtained photosensitive composition film, and then the peeled surface was laminated onto a 5 cm×5 cm alumina substrate using a vacuum film laminator (MVLP-500 / 600; manufactured by Meiki Seisakusho Co., Ltd.) under the conditions of upper and lower hot plate temperatures of 80° C., vacuum suction time of 20 seconds, vacuum pressing time of 30 seconds, and lamination pressure of 0.5 MPa to form a photosensitive composition film on the alumina substrate. After that, the PET film as the support film was peeled off, and a photomask having a pattern of through-hole sizes of 20 μmφ and 10 μmφ and a pattern of line / space widths of 40 μm / 20 μm and 20 μm / 10 μm was set in the exposure device. Under the condition that the exposure gap between the photomask and the photosensitive composition film was 100 μm, an ultra-high pressure mercury lamp equipped with an i-ray bandpass filter was used at an exposure dose of 200 mJ / cm 2 、300mJ / cm 2 、400mJ / cm 2 , and 500mJ / cm 2(value of the i-ray illuminometer) for patterned exposure. After exposure, a 2.38 mass % TMAH aqueous solution or cyclopentanone is used and developed by immersion development, and isopropyl alcohol or water is used for rinsing for 30 seconds to prepare a developed film after pattern processing of the photosensitive composition film. The development time is set to twice the time for the unexposed part to be completely dissolved. The developed pattern is thermally cured in the same manner as in Example 1 to prepare a cured film of the photosensitive composition. The evaluation is performed in the same manner as in Example 1. In Example 155, the content of fluorine element in the total solid content of the composition and the content of fluorine element in the cured product exceed 1,000 mass ppm. In addition, the sensitivity and development residue of the photosensitive composition film are evaluated by the method described below. The evaluation results of the photosensitive composition film using a photosensitive composition film having a composition 158 are as follows: sensitivity A, development residue A, mechanical properties A, and migration resistance B+.

[0777] The sensitivity of the photosensitive composition film is evaluated by the following method. A developed film in which the photosensitive composition film is patterned is prepared by the method described in Example 155. An FPD / LSI inspection microscope (OPTIPHOT-300; manufactured by Nikon) is used to observe the analysis pattern of the prepared developed film. As an indicator of sensitivity, the exposure amount (the value of the i-ray illuminance meter) that can form a spatial pattern equivalent to an opening with a size width of 20 μm in a pattern with a line width / space width of 40 μm / 20 μm is set as the sensitivity. The sensitivity is determined as follows: 900 mJ / cm 2 The following A+, A, B+, B, C+, and C are considered qualified, and the sensitivity is 600mJ / cm 2 The following A+, A, B+, and B are considered good, and the sensitivity is 400mJ / cm 2 The following A+ and A are considered excellent.

[0778] A+: Sensitivity is 300mJ / cm 2 the following

[0779] A: Sensitivity exceeds 300mJ / cm 2 And 400mJ / cm 2 the following

[0780] B+: Sensitivity exceeds 400mJ / cm 2 And 500mJ / cm 2 the following

[0781] B: Sensitivity exceeds 500mJ / cm 2 And 600mJ / cm 2 the following

[0782] C+: Sensitivity exceeds 600mJ / cm 2and 750mJ / cm 2 the following

[0783] C: Sensitivity exceeds 750mJ / cm 2 And 900mJ / cm 2 the following

[0784] D: Sensitivity exceeds 900mJ / cm 2 and 1,500mJ / cm 2 the following

[0785] E: Sensitivity exceeds 1,500mJ / cm 2 .

[0786] The development residue of the photosensitive composition film is evaluated by the following method. A developed film in which the photosensitive composition film is patterned is prepared by the method described in Example 155. An FPD / LSI inspection microscope (OPTIPHOT-300; manufactured by Nikon) is used to observe the analysis pattern of the prepared developed film. As an indicator of the development residue, the presence or absence of residue in the pattern corresponding to the opening portion is observed in a pattern with a line width / space width of 40μm / 20μm. It is determined as follows: A+, A, B+, B, C+, and C with a residue area of ​​less than 20% are qualified, A+, A, B+, and B with a residue area of ​​less than 10% are good, and A+ and A with a residue area of ​​less than 3% are excellent.

[0787] A+: No residue

[0788] A: The area of ​​residue is less than 3%.

[0789] B+: The area of ​​residue is more than 3% and less than 6%.

[0790] B: The area of ​​the residue is more than 6% and less than 10%

[0791] C+: The area of ​​residue is more than 10% and less than 15%.

[0792] C: The area of ​​residue is more than 15% and less than 20%

[0793] D: The area of ​​the residue is more than 20% and less than 50%.

[0794] E: The area where the residue exists is more than 50% and not more than 100%.

[0795] <Example 156>

[0796] The same operation and evaluation as in Example 155 were performed using Composition 159. In Example 156, the content of fluorine element in the total solid content of the composition and the content of fluorine element in the cured product exceeded 1,000 mass ppm. The evaluation results of the photosensitive composition film using the photosensitive composition coating having Composition 159 were as follows: sensitivity was A, development residue was A+, mechanical properties were A+, and migration resistance was A+.

[0797] Description of Figure Numbers

[0798] 1 Si wafer

[0799] 2 Al pad

[0800] 3 Passivation layer

[0801] 4 Insulation layer

[0802] 5 Metal Layer

[0803] 6 Metal wiring

[0804] 7 Insulation layer

[0805] 8 barrier metal layer

[0806] 9 Strike

[0807] 10 Solder Bumps

Claims

1. A photosensitive composition comprising (A) a binder resin and (C) a photosensitizer, and further comprising (B) a radical polymerizable compound and / or (F) a crosslinking agent, wherein: The (A) binder resin contains the following (A1) resin and / or (A2) resin, Satisfy the following conditions (α); (A1) Resin: A resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin (A2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin (α) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (1x) (1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

2. The photosensitive composition according to claim 1, wherein the sulfonic acid, and the phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, and phosphinate ester (hereinafter referred to as "organic acid containing phosphorus element") have the following specific substituent a, The carboxylic acid containing fluorine element has the following specific substituent b, The condition (α) is the following condition (α2), and satisfies the following condition (α2); (α2) further contains one or more selected from the group consisting of a sulfonic acid having the following specific substituent a, an organic acid containing a phosphorus element having the following specific substituent a, and a carboxylic acid containing a fluorine element having the following specific substituent b, and satisfies the following condition (1y): Specific substituent a: one or more selected from the group consisting of a monovalent aliphatic group to a divalent aliphatic group having 1 to 18 carbon atoms, a monovalent alicyclic group to a divalent alicyclic group having 4 to 18 carbon atoms, a monovalent aromatic group to a divalent aromatic group having 6 to 15 carbon atoms, a monovalent fluorinated aliphatic group to a divalent fluorinated aliphatic group having 1 to 18 carbon atoms, a monovalent fluorinated alicyclic group to a divalent fluorinated alicyclic group having 4 to 18 carbon atoms, and a monovalent fluorinated aromatic group to a divalent fluorinated aromatic group having 6 to 15 carbon atoms Specific substituent b: one or more selected from the group consisting of monovalent fluorinated aliphatic groups to divalent fluorinated aliphatic groups having 1 to 18 carbon atoms, monovalent fluorinated alicyclic groups to divalent fluorinated alicyclic groups having 4 to 18 carbon atoms, and monovalent fluorinated aromatic groups to divalent fluorinated aromatic groups having 6 to 15 carbon atoms (1y) The total content of the sulfonic acid having the specific substituent a, the organic acid containing phosphorus having the specific substituent a, and the carboxylic acid containing fluorine having the specific substituent b in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

3. The photosensitive composition according to claim 2, wherein the condition (α2) is the following condition (α3), and the following condition (α3) is satisfied: The sulfonic acid contains one or more selected from the group consisting of methanesulfonic acid, cyclohexanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, xylenesulfonic acid, trifluoromethanesulfonic acid, hexafluorocyclohexanesulfonic acid, hexafluorobenzenesulfonic acid, pentafluorotoluenesulfonic acid, tetrafluoroxylenesulfonic acid, trifluoromethylbenzenesulfonic acid, trifluoromethyltoluenesulfonic acid, and trifluoromethylxylenesulfonic acid. The carboxylic acid containing fluorine element contains at least one selected from the group consisting of trifluoroacetic acid, trifluoropropionic acid, hexafluorocyclohexanecarboxylic acid, hexafluorobenzoic acid, and trifluoromethylbenzoic acid; (α3) further contains sulfonic acid and / or carboxylic acid containing fluorine element and satisfies the following condition (1z): (1z) The total content of the sulfonic acid and the carboxylic acid containing a fluorine element in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

4. The photosensitive composition according to claim 1, further satisfying the following condition (β): (β) further contains one or more selected from the group consisting of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (2x): (2x) The total content of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is 0.010 to 1,000 ppm by mass.

5. The photosensitive composition according to claim 1, further satisfying the following condition (γ): (γ) further contains one or more selected from the group consisting of benzene, toluene, xylene, and naphthalene, and satisfies the following condition (3) (3) The total content of benzene, toluene, xylene, and naphthalene in the photosensitive composition is 0.010 to 1,000 ppm by mass.

6. The photosensitive composition according to any one of claims 1 to 5, wherein the (A) binder resin comprises the (A1) resin, The (A1) resin contains one or more selected from the group consisting of the following (A1-1) resin, (A1-2) resin, (A1-3) resin, (A1-4) resin, (A1-5) resin, (A1-6) resin, and copolymers containing two or more of these resins. (A1-1) Resin: Polyimide (A1-2) Resin: Polyimide precursor (A1-3) Resin: polybenzoxazole (A1-4) Resin: polybenzoxazole precursor (A1-5) Resin: Polyamide-imide (A1-6) Resin: polyamideimide precursor.

7. The photosensitive composition according to claim 6, further comprising at least one selected from the group consisting of a cyclic amide compound represented by the general formula (20), an amide compound represented by the general formula (21), a cyclic urea compound represented by the general formula (22), a urea compound represented by the general formula (23), an oxazolidinone compound represented by the general formula (24), and an isoxazolidinone compound represented by the general formula (25), and the composition satisfies the following condition (4). (4) The total content of the cyclic amide compound represented by the general formula (20), the amide compound represented by the general formula (21), the cyclic urea compound represented by the general formula (22), the urea compound represented by the general formula (23), the oxazolidinone compound represented by the general formula (24), and the isoxazolidinone compound represented by the general formula (25) in the total solid content of the photosensitive composition is 0.010% by mass to 5.0% by mass [Chemistry 1] (In general formula (20) to general formula (25), R 46 ~R 56 R each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 4 to 10 carbon atoms, an aryl group having 6 to 15 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; 130 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyalkyl group having 1 to 6 carbon atoms, a hydroxyalkoxy group having 1 to 6 carbon atoms, a hydroxy group, an amino group, a monoalkylamino group having 1 to 6 carbon atoms, or a dialkylamino group having 2 to 12 carbon atoms; R 131 ~R 142 Each independently represents an alkyl group having 1 to 6 carbon atoms; α, β, and γ each independently represent an integer from 0 to 6; a, b, c, e, f, g, h, i, j, k, l, and m each independently represent an integer from 0 to 2; when α is 0, a is 0; when β is 0, b is 0; when γ is 0, c is 0. ).

8. The photosensitive composition according to claim 7, further comprising at least one selected from the group consisting of a component containing sodium, a component containing potassium, a component containing magnesium, a component containing calcium, a component containing iron, a component containing copper, and a component containing chromium, and the composition satisfies the following condition (5). (5) The total content of the sodium element, potassium element, magnesium element, calcium element, iron element, copper element, and chromium element in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass. 9 . The photosensitive composition according to claim 1 , wherein the (C) photosensitizer contains a (C1) photopolymerization initiator, and the (C1) photopolymerization initiator contains a (C1-1) oxime ester compound and / or a (C1-2) phosphine oxide compound.

10. The photosensitive composition according to claim 9, further comprising at least one selected from the group consisting of acetic acid, propionic acid, cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, and trimethylbenzoic acid, and satisfying the following condition (6), and / or It also contains an aldoxime compound and / or a ketoxime compound and satisfies the following condition (7); (6) The total content of acetic acid, propionic acid, cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, and trimethylbenzoic acid in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass. (7) The total content of the aldoxime compound and the ketoxime compound in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass.

11. The photosensitive composition according to claim 10, further comprising at least one selected from the group consisting of a component containing a chlorine element, a component containing a bromine element, and a component containing a sulfur element, and satisfying the following conditions (8) and / or (9), and / or It also contains water and satisfies the following condition (10); (8) The total content of chlorine and bromine in the total solid content of the photosensitive composition is 0.010 to 500 ppm by mass. (9) The content of sulfur in the total solid content of the photosensitive composition is 0.010 ppm by mass to 500 ppm by mass (10) The content of water in the photosensitive composition is 0.010 mass % to 3.0 mass %.

12. The photosensitive composition according to any one of claims 1 to 5 and 9 to 11, further satisfying the following condition (1α), (1α) The content of fluorine element in the total solid content of the photosensitive composition is 1,000 ppm by mass or less.

13. The photosensitive composition according to any one of claims 1 to 5 and 9 to 11, further satisfying at least one of the following conditions (δ), (ε), and (ζ), (δ) The (B) radical polymerizable compound contains the following (B1) first polymerizable compound and (B2) second polymerizable compound (ε) The (B) radical polymerizable compound contains the following (B3) third polymerizable compound and (B4) fourth polymerizable compound (ζ) The (B) radical polymerizable compound contains the following (B1) first polymerizable compound or (B2) second polymerizable compound, and further contains the following (B3) third polymerizable compound or (B4) fourth polymerizable compound (B1) First polymerizable compound: a compound having the following structure (I-b1) and having at least two free radical polymerizable groups (I-b1) Structure: Structure containing an alicyclic structure and / or structure containing a heteroalicyclic structure (B2) Second polymerizable compound: a compound having the following structures (I-b2) and (II-b2) and having at least two free radical polymerizable groups (I-b2) Structure: Structure containing an aromatic structure (II-b2) Structure: Structure containing aliphatic structure (B3) Third polymerizable compound: a compound having at least two (meth)acryloyl groups and further having the following structure (I-b3) (I-b3) Structure: A structure containing an aliphatic structure in which at least two (meth)acryloyl groups are linked with a minimum number of 4 to 10 atoms. (B4) Fourth polymerizable compound: a compound having at least two (meth)acryloyl groups and further having the following structure (I-b4): (I-b4) Structure: a structure in which at least two (meth)acryloyl groups are linked with each other by a minimum number of atoms of 11 to 45 and which contains an aliphatic structure.

14. The photosensitive composition according to any one of claims 1 to 5 and 9 to 11, further comprising (G) inorganic particles, The (G) inorganic particles include one or more selected from the group consisting of silicon dioxide particles, aluminum oxide particles, titanium oxide particles, vanadium oxide particles, chromium oxide particles, iron oxide particles, cobalt oxide particles, copper oxide particles, zinc oxide particles, zirconium oxide particles, niobium oxide particles, tin oxide particles, and cerium oxide particles.

15. A photosensitive composition comprising (A) a binder resin and (C) a photosensitizer, and further comprising (B) a radical polymerizable compound and / or (F) a crosslinking agent, wherein: The (A) binder resin contains the following (A1) resin and / or (A2) resin, Satisfying one or more selected from the group consisting of the following conditions (α), (β), and (γ); (A1) Resin: A resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin (A2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin (α) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (1x) (1x) the total content of sulfonic acid, phosphoric acid, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphinic acid ester, and carboxylic acid containing fluorine in the total solid content of the photosensitive composition is 0.010 mass ppm to 1,000 mass ppm (β) it also contains one or more selected from the group consisting of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion, and satisfies the following condition (2x) (2x) the total content of chloride ion, bromide ion, sulfate ion, sulfite ion, nitrate ion, nitrite ion, phosphate ion, phosphite ion, hypophosphite ion, formate ion, and fluoride ion in the total solid content of the photosensitive composition is 0.010 mass ppm to 1,000 mass ppm (γ) further contains one or more selected from the group consisting of benzene, toluene, xylene, and naphthalene, and satisfies the following condition (3) (3) The total content of benzene, toluene, xylene, and naphthalene in the photosensitive composition is 0.010 to 1,000 ppm by mass. 16 . A photosensitive composition film comprising a photosensitive composition coating film obtained by forming the photosensitive composition according to claim 1 , and a support.

17. A cured product obtained by curing the photosensitive composition according to any one of claims 1 to 5, 9 to 11, and 15.

18. An electronic component comprising the hardened material according to claim 17.

19. A method for producing a cured product, comprising: (1) forming a coating film of the photosensitive composition according to any one of claims 1 to 5, 9 to 11, and 15 on a substrate; (2) a step of irradiating the coating film of the photosensitive composition with active chemical rays through a photomask; (3) a step of developing the photosensitive composition using a developer to form a pattern; and (4) A step of heating the pattern to obtain a cured pattern of the photosensitive composition.

20. An electronic component comprising a hardened material, wherein: The cured product contains the following (XA1) resin and / or (XA2) resin, Satisfy the following conditions (Xα); (XA1) Resin: a resin containing one or more selected from the group consisting of an imide structure, an amide structure, an oxazole structure, and a siloxane structure in the structural unit of the main chain of the resin (XA2) Resin: A resin having a phenolic hydroxyl group in the structural unit of the main chain of the resin (Xα) further contains one or more selected from the group consisting of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite, phosphinic acid, phosphite, and carboxylic acid containing fluorine element, and satisfies the following condition (X1x): (X1x) The total content of sulfonic acid, phosphoric acid ester, phosphonic acid, phosphonic acid ester, phosphite ester, phosphinic acid, phosphinate ester, and carboxylic acid containing fluorine element in the cured product is 0.010 to 1,000 ppm by mass.

Citation Information

Patent Citations

  • Resin composition and display device using the same

    JP2007016214A

  • Positive photosensitive resin composition

    JP2012208360A

  • Pigment dispersion, negative photosensitive composition, and cured product

    JP2020070352A

  • Positive photoresist composition, coating film thereof, and novolac phenol resin

    WO2012141165A1

  • Negative-type photosensitive resin composition, cured film, and organic el display and manufacturing method therefor

    WO2019087985A1